Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Mining and floods: a systematic review of empirical studies on community resilience strategies and interventions - Mariam Bouzid; William J. Guerrero; Luz Elba Torres-Guevara; Dairo Steven Muñoz Pinzón; Carlos Daniel Montes Rodriguez; Lady Giovanna Rojas Pineda; Juan José Díaz Castro; Erika Cardona Patiño; Karol Elkjaer Mondragon Sanchez (The Extractive Industries and Society, 2026)

Ecological and economic outcomes of area-based conservation and sustainable fisheries management in the Mediterranean Sea - M. D. Castro-Cadenas; J. Claudet; M. Ortega; V. Sbragaglia; M. Coll (Reviews in Fish Biology and Fisheries, 2026)
Intergovernmental targets are reinforcing the need for more sustainable fisheries and more effective marine conservation. It is now urgent to understand how area-based conservation and sustainable fisheries management tools contribute to these environmental and socio-economic goals. Here, we systematically reviewed and assessed the outcomes of marine protected areas (accounting for their level of protection and of enforcement), fisheries restricted areas, and fishing effort reduction measures in the Mediterranean Sea, using 11 ecological and economic indicators. We show that commercial species in general, and fish species in particular, showed the highest proportion of positive to neutral effects in response to the management tools assessed compared to non-commercial and benthic assemblages. Among the management tools, partially protected areas showed the lowest proportion of positive to neutral effects compared to fully protected areas, and to the other management tools. Partially protected areas and fully protected areas showed higher neutral to negative ratio than fishing effort reduction measures overall. Within MPA protection levels with high enforcement, fully protected areas outperformed minimally protected areas, based on the higher positive to neutral effects ratio. Our results further underscored the critical role of enforcement, particularly for fully protected areas, which were found more beneficial overall under high enforcement than medium enforcement (based on positive to neutral effects ratio). Our findings support the prioritisation of well enforced fully protected areas and the integration of fisheries management and conservation objectives in marine spatial planning to effectively achieve regional and global sustainability goals for the ocean.

Vasoactive intestinal peptide advances chondrogenesis and modulates pathogenic mediators in human osteoarthritis - Karolina Tecza; Cristina Rodríguez-Hernández; Raúl Villanueva-Romero; David Castro-Vázquez; Alicia Cabrera-Martín; Paula Arribas-Castaño; Mar Carrión; Irene Gutiérrez-Cañas; Raquel Largo; Valentina Calamia; Francisco J. Blanco; Rosa P. Gomariz; et al. (Journal of Molecular Medicine, 2026)

Use of microsensor platform to differentiate metabolic parameters associated with developmental timing and sex of individual bovine blastocysts - Ming-Hao Cheng; Kyle J. Fresa; Raul A. Gonzalez-Castro; Adam J. Chicco; Elaine M. Carnevale; Thomas W. Chen (Theriogenology, 2026)

Optimization of magnetic nanostructured materials for cyanotoxin removal by oxidation and regeneration methods - Alejandro Cao; Natalia Vilariño; Lisandra de Castro Alves; Yolanda Piñeiro; José Rivas; María J. Sainz; Cristina Carrera; Almudena Graña; Ana M. Botana; Luis Rodríguez-Santos; M. Carmen Louzao; Luis M. Botana (Journal of Environmental Sciences, 2026)

Chemical environment of an acidic Hibiscus sabdariffa beverage and its role in early amylolytic interactions in a starch-based food system - Sofia Guadalupe Chairez-Huerta; José P. Tejeda-Miramontes; Alicia Paulina Cárdenas-Castro; Edgar J. Mendivil; Jorge Alberto Sánchez-Burgos; Sonia Guadalupe Sáyago-Ayerdi (Food Research International, 2026)

Detection by PCR of Borrelia theileri in ticks and anti-rGlpQ antibodies in cattle from Guanajuato, Mexico - Sofía L. Luna-Rojas; José Luis Gutiérrez-Hernández; Edwin Vázquez-Guerrero; Jose Alberto Hernández-Martínez; Rigoberto Hernández-Castro; Paulina Estrada-de los Santos; J. Antonio Ibarra (Veterinary Research Communications, 2026)

Integrating cytotoxicity and NMR-based metabolomics to uncover bioactive aporphine alkaloids and pentacyclic triterpenoids from Siparuna guianensis - Salva Asghar; Cibele A. Cesila; Gracimerio J. Guarneire; Samira C. C. Ludgero; Sandra B. R. Castro; Alessandra P. Carli; Caio César S. Alves; Danielle F. Dias; Marisi G. Soares; Nerilson M. Lima (Natural Product Research, 2026)

Prenatal fluoride exposure and motor development among infants in Los Angeles, California - Durdana Khan; Sandrah P. Eckel; Ixel Hernandez-Castro; Howard Hu; Tingyu Yang; Shohreh F. Farzan; Carrie V. Breton; Theresa M. Bastain; Ashley J. Malin (Environmental Research, 2026)

When taxonomy lags behind evolution: Conservation implications of cryptic diversity in the Iberian rabbit - Rafael Villafuerte; Paulo C. Alves; Miguel Carneiro; Francisca Castro; Pedro J. Esteves; Julia E. Fa; Nuno Ferrand; Vicente Piorno; João Queiros; Carlos Rouco; Patricia H. Vaquerizas; Miguel Delibes-Mateos (Biological Conservation, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Photocatalytic caffeine degradation and toxicity reduction using reduced graphene oxide-modified zinc telluride - A. J. Vilvert; P. D. Macruz; R. P. Nippes; H. C. L. Geraldino; L. V. de Castro-Hoshino; I. R. Bautitz; J. C. G. Moraes (International Journal of Environmental Science and Technology, 2026)
The occurrence of emerging pollutants in aquatic matrices has raised environmental concern because of their persistence and potential toxicity. This study assessed caffeine degradation and toxicity reduction using zinc telluride functionalized with reduced graphene oxide as heterogeneous photocatalyst. The catalysts were synthesized by the wet impregnation method with excess solvent, and characterized by physicochemical and optical techniques. The results indicated zinc telluride nanoparticles distributed on the surface of reduced graphene oxide sheets, together with changes in textural and optical properties, including a lower band gap for the composites. Photocatalytic tests were performed using a mercury vapor lamp emitting ultraviolet–visible radiation, with the main emission at 365 nm. The effects of reduced graphene oxide content, catalyst loading, initial caffeine concentration, and pH variation were evaluated. Under the tested experimental conditions, the composite containing 1.0% reduced graphene oxide showed the highest degradation performance, reaching 93% caffeine degradation in 85 min. The degradation profile was best described by the half-order kinetic model. The reduced photoluminescence intensity suggests lower electron–hole recombination, although direct confirmation of reactive species requires complementary analyses. Toxicity tests indicated lower Artemia salina mortality and improved Lactuca sativa germination after treatment with the 1.0% reduced graphene oxide-modified zinc telluride catalyst. The results indicate that reduced graphene oxide incorporation can improve caffeine photodegradation and reduce toxicity under the evaluated conditions.

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Seasonal Variability of Residence Time and Ocean Exchange in a Semi-enclosed Gulf in Northwestern Australia - Camille M. Grimaldi; Michael V. W. Cuttler; Johan Reyns; Jessica A. Benthuysen; Carolina Castro-Sanguino; Luke Thomas; James P. Gilmour; Ryan J. Lowe (Estuaries and Coasts, 2026)
Coastal water exchange with the open ocean plays a key role in regulating the transport and distribution of nutrients, heat, pollutants, suspended sediments and organisms in semi-enclosed systems. In this study, we quantify coastal water exchange for Exmouth Gulf (Australian North West Shelf), a globally significant water body adjacent to the Ningaloo Coast World Heritage Area. We use a high-resolution (200 m) hydrodynamic model, along with particle tracking, to quantify the spatiotemporal variation in circulation, water residence times, and export from the Gulf to the adjacent ocean. Water residence times in Exmouth Gulf are primarily influenced by tidal and wind forcing, with wind waves providing an additional, though secondary, contribution. The shortest Gulf residence times occurred in spring (∼52 days) and the longest in winter (∼276 days). Spatially (and across seasons), residence times within specific subregions were shortest near the western entrance (< 1 day), and longest in the southern Gulf (> 49 days). Export to the ocean was strongest during winter (albeit relatively small, accounting for only 5% of all particles), whereas during the rest of the year particles predominantly remained along the wide, shallow continental shelf to the north-east of the Gulf. Connections between the Gulf and the Ningaloo Coast World Heritage Area varied seasonally in strength, reflecting changes in the regional circulation drivers. Overall, the seasonality of regional wind patterns (via surface currents and wind waves) shaped the residence time and export of material and organisms to surrounding areas. We show that wind waves reduce residence times by up to 15% in parts of the Gulf and thus are an important component of system modelling. A thorough understanding of such dynamics is critical to make informed decisions about the conservation and management of the area.

Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Sexually dimorphic organization of extracellular matrix and perineuronal nets in the prairie vole (Microtus ochrogaster) social brain - Analía E. Castro; Natalia Uriarte; Daniel Zangrando; Francisco J. Camacho; Raúl G. Paredes; Wendy Portillo; Javier Nogueira (Brain Structure and Function, 2026)

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Medicinal plant discrimination in Paramos and cloud forests of northern Peru: A study of deep learning techniques and a novel approach for data augmentation - W. Castro; M. Juarez; D. Gálvez-Paucar; V. Tirado; J. Gonzáles; F. Torres-Guevara (Remote Sensing Applications: Society and Environment, 2026)

Trophic ecology of two discarded elasmobranchs (Scyliorhinus canicula and Torpedo marmorata) in a NE Atlantic trawl fishery (Gulf of Cádiz) - C. Fernández-Oliveras; C. Rodríguez-García; J. Sarmiento-Carbajal; R. Cabrera-Castro (Marine Environmental Research, 2026)

Mechanisms of porphyrin-mediated photohemolysis of erythrocytes - Lais Alonso; Iouri E. Borissevitch; Fabio Castro Bezerra; Antonio Alonso; Pablo J. Gonçalves (Journal of Photochemistry and Photobiology B: Biology, 2026)

Mn/Co-modified CaO pellets bound with mesoporous γ-Al2O3 for thermochemical energy storage: balancing energy-storage density, mechanical strength and solar absorptance - D. Castro-Yáñez; A. Peral; J. González-Aguilar; M. Romero; E.S. Sanz-Pérez; L. Briones; J.M. Escola (Journal of Cleaner Production, 2026)

Impacts of bottom trawl fishing in the Juan Fernández ridge, Chile - I. Petit; J.M. Tapia-Guerra; C.F. Gaymer; J. Sellanes; M. Castro-Contreras; M.-A. Gallardo; E.E. Easton; L. Watling; I. Payá (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Hydrological controls on carbon accumulation in sedimentary environments of a Peruvian high-Andean lacustrine system - Renzo Gonzales; Héctor Aponte; Rodrigo Castro; James Apaéstegui; Jorge Cardich; Jaime Rivera; Wilson Machado; Christian J. Sanders; Matthieu Carré; Alexander Pérez (Journal of Paleolimnology, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

A Framework-Based Evaluation of Open Data Platforms in European Ports: A Comparative Study of Barcelona and Antwerp–Bruges - Lucas Freitas; Ana J. Mendes; Marcela Castro; Tiago Pinho (Journal of Marine Science and Engineering, 2026)
Open data platforms (ODPs) are emerging as strategic infrastructures for smart port development within the European Union, yet there is limited research offering integrated approaches to evaluate their performance across technical, operational, and regulatory dimensions. To address this gap, this study develops an analytical framework combining four complementary perspectives: open data platform design, FAIR (Findability, Accessibility, Interoperability, and Reusability) principles, smart port enablement, and EU regulatory alignment. The framework is applied through a qualitative comparative case study of the Ports of Barcelona and Antwerp–Bruges, based exclusively on secondary data sources, including the academic literature, policy documents, and publicly accessible platform data. The analysis is structured around three analytical dimensions—FAIR and interface features and accessibility, smart port enablement, and EU regulatory alignment—applied consistently across both cases. The findings reveal two distinct models: Barcelona adopts an open-by-default approach prioritising accessibility, transparency, and integration with public data ecosystems, while Antwerp–Bruges follows a controlled-access model focused on operational integration, system reliability, and business-to-business data exchange. Both approaches align with EU policy frameworks but involve different trade-offs between openness and operational control. The study contributes a structured, transferable framework for evaluating port ODPs and identifies practices for their design and governance in smart port and maritime logistics contexts.

Prenatal exposure to metal mixtures and mitochondrial DNA content and telomere length in newborns: Potential modulation by TERT gene variants - Marvin Paz-Sabillón; Emilio J. Córdova; Luisa Torres-Sánchez; Nereida Montes-Castro; Luz M. Del Razo; Betzabet Quintanilla-Vega (Environmental Pollution, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Mapping and quantifying nature’s contributions to people underpinning international food trade: the case of the Brazilian coffee and soy supply-chains - Gabriela Rabeschini; Antonio J. Castro; Abhishek Chaudhary; María R. Felipe-Lucia; Thomas Koellner; Kira Lancker; Alexandra Marques; Stephan Pfister; Catharina J. E. Schulp; Louise Willemen; Thomas Kastner (Sustainability Science, 2026)

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Influence of climate variability and shark interactions on artisanal deep-water fisheries in Spain's largest marine reserve - David Jiménez-Alvarado; Ana Espino-Ruano; Airam Guerra-Marrero; Julián Cabana-Gandiaga; Tomas Bañeras; José J. Castro-Hernández; Lorena Couce-Montero (Marine Environmental Research, 2026)

New findings on the performance of anaerobic reactors: Ecotoxicological assessment of sublethal effects of antibiotic mixtures in wastewater on freshwater invertebrates - Gleyson B. Castro; Mateus Cottorello-Fonsêca; Tallyson T.C. de Souza; David S. Alexandre; Juliano J. Corbi (Journal of Environmental Chemical Engineering, 2026)

Effect of graphene quantum dot size on the capacitance of rGO-based supercapacitors fabricated with a sustainable electrolyte (seawater) - R.A. Mendoza-Jiménez; J. Oliva; T.A. Esquivel-Castro; C. Rodriguez-Gonzalez; P. Salas (Chemical Engineering Journal, 2026)

Parametrization of scour protection deformation around mud mats and pile clusters of complex jacket offshore substations - J. Sarmiento; R. Guanche; A. Álvarez; J. Castro (Coastal Engineering, 2026)

Trees just go “nuts”: prioritizing carbon allocation to yield in almond trees - Shreya S. Veeravelli; Andrew J. McElrone; Ian R. Wright; Mina Momayyezi; Kyle R. Knipper; Nicolas E. Bambach; Sebastian Castro Bustamante; Andrew J. Gal; Sat Darshan S. Khalsa; Ranjith Karunakaran; Hung T. T. Nguyen; Morgan E. Furze (Planta, 2026)
Main conclusion Almond trees prioritize C to yield rather than stem growth, and their overall lower NSC stores compared to forest trees may have consequences for resilience under environmental variability. Abstract Perennial tree crops store nonstructural carbohydrates (NSCs) as energy reserves that can be used to persist during both predictable periods of reduced activity like dormancy and more unpredictable periods associated with stress. For deciduous tree crops, which lose their leaves at the start of dormancy, the NSC reserves accrued by that time are critically important for fueling respiration but may also influence processes in the following growing season. To quantify the seasonal NSC fluctuation surrounding dormancy and its influence on downstream processes like growth and yield, we conducted a comparative study of four almond varieties in a commercial orchard (California, USA). Sugar and starch concentrations were quantified in branch, stem, and coarse root when entering and exiting dormancy. We then assessed the correlation between these NSC data and metrics of stem growth and yield in the following growing season. We further explored long-term trade-offs between stem growth and yield using historical data from 2017 to 2022. Overall, total NSC concentrations significantly decreased during the dormant season in all organs. We observed a significant positive correlation between branch total NSC concentration when entering dormancy and yield the next year. However, we unexpectedly found that stem total NSC concentrations when entering dormancy were negatively correlated with stem growth the next year, suggesting that stem reserves were primarily used to support wintertime respiration or translocated to other organs. A long-term trade-off between stem growth and yield was evident; as yield increased, basal area increment tended to decrease. Additionally, we found whole-tree NSC storage to be lower in almond trees compared to temperate forest trees, reflecting prioritization to yield over NSC storage. Overall, these findings advance our understanding of crop tree carbon physiology and provide insight into the resilience of different almond cultivars under changing environmental conditions.

Encapsulated Amazonian Microalgae Reduce Ammonia and Improve Survival of Female Poecilia reticulata During Simulated Transport - Marianela Cobos; Marcos J. Guerra; Leonardo J. Pizarro; Gladys R. Panduro; Danitza E. Ampudia; Freddy O. Espinoza-Campos; Carlos G. Castro; Juan C. Castro (Fishes, 2026)
The accumulation of un-ionized ammonia (NH3) during the transport of live ornamental fish poses a critical threat to animal welfare and post-transport survival. This study evaluated the efficacy of calcium alginate-encapsulated native Amazonian microalgae, Ankistrodesmus sp., Chlorella sp., Scenedesmus sp., and Synechococcus sp., for NH3 bioremediation during a 15-day simulated transport of female Poecilia reticulata. Biometric endpoints were selected using a four-criterion framework, identifying specific growth rate by weight (SGRW), specific growth rate by length (SGRL), and Fulton’s condition factor (K) as essential non-redundant parameters. Time-weighted average (TWA) NH3 served as the primary dose variable for four-parameter log-logistic modeling fitted to biological replicate means (n = 15). Ankistrodesmus sp. and Scenedesmus sp. maintained 97.8% survival and restricted TWA NH3 to 0.036 and 0.047 mg/L, respectively, whereas the empty capsule control reached 6.7% survival and 0.150 mg/L TWA NH3. Kruskal–Wallis tests on biological replicate means confirmed significant treatment effects on all biometric endpoints (SGRW: H(4) = 13.50, ε2 = 0.950; SGRL: H(4) = 13.50, ε2 = 0.95; p

Encapsulation of echium oil by electrospraying and mono- or coaxial spray-drying using plant protein hydrolysates as emulsifiers - Mariana Sisconeto Bisinotto; Inar Alves Castro; Emilia M. Guadix; Pedro J. García-Moreno (Food Chemistry, 2026)

A machine learning framework for California vineyard water status monitoring using sUAS Imagery and short-term meteorological data - Rui Gao; Maria Mar Alsina; Alfonso F. Torres-Rua; Lawrence Hipps; William P. Kustas; Martha Anderson; Héctor Nieto; Andrew J. McElrone; Kyle Knipper; Nicolas Bambach Ortiz; Sebastian J. Castro; John H. Prueger; et al. (Irrigation Science, 2026)
Efficient irrigation management is essential for sustainable crop production under increasing temperatures and tightening water supplies. In vineyards, water status significantly influences vine growth, yield, and fruit quality, and deficit irrigation is often used to impose controlled stress while avoiding damaging levels of water limitation. This creates a practical need for routine, field-scale monitoring of vine water status. In this study, we developed an operational machine-learning framework to estimate grapevine leaf water potential (Ψ leaf ) by integrating daytime sUAS thermal imagery with short-term local meteorological information. When all candidate predictors were included, the trained eXtreme Gradient Boosting (XGB) model achieved R 2 = 0.71, RMSE = 0.14 MPa , and bias = − 0.06 MPa on the independent test dataset. A simplified XGB model using a compact predictor set–maximum air temperature in the 24 h prior to flight, air temperature at flight time, their difference, and canopy temperature – achieved R 2 = 0.63, RMSE = 0.16 MPa , and bias = − 0.06 MPa , with performance not significantly different from the full model at α = 0.05. This reduced-feature formulation supports vineyard-scale Ψ leaf estimation and mapping while maintaining strong predictive skill and low computational burden. Our research highlights the potential for broader applicability, particularly for monitoring rapidly developing hot and dry conditions and supporting adaptive water resource management.

Unstable bridges—exploring the possibilities for “in between” spaces amidst divergent narratives in environmental governance - Blanca González-Mon; Violeta Cabello; Amanda Jiménez-Aceituno; María Mancilla García; Antonio J. Castro; María D. López-Rodríguez; Michele-Lee Moore; Maja Schlüter (Sustainability Science, 2026)
Social-ecological systems increasingly face polarization dynamics that challenge environmental governance. Such polarization implies the development of opposing narratives with limited interaction, each framing environmental problems and solutions in distinct ways. In this study, we analyze a case of narrative polarization around the eutrophication crises of the Mar Menor lagoon in Spain, focusing on how proposed solutions are narrated to address this complex environmental puzzle. We use a mixed-method approach that combines social network analysis and an analysis of narrative practices in interview situations, to investigate whether and how potential solutions to eutrophication in the Mar Menor can be understood as bridging spaces that create opportunities for interaction between divergent societal narratives. Our three-step analysis includes: (a) a network analysis of reports proposing solutions to identify solutions with a bridging role (i.e., those linking reports that otherwise have little overlap in the solutions proposed); (b) a thematic narrative analysis to investigate the solutions proposed by diverse actors; and (c) an analysis of narrative practices around selected bridging solutions to explore if they constitute new spaces where narratives can interact and confront positions - what we call bridging spaces. We suggest this mixed methods approach allows for the identification of potential bridging spaces to mediate polarization and outline directions for future research on both the case study specifically, and on polarization in environmental governance more generally.

Benthic diatoms and phytoplankton diversity in urban streams and ponds: charting a course for conservation - A. T. Castro-Castellon; M. J. Hill; E. Conroy; A. Daw; H. Gurung; J. S. Hernández-Avilés; S. J. Hobbs; V. H. Salinas-Camarillo; I. Thornhill (Biodiversity and Conservation, 2026)
Benthic diatom and phytoplankton communities are key indicators of freshwater ecosystem health and change but remain understudied. A better understanding of their distribution and abundance drivers is crucial for effective biodiversity assessment and conservation. This study adopts a novel, multi-ecosystem approach to examine the seasonal (2019–2020) diversity of benthic diatom assemblages in urban streams and phytoplankton assemblages in ponds across Bristol (UK) and the local environmental factors shaping these communities. Among ponds, winter recorded significantly fewer phytoplankton taxa than summer and autumn. Among streams, patterns of benthic diatom beta diversity indicated higher turnover in autumn than in winter, and among pond habitats, turnover dominated in the summer and autumn seasons, but nestedness explained more of the composition variation in winter. No significant differences in Local Contributions to Beta Diversity (LCBD) were recorded between seasons for either streams or ponds. However, among streams, LCBD was consistently high at sites with elevated phosphorus, indicating how nutrient enrichment can shape unique assemblages. In streams, nitrate emerged as the principal driver of diatom diversity and composition during the autumn season, whilst, pH, ammonium, zinc, and potassium distinguished diatom communities during the winter. In ponds, pH influenced phytoplankton assemblages in summer, possibly through nutrient and inorganic carbon availability changes. However, no strong environmental–species relationships were identified in autumn or winter, suggesting biotic interactions may be more influential during these seasons. We highlight the need for more comprehensive, long-term monitoring for the inclusion of diatoms and phytoplankton in urban freshwater management and conservation strategies.

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

Phytoplankton realized niches along the continental shelf and inner seas of Chilean Patagonia - Catharina Alves-de-Souza; Lautaro Cifuentes; Marcelo H. Gutiérrez; Flavio A. Solís-Mundaca; Valentina Valdés-Castro; Diego A. Narváez; Fabián J. Tapia; Giovanni Daneri; Paulina Montero; Heide Schulz-Vogt; Camila Fernández (Progress in Oceanography, 2026)

Floral scent differentiation among species of the root-holoparasitic family Lennoaceae and its implications for pollination ecology - Nadia Castro-Cárdenas; Pactli F. Ortega-González; Francisco J. Espinosa-García; Daniel Sánchez; Yolanda M. García-Rodríguez; Sonia Vázquez-Santana (Biochemical Systematics and Ecology, 2026)

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

On the globally distributed genus Gryllodes Saussure, 1874 (Orthoptera: Gryllidae: Gryllinae) as a non-native presence in the Americas: taxonomy, morphology, bioacoustics, new records, and species distribution modeling - Riuler Corrêa Acosta; Rodrigo Antônio Castro-Souza; Oscar J. Cadena-Castañeda; Luiz Augusto Padilha Santos; Maria Kátia Matiotti da Costa; Edison Zefa; Rafael Dudeque Zenni; Gustavo Costa Tavares (International Journal of Tropical Insect Science, 2026)
Non-native insects are often inconspicuous organisms that can negatively impact the economy, biodiversity, and public health. Field crickets (Orthoptera: Gryllidae: Gryllinae) have historically been used as a food source for livestock, pets, and humans—a practice that likely facilitated the spread of certain species into urban centers and non-native habitats. Although rarely cited as invasive, species like Gryllodes sigillatus and Gryllodes supplicans are now widely distributed across diverse environments. Based on recent fieldwork in Brazil, Guatemala, Costa Rica, Colombia, and Ecuador, we conducted morphological and acoustic analyses that confirmed the presence of G. sigillatus in all five countries and documented the first record of G. supplicans in Brazil. We also reassigned Gryllodes flavispina to Loxoblemmus , limiting Gryllodes to two recognized species. This prompted a reassessment of diagnostic traits and the development of global distribution models. Our findings revealed consistent acoustic and morphological differences between the species, facilitating future detection and monitoring. Biogeographic models predict a broad potential distribution and multiple zones of sympatry. Although Gryllodes species are proposed as alternative food, little is known about their ecological impacts if released or escaped into natural ecosystems. Further studies should assess the consequences of their establishment in non-native regions.

Mapping biocultural diversity: An integrative spatial approach to inform conservation and management decisions - Irene Otamendi-Urroz; Juan Miguel Requena-Mullor; Cristina Quintas-Soriano; Graeme S. Cumming; Antonio J. Castro (Ambio, 2026)
Effective conservation and sustainable management require metrics that capture the coupled dynamics of biological and cultural systems. Quantifying and mapping this biocultural diversity remains difficult due to its multidimensional and context-dependent nature. This study introduces the Biocultural Index for Refugia Exploration (BIRE), an integrative spatial approach combining biological and socio-cultural variables to map biocultural diversity. Using publicly available datasets, BIRE applies a percentile-based scoring system to identify biocultural diversity hotspots at the municipal scale. Tested in two contrasting Spanish regions (Almería and Navarra), BIRE revealed distinct spatial patterns, with higher values representing hotspots in rural and mountainous municipalities and lower values (coldspots) in urbanized areas. The index proved robust, flexible, and replicable across diverse social-ecological contexts. BIRE offers a policy-relevant framework linking scientific evidence with decision-making processes. In doing so, BIRE can guide targeted interventions in sustainable management, conservation, and planning, supporting decision-makers in identifying and prioritizing key areas.

Geographic distribution and notes on biology of Plecia plagiata (Wiedemann, 1824) (Diptera: Bibionidae) - Daniel de Castro Schelesky-Prado; Rafaela Lopes Falaschi; Scott J. Fitzgerald; Lívia Maria Fusari (Biologia, 2026)
Plecia plagiata (Wiedemann, 1824) is a species with a wide geographic distribution in the Neotropical region, with records in 20 countries. However, some records are notably vague, only mentioning the occurrence of the species in a certain country or region without a precise locality. This species had records for almost all months of the year, except for April, May, and December. Here, the geographic and seasonal distribution of P. plagiata are extended based on records from iNaturalist, a citizen science social network, and deposited material from scientific collections. In total, new records for 125 first-level administrative divisions in the Neotropical region were reported. The adult morphology and identification are discussed. Additionally, information on feeding habits and reproductive behavior are provided for the first time.

Monitoring the reserve effect of a coastal no-take area in the northeast Atlantic along the first ten years of implementation - Ana Filipa Silva; José Lino Costa; Patrícia Teodoro; João J. Castro; Pedro Raposo de Almeida; Bernardo Ruivo Quintella (Ocean & Coastal Management, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Delayed flowering time when combining warm temperature and short days in barley - Nicolás F. Mastandrea; Ariel J. Castro; Roxana Savin; Gustavo A. Slafer (Plant Science, 2026)

Impact of different hydrodynamic flow regimes on antibiotic removal in anaerobic fixed-bed bioreactors: operational, ecotoxicological and microbiological aspects - Mateus Cottorello-Fonsêca; Gleyson B. Castro; Elias G.F. Rezende; Isabel K. Sakamoto; Francisco R.S. Freitas; Rodrigo B. Carneiro; Carolina A. Sabatini; Rogers Ribeiro; Juliano J. Corbi; Marcelo Zaiat (Journal of Water Process Engineering, 2026)

Ultra-rapid freezing yields a higher cryoresistance than the conventional slow freezing of epididymal guinea pig (Cavia porcellus) spermatozoa - Diego A. Galarza; Christian A. Hernández-Lojano; Anddy J. Salinas-Ulloa; Mauricio Duma; Manuel E. Soria; Gonzalo Castro-Jerez; Juan Pablo Garzón (Cryobiology, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Population dynamics and life history traits of the commercially important jaguar round crab Xantho poressa (Olivi, 1792) in Gran Canaria’s Intertidal Zones (Spain) - Airam Guerra-Marrero; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Regional Studies in Marine Science, 2026)

Analytical estimates for heliocentric escape of satellite ejecta - Jose Daniel Castro-Cisneros; Renu Malhotra; Aaron J. Rosengren (Icarus, 2026)

Understanding and predicting CO2 capacity loss in activated carbons under humid conditions - R. Morales-Ospino; M. Aoun; J. Castro-Gutiérrez; M.T. Izquierdo; A. Celzard; V. Fierro (Chemical Engineering Journal, 2026)

Multispecies weed mapping using deep learning on UAV imagery for SSWM in maize and tomato - G. A. Mesías-Ruiz; I. Borra-Serrano; J. Dorado; A. I. de Castro; J. M. Peña (Precision Agriculture, 2026)
Purpose: Accurate identification and mapping of multiple weed species at early growth stages is a critical step toward operational site-specific weed management (SSWM), yet most UAV-based studies have so far been limited to broad weed categories or single dominant species. This study aimed to evaluate and compare deep learning models for multispecies weed classification, detection and mapping in maize and tomato fields using UAV-based RGB imagery. Methods: Three convolutional neural networks (Inception-ResNet-v2, EfficientNet-B0, YOLOv8) and two Vision Transformers (ViT-Base, Swin-T) were assessed for the classification of nine common weed species. The two best-performing classifiers were then implemented in object detection frameworks (YOLOv8m and DETA), and species-specific treatment maps were generated using adaptive economic weed thresholds applied to gridded density weed data. Results: Swin-T and YOLOv8 achieved the highest classification metrics, with weighted F1-scores of 98.1% and 97.0%, respectively. For object detection, YOLOv8m outperformed DETA, reaching a mean Average Precision of 0.93 and a recall of 0.94, while substantially reducing inference time. The multispecies treatment maps revealed over 70% of weed-free areas, indicating the potential benefits of cost-saving approaches compared to uniform full-field treatments. Conclusions: The proposed workflow enabled accurate multispecies weed classification, detection and mapping at early growth stages, providing valuable inputs for decision support systems and smart sprayers to gradually advance SSWM for a more selective, efficient and sustainable weed control.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Replacing natural savannas with eucalyptus and soybeans changes the matrix use and reduces bat taxonomic and functional diversity in the Amazonian savannas - Bruna S. Xavier; Karen Mustin; Tiago M. Marques; Marcelo M. Ferreira; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Jorge M. Palmeirim; Ana M.C. Santos; Marcus V. Vieira; William D. Carvalho (Agriculture, Ecosystems & Environment, 2026)

Correction: Designing gender-inclusive data systems in small-scale fisheries - Sarah J. Harper; Meryl Williams; Danika Kleiber; Mark Axelrod; Sangeeta Mangubhai; Elin Torell; Gonzalo Macho; Kafayat Fakoya; Nikita Gopal; Elena Ojea; Sarah Lawless; Nicole Franz; et al. (Ambio, 2026)

Designing gender-inclusive data systems in small-scale fisheries - Sarah J. Harper; Meryl Williams; Danika Kleiber; Mark Axelrod; Sangeeta Mangubhai; Elin Torell; Gonzalo Macho; Kafayat Fakoya; Nikita Gopal; Elena Ojea; Sarah Lawless; Nicole Franz; et al. (Ambio, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Strategies to build trustworthiness and increase diversity in colorectal cancer biospecimen research: a multi-phase, multi-site qualitative study - Kristi L. Roybal; Brett Nava-Coulter; Jane Roberts; Destiny Harden; Saul Castro; Anna Revette; Maria Connolly; Gina Johnson; Jennifer A. Rountree; Suzanne Brodney; Kimberly Schoolcraft; David A. Drew; et al. (Journal of Community Genetics, 2026)

Evaluating factors affecting the sample processing for trace analysis of organophosphate tri- and di-esters in seawater: Application in the Loire estuary (France) - P. Zapata-Corella; M. Velázquez-Gómez; C. Pollono; J. Castro-Jiménez (Marine Pollution Bulletin, 2026)

Laboratory investigation and modelling of alternative materials for sub-ballast and formation rehabilitation in a heavy haul railway line - G. Castro; J. Saico; R. Motta; E. Moura; R. Costa; L. Bernucci; A. Paixão; E. Fortunato (Transportation Geotechnics, 2026)

The emerging pollutants polycyclic aromatic compounds (PAH'S) bisphenol a (BPA), and phthalates impair immune system function: Effects on human macrophages - K. Bobadilla-Lozoya; J. Morales-Montor; K.G. Mejía-Salgado; K.E. Nava-Castro (Toxicology in Vitro, 2026)

Plastic occurrence in Macaronesia: Three years of monitoring on forty-six beaches across nineteen islands in an Atlantic region - Cristopher Domínguez-Hernández; Cristina Villanova-Solano; Soledad Álvarez; Sergio J. Álvarez-Méndez; Adeline Alves; João Canning-Clode; Mara de Castro Abu-Raya; Francisco J. Díaz-Peña; Sofia Garcia; May Gómez; Javier González-Sálamo; Cintia Hernández-Sánchez; et al. (Science of The Total Environment, 2026)

Genotoxic and cytotoxic effects of dietary patterns and lifestyle factors: A cross-sectional comparison of Brazilian and Spanish gym users - Diene da Silva Schlickmann; Gabriela Cristina Uebel; Patrícia Molz; Nikolas Mateus Pereira de Souza; Renato Alberto Weber Colombelli; Aline Alves da Luz; Munithele Moraes Eisenhardt; Geovana Andrine Vogt; Caroline Brand; Eliane Aparecida de Castro; Pedro J. Benito; Alexandre Rieger; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Replacing the natural savanna matrix with eucalyptus plantations and soybean fields changes the seed rain promoted by bats in Amazonian savannas - Bruna S. Xavier; Jeferson Vizentin-Bugoni; Marcelo M. Ferreira; Tiago M. Marques; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Karen Mustin; Jorge M. Palmeirim; Marcus V. Vieira; William D. Carvalho (Biological Conservation, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Diverse values of nature can drive transformative change in the WEFE nexus governance in Mediterranean countries - Enrica Garau; Gabriela de Abreu; Irene Perez-Ramirez; Nora Schütze; Yasmine A. Farhat; Jessica Loureiro; Hala El Moussaoui; Olfa Mahjoub; Hacib Amami; Serena Sandri; Nooh Alshyab; Pietro Drei; et al. (Sustainability Science, 2026)
The water–energy–food–ecosystem (WEFE) nexus has emerged as a useful concept to describe and address complex interdependencies in natural resource governance. However, most existing research predominantly emphasizes biophysical and economic dimensions, overlooking the social and cultural dimensions of the nexus and how communities perceive and value these interconnections at diverse local scales. This study aims to bridge this gap by integrating the Diverse Values of Nature framework (IPBES) and the Human–Nature Connectedness (HNC) framework into WEFE nexus research, to explore how communities relate to WEFE systems and how these relations influence and shape the perception of well-being and sustainable natural resources governance. We conducted 110 semi-structured interviews across seven Mediterranean case studies (Spain, Portugal, Morocco, Tunisia, Jordan, and Italy), focusing on agricultural actors. The interviews were analyzed to identify value types (instrumental, intrinsic, and relational), HNC dimensions (material, experiential, cognitive, emotional, and philosophical), and links to diverse components of human well-being, which local actors associated with their WEFE nexus systems across the seven case studies. Results reveal that instrumental values dominate across the analyzed case studies, while intrinsic and relational values also play a crucial role in shaping governance priorities. In addition, the emotional and philosophical dimension of HNC emerged as key leverage points for governance transformations of the WEFE nexus. Additionally, case-specific contrasts and variations (e.g., varying levels of emotional bonds attached to diverse WEFE nexus systems) highlight the important need for applying context-sensitive and place-based approaches. Based on these findings, we argue that integrating non-monetary values, context-sensitive approaches, and human–nature relationships into WEFE governance could be essential for recognizing and supporting diverse worldviews, local knowledge systems, and cultural identities. This study contributes to advancing nexus thinking by demonstrating how social values and human–nature connections, not just monetary or biophysical trade-offs, in systems can inform transformative changes in WEFE nexus approaches and natural resource governance. This study advances nexus thinking beyond technical efficiency, advocating for inclusive, adaptive, and equity-centered approach.

Modelling the diurnal cycle of evapotranspiration using remote sensing models – are we there yet? - K. V. Athira; Eswar Rajasekaran; Kukku Sara; Gilles Boulet; William P. Kustas; Rahul Nigam; Bimal K Bhattacharya; Joseph G. Alfieri; John H. Prueger; Maria Mar Alsina; Lawrence E. Hipps; Lynn G. McKee; et al. (International Journal of Remote Sensing, 2025)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Post-fire recovery of temperate and mediterranean ecosystems: An interplay between fire severity, soil nutrients, and vegetation from early-stage to decadal-scale dynamics - Jhenkhar Mallikarjun; Anna Gorbushina; Yakov Kuzyakov; Moritz Koester; Rodrigo Castro; Anna Yudina; Khaled Abdallah; Francisco J. Matus; Michaela A. Dippold (CATENA, 2025)

Environmental justice gaps in human-wildlife conflict research from a social-ecological systems perspective - Daniela Alba-Patiño; Berta Martín-López; Miguel Delibes-Mateos; Juan M. Requena-Mullor; Antonio J. Castro (Biological Conservation, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Seismicity and active seismic structures in the Valle de la Trinidad, Baja California, Mexico - Boris Rösler; Oscar Castro-Artola; Alejandra Martínez; Carlos E. Reinoza; Luis A. Yegres H.; J. Antonio Vidal-Villegas; Franck A. Audemard M. (Journal of Seismology, 2025)

“Resilience-based framework for enhancing NaTech risk management in industrial critical infrastructures” - David J. Castro Rodriguez; Antonello A. Barresi; Micaela Demichela (Environment Systems and Decisions, 2025)
Industrial facilities, once considered isolated entities, are now approached as complex socio-technical systems that involve intricate networks operating within the confines of the surrounding environment. The increasing frequency of extreme natural events due to climate change has highlighted the vulnerability of industrial plants to NaTech (natural hazards triggering technological scenarios). Current methodologies for NaTech risk assessment focus predominantly on immediate consequences, overlooking the long-term complexities that both industrial systems and their surrounding territories may face. This research proposes a resilience-based framework for NaTech risk management, considering three main stages —awareness, preparedness, recovery—and a loop for continuous learning to address the evolving NaTech challenges. Awareness emphasizes proactive vulnerability characterization under the function-location perspective. It addresses the interactions between industrial plants and multi-hazard contexts by implementing innovative methodological procedures based on qualitative, quantitative, and spatial techniques. Preparedness is supported by an innovative multi-risk tool considering the dynamic vulnerability of equipment categories to individual and overlapped interacting hazards, able to deploy the vulnerability into hierarchical safety layers to design robust and context-specific safer systems. The recovery stage is described through a retrospective case of hydrocarbon pollution caused by rainfall, integrating countermeasures and sustainable technological solutions. Overall, this research highlights the need for multidimensional approaches to tackle the evolving challenges posed by NaTech events. The outcomes present a comprehensive resilience-based framework, and operational procedures guiding the practical implementation of resilience principles and advancing the understanding of complex industrial systems while supporting their long-term sustainability facing natural factors.

Phylogenetic Relationships of the Moles and their Relatives (Talpidae): Insights from Mitogenomes - Sara Sampaio; André Gomes-dos-Santos; L. Filipe C. Castro; Jonathan J. Hughes; Ivan N. Bolotov; Viatcheslav V. Rozhnov; Marina V. Rutovskaya; Ilia G. Meschersky; Joana Paupério; Paulo C. Alves; Jeremy B. Searle; Manuel Lopes-Lima (Evolutionary Biology, 2025)

Anaerobic reactors for hospital wastewater treatment: a critical review of microbial communities in the antibiotic biodegradation and ecotoxicological impacts - Mateus Cottorello-Fonsêca; Gleyson B. Castro; Juliano J. Corbi; Marcelo Zaiat (Biodegradation, 2025)

Where nature is not so green: Exploring perceptions of urban nature in a semi-arid city - Enrica Garau; Juan Miguel Requena-Mullor; Cristina Quintas-Soriano; Gabriela de Abreu; Daniela Alba-Patiño; Antonio J. Castro (Urban Forestry & Urban Greening, 2025)

Magnetic anomalies controlled by surficial dynamics and quaternary drainage patterns in volcanic-derived soils (Tuscania, Italy) - Antonio M. Casas-Sainz; Teresa Román-Berdiel; Juan J. Villalaín; Manuel Castro-Priego; Marta Pérez-Polo; Andrés Pocoví; Pilar Diarte-Blasco (Journal of Applied Geophysics, 2025)

Development of a novel sugaring-out assisted extraction (SoAE) method for zinc determination in milk samples by flame atomic absorption spectrometry with discrete sample introduction - Eduardo da Silva G. de Castro; Ricardo J. Cassella (Food Chemistry, 2025)

Polyphenol profile and associated antioxidant, antiproliferative and anti-inflammatory activities of Mexican Opuntia fruits - N.C. Castro-Alatorre; C. Jiménez-Martínez; J. Girón-Calle; A.G. Garzón; S.R. Drago; J. Vioque (Food Bioscience, 2025)

Scopoletin release modulation in alginate-gums beads analysed by a novel spectrophotometric technique in radiofrequency spectra - Giorgia Frutaz; Pedro J. Fito; María Victoria Traffano-Schiffo; Rafael Gadea-Girones; Marta Castro-Giraldez (Food Hydrocolloids, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Phenolic compounds and epigenetic mechanisms regulating gene expression: effects on human health - Silvia Lorente-Cebrián; André G. V. Costa; J. Andrés Castillo-Rivas; Marta Castro; José Miguel Arbonés-Mainar; Saioa Goñi; Sara Remón; Paula Aranaz; Víctor López; Inmaculada Martín-Burriel; Fermín I. Milagro (Journal of Physiology and Biochemistry, 2025)
Phenolic compounds are a large class of phytochemicals with relevant physiological effects that are naturally found in plant-origin foods and derived products. Beneficial effects associated with polyphenol consumption are related to their ability to prevent and/or counteract disease features: they exert anti-inflammatory, antioxidant and anticancer effects, as well as protective actions against metabolic diseases. Phenolic compounds and their metabolites can modulate cell function by regulating gene expression. These effects are partially mediated through specific changes in epigenetic mechanisms such as DNA methylation, histone modifications and microRNA (miRNA) expression. Some polyphenols affect DNA methylation and are effective in counteracting deleterious actions induced by inflammatory/pro-oxidant factors, both in in vitro and in vivo settings. Specific mechanisms include modulation of methyl-transferases, whose levels are inhibited upon polyphenols treatment. Some polyphenols are histone deacetylase inhibitors, which prevent transcriptional repression and suppress tumor and inflammation genes by affecting selective regulation of miRNA expression. Their mostly recognized actions as anti-inflammatory and antioxidants seem to be partially mediated through regulation of individual miRNAs. Due to these actions, polyphenols and polyphenol-derived metabolites are under study in clinical and interventional trials for their benefits on inflammation and/or metabolic disorders. In conclusion, phenolic compounds might be an interesting approach to contribute to human homeostasis given their capacity to dynamically regulate epigenetic factors at cellular and systemic level. The present review aims to study available evidence regarding regulatory effects of polyphenols on gene expression, specifically mediated through epigenetic mechanisms.

Thermal tolerance and metabolic scope of Sphoeroides annulatus juveniles, a fish with aquaculture potential - Ruth Garcia-Villarreal; Ana Denise Re-Araujo; J. Pablo Sánchez-Ovando; Leonardo Ibarra-Castro; Melany Sánchez-González; Fernando Díaz (Journal of Thermal Biology, 2025)

Design, manufacturing, and performance of innovative aluminium-backed BIPV facade modules: a case-study in Germany - S. Jahreis; B. Jaeckel; R. Koepge; J. Fröbel; P. Schenk; M. Pander; R. Castro (Energy and Buildings, 2025)

Transcriptomic resilience to heat stress in a wide-spread Acropora coral - Declan J. A. Stick; W. Jason Kennington; Carolina Castro-Sanguino; Shannon L. Duffy; Dean Z. Tysdale; James P. Gilmour; Luke Thomas (Coral Reefs, 2025)
As climate change progresses and severe disturbances become routine, understanding rates and mechanisms of recovery in habitat-forming species is central to predicting the broader response of ecosystems to climate change. Here, we combined acute experimental heat stress and RNA sequencing to explore patterns of transcriptome plasticity and resilience to heat stress in a common Acropora coral from the World Heritage-listed Ningaloo Reef. Our data showed that corals subjected to sub-bleaching temperatures (33 ℃) elicited a large transcriptional response during heat stress, but quickly recovered to baseline levels of expression 16 h after temperatures returned to pre-treatment conditions, with no evidence of bleaching. In contrast, corals exposed to a one degree increase (34 ℃) from the sub-bleaching heat treatment, mounted a transcriptional response nearly twice that of the sub-bleaching temperature, showed a lingering stress response in their transcriptome, and eventually bleached. Moreover, variation in the severity of bleaching among colonies was linked to patterns of transcriptome recovery—individuals that bleached heavily showed a larger lag in transcriptional recovery than those with lower levels of bleaching. Together, these findings provide new insight into the genetic mechanisms of heat stress recovery in coral and highlight the role of transcriptional plasticity in the resilience of coral to increasing disturbances.

Sugaring-out assisted extraction (SoAE): A novel approach for the determination of Cd and Pb in milk by graphite furnace atomic absorption Spectrometry - Eduardoda Silva G. de Castro; Ricardo J. Cassella (Analytica Chimica Acta, 2025)

Exploring biocultural diversity: A systematic analysis and refined classification to inform decisions on conservation and sustainability - Irene Otamendi-Urroz; Cristina Quintas-Soriano; Jan Hanspach; Juan Miguel Requena-Mullor; Anna Sophie Lagies; Antonio J. Castro (Ambio, 2025)
Biocultural diversity reflects the interplay among biological and cultural diversity within social-ecological systems, shaped by human societies’ unique interactions with nature. This concept encompasses diverse knowledge, beliefs, practices, and values linked to local biodiversity. Despite its growing relevance, research gaps persist, including the need for theoretical clarity and a broader empirical application. To examine biocultural diversity’s role in conservation and sustainability, we conducted a systematic mapping of scientific literature in English and Spanish from 1990 to 2021, using cluster analysis to identify research trends. Including Spanish literature broadened the analysis, offering unique perspectives often overlooked. Results reveal gaps on research, particularly regarding intangible biocultural components (e.g., traditional knowledge, values, or worldviews) and the need for research in underrepresented regions like Africa and Asia. To advance in this direction, we propose a novel classification for biocultural diversity to foster holistic understanding, encourage exploration of intangible components, and promote collaboration among stakeholders.

Illegal artisanal longline use in the Galapagos Marine Reserve characterized through monitoring and control data - Andres Romero-Caicedo; Paola Buitron-Lopez; Andres Tapia-Jaramillo; Simon J. McKinley; Edwin Castro-Briones; Gonzalo Sevilla-Cedeño; John Ronquillo-Garzon; Gabriel Maciel de Souza Vianna (Frontiers in Marine Science, 2025)
Illegal longline fishing in the Galapagos Marine Reserve (GMR) represents a socioecological issue with significant impact on protected marine species. This study characterizes the use of illegal longlines in the GMR by combining and analyzing datasets generated from monitoring and control operations by the Galapagos National Park Directorate. We explored temporal and spatial patterns of longline detections, identified impacted species, and estimated compliance of vessels associated with longlines. The number of longlines detected varied across years but no clear seasonal pattern was evident. The most frequently captured species taxa were sharks and rays, including critically endangered scalloped hammerheads ( Sphyrna lewini ) and endangered manta rays ( Mobula birostris ). The critically endangered waved albatrosses ( Phoebastria irrorata ), as well as green turtles ( Chelonia mydas ), were also captured. Longline fishing occurred frequently in the submarine canyon south of Isabela Island, the seamount east of Santa Cruz Island, and waters between Pinzon, Isabela, and Santiago Islands, which are areas of high primary productivity and popular fishing grounds. Longlines were also frequently recorded near Darwin and Wolf Islands, a regionally-important hotspot for shark conservation. Offending vessels associated with longlines represented 17% of the artisanal fleet targeting pelagic fish species and were responsible for approximately 30% of pelagic fish landings. Notably, 80% of the fishing trips by the offending vessels when longlines were recorded had no associated fisheries landing recorded. Offending vessels had their Automatic Identification Systems (AIS) deactivated, in 69% of the fishing trips when illegal longlines were recorded, despite their use being mandatory by law. These findings provide baseline data to assist managers of the GMR to improve enforcement effort allocation and underscore the importance of strengthening surveillance and enforcement efforts to mitigate illegal fishing activities.

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Participatory mapping of marine ecosystem services in the Cabo de Gata-Níjar Natural Park (Spain) - Gabriela de Abreu; Irene Olivé; Sebastian Villasante; Mónica Expósito-Granados; Pablo Pita; Jone Molina-Urruela; Emilio Fernández; Gonzalo Méndez-Martínez; Antonio J. Castro (Ocean & Coastal Management, 2025)

Tailored toxins: Coagulotoxic variations in Atropoides, Cerrophidion, Metlapilcoatlus, and Porthidium viperid venoms against diverse vertebrate plasmas - Lee Jones; Edgar Neri-Castro; Nicholas J. Youngman; Joshua Llinas; Mark Haworth; Amber Gillett; Bryan G. Fry (Toxicon, 2025)

Oxidative foliar photo-necrosis, a mechanism of damage by phyto-pathogenic fungi - Roberto Hernández-Chacón; Lervin Hernández-Ramos; Laura Navarro de la Fuente; Manuel E. Medina; José J. Fernández; Ana R. Díaz-Marrero; Alejandro Salinas-Castro; Irene Lagunes; Ángel Trigos (Physiological and Molecular Plant Pathology, 2025)

Lunar impact ejecta flux on the Earth - Jose Daniel Castro-Cisneros; Renu Malhotra; Aaron J. Rosengren (Icarus, 2025)

Exploring agricultural stakeholders’ mental models of the water-energy-food-ecosystems (WEFE) Nexus: Insights from Mediterranean case studies - Enrica Garau; Gabriela de Abreu; Irene Pérez-Ramírez; Nora Schütze; Yasmine Farhat; Hala El Moussaoui; Jessica Loureiro; Olfa Mahjoub; Abir Ben Slimane; Hacib Amami; Abdellaziz Zairi; Andreas Thiel; et al. (Environmental Science & Policy, 2025)

Productive Potential and Contribution of Biological Nitrogen Fixation To Sugarcane Cultivation for Energy Purposes - Carolina Almada Gomes de Oliveira; Edevaldo de Castro Monteiro; Wesley dos Santos Souza; Paulo Vitor Alves Pio; Bruno J. R. Alves; Robert Michael Boddey; Segundo Urquiaga (Journal of Soil Science and Plant Nutrition, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Contributions of Net-Map to sustainability action research - Sofía Valeria Cortés-Calderón; María D. López-Rodríguez; Amanda Jiménez-Aceituno; Antonio J. Castro; María Mancilla-García (Current Opinion in Environmental Sustainability, 2025)

Highly open 3D carbon structures enhance solar steam generation - R. Fillet; V. Nicolas; P. Blyweert; J. Castro-Gutiérrez; B. Rousseau; A. Celzard; V. Fierro (Chemical Engineering Journal, 2025)

Mathematical modeling of neuroblast migration toward the olfactory bulb - Daniel Acosta-Soba; Carmen Castro; Noelia Geribaldi-Doldán; Francisco Guillén-González; Pedro Nunez-Abades; Noelia Ortega-Román; Patricia Pérez-García; J. Rafael Rodríguez-Galván (Mathematical Biosciences, 2025)

HIstopathological study of diseased sea urchins found dead in a rocky beach of Gran Canaria (Canary Islands) - M.J. Caballero; R. Nuñez-González; E. Montesdeoca-Morales; D. Padilla; J. Luis Martín Barrasa; G. Montero-Hernández; J. Juan Castro; A. Castro-Alonso (Journal of Comparative Pathology, 2025)

Retrospective characterization of viral induced skin and genital proliferative lesions in stranded cetaceans off the coasts of Spain - M.A. Jimenez Martinez; L. Sanchez Gil; I. Vargas Castro; J. Luis Crespo; M. Fayos Martinez; D. Garcia Parraga; J. Manuel Sanchez Vizcaino (Journal of Comparative Pathology, 2025)

Adenomatous polyposis in a cow associated to mutations in the adenomatous polyposis coli (APC) tumour-suppressor gene - O. Quesada-Canales; A. Castro-Alonso; E. Plamenova Stefanova; M. Andrada; J. Díaz-Delgado; S. Zhao; K.L. Ho (Journal of Comparative Pathology, 2025)

The multifaceted spectra of power − A participatory network analysis on power structures in diverse dryland regions - Veronica Olofsson; Maria Mancilla Garcia; Antonio J. Castro; Sofía Cortés Calderón; Amadou Hamath Diallo; Amanda Jiménez Aceituno; María D. López-Rodríguez; Taís Sonetti Gonzalez; Amanda Sousa Silvino; Ana Paula Aguiar (Global Environmental Change, 2025)

The utility and applicability of vegetation index-based models for the spatial disaggregation of evapotranspiration - Sangeetharani Munusamy; Eswar Rajasekaran; Dharmendra Saraswat; William P. Kustas; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; John H. Prueger; Joseph G. Alfieri; Maria Mar Alsina (Irrigation Science, 2025)

First evidence of lead-induced impairment of intestinal digestive enzyme activity in birds - Ana C. Castro-Guijarro; Rodolfo J. Arias; Noelia C. Fernández; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2025)

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

The fingerprint of pesticides in agricultural used polyethylene - Gabriela Castro; Victoria Fernández-Fernández; Miguel Cobo-Golpe; María Ramil; Enrique Blázquez-Blázquez; María L. Cerrada; I. Bernabé; J. Martínez Urreaga; M.U. de la Orden; Isaac Rodriguez (Waste Management, 2025)

Improving the effectiveness of safe cyanotoxin removal from drinking water using magnetic iron oxide nanoparticle-loaded carbon composites - Alejandro Cao; Natalia Vilariño; Lisandra de Castro Alves; Yolanda Piñeiro; Jose Rivas; Ana M. Botana; Cristina Carrera; María J. Sainz; Luis Rodríguez-Santos; M. Carmen Louzao; Luis M. Botana (Journal of Water Process Engineering, 2025)

Leveraging agrobiodiversity for sustainable transition in greenhouse-based intensive agriculture across Mediterranean drylands - Lorenzo Carretero-Paulet; Antonio J. Mendoza-Fernández; Francisco Javier Alcalá; Antonio J. Castro (Journal of Arid Environments, 2025)

Micro-CT reconstruction reveals new information about the phylogenetic position and locomotion of the Early Cretaceous bird Iberomesornis romerali - Javier Castro-Terol; Alejandro Pérez-Ramos; Jingmai K. O’Connor; José Luis Sanz; Francisco J. Serrano (Geobios, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

Exopolysaccharides of Ganoderma lucidum Activate the NLRP3 Inflammasome, Modulating Phagocytes and the Response of Mice to Infection with Cryptococcus neoformans - Pedro H. M. Bürgel; Raffael J. A. de Castro; Angelina M. Basso; Luísa C. Coelho; Clara L. F. Marina; Isaque M. Siqueira; Alysia V. Gonzales; Pavel Kucheryavy; Vitor H. Pomin; Elaine Rosechrer Carbonero; Aldo H. Tavares; Anamélia Lorenzetti Bocca (Mycopathologia, 2025)

Correction: The IGCP 714 Project “3GEO– Geoclimbing & Geotrekking in Geoparks”– Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Utilization of different protein sources and intestinal histology in yellowtail snapper, Ocyurus chrysurus - Stephanie F. Velasquez; Leonardo Ibarra-Castro; John D. Stieglitz; Khanh Nguyen; Timothy J. Bruce; D. Allen Davis (Animal Feed Science and Technology, 2025)

In vitro antitumor effects of aqueous extract and protease inhibitors from Sterculia striata st. Hil. et naud and metabolite profiling - Tadeu F. Braga Junior; Nerilson M. Lima; Gabriela P. Carli; Roberta M Cachuba; Gracimério J Guarneire; Beatriz J Tabai; Roberta M Abrão; Samuel G Barbosa; Lucas S. Machado; Jander S Nunes; Fabiana S. Machado; Teresinha de Jesus A. S. Andrade; et al. (Natural Product Research, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Insights into the mobility of rare earth complexes in groundwater-rock interactions: A geochemical view from modeling of computational chemistry - O. Castro-Ocampo; Gustavo Santos-Raga; E. Santoyo; Fernando J. Guerrero; Cornelio Delesma; Jesús Muñiz (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Aerobic bioremediation of selenite in marine and freshwater environments via intracellular selenium nanoparticle formation by Pseudomonas frigusceleri MPC6 in glycerol-fed continuous bioreactors - Matias Orellana-Saez; Yeney Lauzurique; Pablo Donoso-Garcia; Manuel Carmona; Andrea Carvajal; Ana L. Riveros; Marcelo J. Kogan; Daniela F. Báez; Ignacio Poblete-Castro (Journal of Environmental Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Assessing Chinese user satisfaction with electric vehicle battery performance from online reviews - Lanxin Shi; Shiqi (Shawn) Ou; Yanzi Zhou; Yonglin Wu; Xiaolu Tan; Xin He; Daniel J. De Castro Gomez; Zhenhong Lin (Transportation Research Part D: Transport and Environment, 2025)

Bio-desulfurization of different vulcanized rubber blends: An ecofriendly approach for end-of-life tires waste pollution - R. Andler; C. Cancino; F. González-Arancibia; J. Rojas; R. Castro; D. Kasai; V. Sanhueza (Journal of Environmental Chemical Engineering, 2025)

Assessing the efficacy of modified plant vaccine antigens in animal immunization: A systematic review - Tatyane Martins Cirilo; Ana Laura Grossi de Oliveira; Jordânia Costa Pinto; José Bryan da Rocha Rihs; Ana Cristina Loiola Ruas; Williane Fernanda Siqueira; Joseane Camilla de Castro; Nathalia Sernizon Guimarães; Ramayana Morais de Medeiros Brito; Lilian Lacerda Bueno; Thomas J. Cleij; Joni Esrom Lima; et al. (Food Bioscience, 2025)

Fluoroquinolone and sulfonamide antibiotics (single and mixtures) impair the motor function of zebrafish larvae at environmentally relevant concentrations - Gleyson B. Castro; Juliano J. Corbi; Mateus Cottorello-Fonsêca; Daniela Correia; Demetrio Raldúa; David S. Alexandre; Thandy Junio da Silva Pinto; Eva Prats; Melissa Faria (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Can macro- or meso-scale coping capacity variables improve the classification of building flood losses? - D. Rodríguez Castro; M. Cools; S. Roucour; P. Archambeau; D. Molinari; A. R. Scorzini; C. Dessers; S. Erpicum; M. Pirotton; J. Teller; B. Dewals (Natural Hazards, 2025)

The sensitivity to initial conditions of the co-orbital outcomes of lunar ejecta - Jose Daniel Castro-Cisneros; Renu Malhotra; Aaron J. Rosengren (Icarus, 2025)

Bioactive arabinoxylan oligomers via colonic fermentation and enzymatic catalysis: Evidence of interaction with toll-like receptors from in vitro, in silico and functional analysis - Caroline de A. Guerreiro; Leandro A.D. Andrade; Cynthia Fernández-Lainez; Layanne N. Fraga; Gabriel López-Velázquez; Tatiana M. Marques; Samira B.R. Prado; Robert J. Brummer; João Roberto O. Nascimento; Victor Castro-Alves (Carbohydrate Polymers, 2025)

Recovery after exploitation of stalked barnacles is facilitated by the presence of conspecifics: a study of post-harvest gap recolonization dynamics in SW Europe - Víctor Gómez-del Campo; Julio Arrontes; Teresa Cruz; Elsa Vázquez; Gonzalo Macho; Eric Thiébaut; Katja Geiger; Joana N. Fernandes; David Jacinto; Alba Aguión; Teresa Silva; David Mateus; et al. (Reviews in Fish Biology and Fisheries, 2025)
We have followed the recovery of gaps produced either by harvesters or by scientists in stands of stalked barnacle ( Pollicipes pollicipes ) during two years in four regions of Europe (SW Portugal, Galicia and Asturias in Spain and Brittany in France; n = 423 gaps), which was extended to four years in Asturias (n = 252 gaps). The presence of adult conspecifics in the margins of the gaps increased by at least four times the probability of initiation of their recovery. After two years of follow-up in the four regions, 90% of the gaps with adjacent conspecifics had initiated recolonization as opposed to only 60% in gaps with no adjacent adults. These figures remained stable after three years of follow up in Asturias, pointing to a large fraction of gaps which are recalcitrant to recolonization. Once initiated, the median rate of recovery after latency was 0.47 cm 2 /month in the four regions and 0.61 cm 2 /month in Asturias, increasing from 0.5 to 2.5 cm 2 /month for a 0 to 25 cm increase of perimeter in contact with adults, which is consistent with heavy recruitment on the stalks of conspecifics. The median estimated time to full recovery of gaps which initiated recovery was 2.65 years, thus recolonization is a slow process. Our results point to the main recommendations that a barnacle clump should never be removed entirely, so that the remaining adults serve as recruitment nuclei for the population, and that a maximum scraper width of 3.5 cm should be set to limit accessory capture of non-target individuals.

Impact of land transformation, management and governance on subjective wellbeing across social–ecological systems - Patricia Santillán-Carvantes; Alejandra Tauro; Patricia Balvanera; Juan Miguel Requena-Mullor; Antonio J. Castro; Cristina Quintas-Soriano; Berta Martín-López (Sustainability Science, 2025)
Recognizing and understanding the subjective wellbeing (SWB) of individuals is essential for designing effective policies that promote human development and the sustainable management of social-ecological systems (SES). This is particularly important for smallholders, critical stewards of biodiversity who face acute livelihood challenges. This article explores how smallholders inhabiting tropical dry forests in Mexico perceive their SWB and how it changes across a spectrum of SES that undergo different land transformations, management intensities, and governance dynamics. Our aims are to identify the dimensions of SWB that smallholders perceive, understand how these dimensions change across SES, and examine how smallholders’ perceptions of fulfilled material and non-material dimensions vary across SES. We analyzed the content of 25 in-depth interviews with farmers and identified 48 SWB items belonging to six categories: (1) social capital, (2) economic capital, (3) agency, (4) nature, (5) pleasant non-work activities, and (6) governmental services, and two additional dimensions referred to obstacles and enablers. We found two prevailing visions of SWB: ‘living well’ prevails especially in areas with communal governance and medium management intensity, and ‘need to earn more’ prevails in areas with individual governance and intensified land management. As management is intensified and governance fosters individualism, the lower the self-perceived material and non-material satisfaction. We discuss the different SWB found per SES, as well as strategies that can foster smallholder’s SWB and SES dynamics that can motivate different conservation goals and sustainable uses of nature, especially in biodiverse areas.

A relational turn in climate change adaptation: Evidence from urban nature-based solutions - Sean Goodwin; Marta Olazabal; Antonio J. Castro; Unai Pascual (Ambio, 2025)
The emergence of nature-based solutions (NbS) in science, policy, and practice signals a paradigmatic shift in urban climate change adaptation, yet empirical investigations into its impact on adaptation definitions and progress tracking remain scarce. Addressing this gap, we conducted thematic analysis on semi-structured interviews ( n = 15) with practitioners responsible for implementing and evaluating urban NbS in different countries. We provide a nuanced understanding of urban adaptation goals within urban NbS according to the insights from these practitioners, extending beyond hazard mitigation and towards cultivating and strengthening relationships between humans and nature. Tracking adaptation progress towards such relational adaptation goals requires acknowledging knowledge pluralism and the diversity of human–nature relations. We propose an alternative definition of adaptation supported by our data that aims to foster a more holistic approach to urban climate adaptation that accounts for the potential benefits of urban NbS across interconnected climate, biodiversity, and social goals.

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Distribution and bioconcentration of semivolatile organic compounds (SVOCs) in soils and vascular plant Colobanthus quitensis from Sub-Antarctic and Antarctic regions - C. Egas; T. Luarte; R. Vargas; E. Castro-Nallar; K. Pozo; P. Přibylová; J. Martiník; M. Molina-Montenegro; C. Galbán-Malagón (Science of The Total Environment, 2025)

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Distinct management units for the Critically Endangered angelshark (Squatina squatina) revealed in the Canary Islands - Eva K.M. Meyers; Nadia Faure; David Jiménez-Alvarado; Joanna Barker; Hector Toledo-Padilla; Fernando Tuya; Charlotte Pike; Lucy R. Mead; Michael J. Sealey; Maria Belén Caro; David M.P. Jacoby; Felipe Ravina Olivares; et al. (Conservation Genetics, 2025)
The angelshark, Squatina squatina , is listed as Critically Endangered on the IUCN Red List of Threatened Species, and remaining populations are highly fragmented throughout its historical distribution. The Canary Islands archipelago in the North East Atlantic has been identified as a uniquely large stronghold for the species. In the present study, we compared the population genetic structure of S. squatina across different islands of the Canary Island archipelago using both microsatellite and single nucleotide polymorphism (SNP) markers. Both markers revealed significant differentiation of angelsharks between islands in the archipelago, with three main genetic units at: (1) Tenerife, (2) Gran Canaria and (3) the island group consisting of La Graciosa, Lanzarote and Fuerteventura. Our results imply a connectivity barrier between some adjacent islands, most likely driven by abyssal depths, and varying geological history and formation of each island and oceanographic patterns (i.e. seasonal coastal upwellings off the African coast). Therefore, we suggest that in the Canary Islands, S. squatina populations should be managed locally, with conservation and research priorities designed and implemented specifically for each of the three genetic units.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Novel combination of 3D-printing and electrochemical deposition to design and prepare metallic honeycomb supported catalysts for dry reforming of methane - O. Bazta; F.J. Botana; J.J. Calvino; M.A. Cauqui; J.M. Gatica; H. Vidal; L. González-Rovira; J. López-Castro; M.P. Yeste; G. Blanco; J.C. Hernández-Garrido (Chemical Engineering Journal, 2025)

Evaluating the precise grapevine water stress detection using unmanned aerial vehicles and evapotranspiration-based metrics - V. Burchard-Levine; I. Borra-Serrano; J. M. Peña; W. P. Kustas; J. G. Guerra; J. Dorado; G. Mesías-Ruiz; M. Herrezuelo; B. Mary; L. M. McKee; A. I. de Castro; S. Sanchez-Élez; et al. (Irrigation Science, 2025)
Precise irrigation management requires accurate knowledge of crop water demand to adequately optimize water use efficiency, especially relevant in arid and semi-arid regions. While unoccupied aerial vehicles (UAV) have shown great promise to improve the water management for crops such as vineyards, there still remains large uncertainties to accurately quantify vegetation water requirements, especially through physically-based methods. Notably, thermal remote sensing has been shown to be a promising tool to evaluate water stress at different scales, most commonly through the Crop Water Stress Index (CWSI). This work aimed to evaluate the potential of a UAV payload to estimate evapotranspiration (ET) and alternative ET-based crop water stress indices to better monitor and detect irrigation requirements in vineyards. As a case study, three irrigation treatments within a vineyard were implemented to impose weekly crop coefficient (Kc) of 0.2 (extreme deficit irrigation), 0.4 (typical deficit irrigation) and 0.8 (over-irrigated) of reference ET. Both the original Priestley-Taylor initialized two-source energy balance model (TSEB-PT) and the dual temperature TSEB (TSEB-2T), which takes advantage of high-resolution imagery to discriminate canopy and soil temperatures, were implemented to estimate ET. In a first step, both ET models were evaluated at the footprint level using an eddy covariance (EC) tower, with modelled fluxes comparing well against the EC measurements. Secondly, in-situ physiological measurements at vine level, such as stomatal conductance (g st ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, were collected simultaneously to UAV overpasses as plant proxies of water stress. Different variants of the CWSI and alternative metrics that take advantage of the partitioned ET from TSEB, such as Crop Transpiration Stress Index (CTSI) and the Crop Stomatal Stress Index (CSSI), were also evaluated to test their statistical relationship against these in-situ physiological indicators using the Spearman correlation coefficient ( ρ ). Both TSEB-PT and TSEB-2T CWSI related similarly to in-situ measurements (Ψ leaf : ρ ~ 0.4; Ψ stem : ρ ~ 0.55). On the other hand, stress indicators using canopy fluxes (i.e. CTSI and CSSI) were much more effective when using TSEB-2 T (Ψ leaf : ρ = 0.45; Ψ stem : ρ = 0.62) compared to TSEB-PT (Ψ leaf : ρ = 0.18; Ψ stem : ρ = 0.49), revealing important differences in the ET partitioning between model variants. These results demonstrate the utility of physically-based models to estimate ET and partitioned canopy fluxes, which can enhance the detection of vine water stress and quantitatively assess vine water demand to better manage irrigation practices.

Evaluation of impacts of biosolids application and drainage water management on soil N2O and CH4 emissions using the flux gradient method - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agriculture, Ecosystems & Environment, 2025)

Environmental factors determining the distribution of Limnoperna fortunei and its impact on benthic communities in the reservoirs of the Rio Negro (Uruguay)) - L. Capurro; J. Pereira; M. Castro; C. Ferrer; D. Fabián; P. Muniz; E. Brugnoli (Biological Invasions, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Hg, Cd, As, and Pb in surface sediments from the tropical coastal lagoon Estero Salado, Gulf of Guayaquil-Ecuador - Franklin I. Ormaza-González; Rubén D. Castro-Rendón; Ana Maridueña-Bravo; Nayiva Bobadilla-Cordova; Ivanna Ramos-Castañeda; Peter J. Statham (Frontiers in Marine Science, 2024)
The Gulf of Guayaquil (GG) is the most important tropical estuarine system of the eastern coast of South America, receiving an average water flow of about 1 650 m 3 s -1 from a river basin of approximately 33 700 km 2 . The city of Guayaquil surrounds the inner coastal lagoon of the Estero Salado (ES) that empties into the GG. This coastal lagoon is of high social, food production, and environmental importance for the city and the GG. However, there is limited high quality data on metal pollution in this zone, no recent information on Hg, and the extent to which sediment metal pollution extends into the GG is presently unknown. As, Cd, Pb, and Hg were analysed in surface sediments from the urban zone and gave average concentrations of 32.3, 2.08, 41.9, and 0.12 mg kg -1 (dry weight), respectively. Additionally, data were obtained for the first time for the El Morro Channel, south of the ES in the GG, which is expected to be a relatively pristine zone; average As, Cd, Pb and Hg concentrations were 6.6, 0.22, 7.9 and 0.02 mg kg -1 (dry weight), well below concentrations seen in the urban ES zone. Estimates of the geo-accumulation index for metal pollution, using the El Morro data as background values, were 1.7 (As), 2.7 (Cd), 1.8 (Pb) and 2.0 (Hg), making the ES class II and a moderately polluted estuary for As, Hg and Pb, but class III and “moderately to heavily polluted” for Cd. If the lowest concentrations of the EM samples are taken the ES is class III for As, IV for Hg and Pb, and V for Cd; id est, the ES would classify as a heavily to extremely polluted estuary regarding these metals. These data show the metal concentrations increase significantly as the main conurbation of Guayaquil is approached from offshore, indicating a strong anthropogenic source of metals from the city, with anticipated negative environmental impacts.

Participatory mapping of uses and ecosystem services as a useful tool for the identification of conflicts in Marine Protected Areas: The case of the Cíes Islands archipelago (NW Spain) - J. Molina-Urruela; E. Fernández; A.J. Castro; M. Expósito-Granados; A. Ovejero-Campos; S. Villasante; G. Méndez-Martínez (Ocean & Coastal Management, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Exploring the ecosystem structure of Zanzibar archipelago, trophic flows and fisheries interaction by using a mass balance modelling approach - Batuli M. Yahya; Lorena Couce; Saleh A.S. Yahya; José J. Castro (Regional Studies in Marine Science, 2024)

Optimization of the stowage of fishing discards: Innovations in trawlers in the Gulf of Cadiz (SW Iberian Peninsula) - Daniel J. Coronil-Huertas; Carlos Rodriguez-García; Santiago Pavón-Quintana; Juan M. Vidal-Pérez; Jésica Sarmiento-Carbajal; Remedios Cabrera-Castro (Regional Studies in Marine Science, 2024)

Measuring the contribution of nature-based solutions beyond climate adaptation in cities - Sean Goodwin; Marta Olazabal; Antonio J. Castro; Unai Pascual (Global Environmental Change, 2024)

Applying the Three Horizons approach in local and regional scenarios to support policy coherence in SDG implementation: Insights from arid Spain - María D. López-Rodríguez; Amanda Jiménez-Aceituno; Cristina Quintas-Soriano; Juan Miguel Requena-Mullor; Enrica Garau; Daniela Alba-Patiño; Irene Otamendi-Urroz; Ana Paula D. Aguiar; Sofía Cortés-Calderón; Antonio J. Castro (Global Environmental Change, 2024)

Optimizing sunflower yield: Understanding pollinator contribution to inform agri-environmental strategies - Lucie Mota; João Loureiro; José A. González; Violeta Hevia; Jorge J. Ortega-Marcos; Carlos Rad; Evan A.N. Marks; Sílvia Castro (Field Crops Research, 2024)

Attenuation of Hyperglycemia in Diabetic Rats Assisted by Immobilized Probiotic in Sodium Alginate - José J. Arriaga-Morales; Cynthia Ordaz-Pichardo; Roberto Castro‑Muñoz; Enrique Durán-Páramo (Probiotics and Antimicrobial Proteins, 2024)
Diabetes mellitus type 2 (DM2) is the most common chronic disease worldwide, characterized mainly by increased glucose concentration in the blood and affecting several organs’ functionality. The daily consumption of probiotic bacteria can help control diabetes and reduce the damage caused. Cell immobilization techniques are a powerful tool that provides physical cell protection to such probiotic bacteria against gastrointestinal conditions. We suggest that cell immobilization could be a significant vector for delivering a high quantity of viable probiotics to the gut, helping attenuate hyperglycemia in diabetic rats. Seventy male Wistar rats were used in this work. Nicotinamide was administrated via intraperitoneal injection 15 minutes before inducing type 2 diabetes (DM2), followed by a second intraperitoneal injection of streptozotocin to induce DM2. Rats were divided into seven groups. For 45 days, a specific treatment was applied to each group. The group of rats, supplied with immobilized Lactobacillus casei, showed a serum glucose concentration of 137 mg/dL, which was close to the one observed in the groups of healthy rats (117 mg/dL) and rats treated with metformin (155 mg/dL). The diabetic rats without treatment presented a higher serum glucose concentration (461 mg/dL). In the rats treated with immobilized L. casei , there was no biochemical parameter alteration, and the cell morphology of the analyzed tissues was similar to those of the healthy group. The consumption of immobilized L. casei could allow a high quantity of viable probiotics to be delivered to the gut, reducing serum glucose concentration by up to 70% compared to diabetic rats and reducing organ damage caused by diabetes.

Combining Spatial Downscaling Techniques and Diurnal Temperature Cycle Modelling to Estimate Diurnal Patterns of Land Surface Temperature at Field Scale - Kukku Sara; Eswar Rajasekaran; Rahul Nigam; Bimal K. Bhattacharya; William P. Kustas; Joseph G. Alfieri; John H. Prueger; Maria Mar Alsina; Lawrence E. Hipps; Lynn G. McKee; Andrew J. McElrone; Sebastian J. Castro; et al. (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)

Analysis of the pharyngeal structure of the genus Oreochromis for species identification through geometric morphometrics in the Aguamilpa reservoir, Nayarit, Mexico - Breidy L. Cuevas-Rodríguez; Wally K. Rubio-Gómez; Jasmín Granados-Amores; Jesús J. Dueñas-Romero; Francisco J. Valdez-González; Eduardo Sandoval-Castro; Claudia A. González-Huerta; Juan P. González-Hermoso; Oscar I. Zavala-Leal (Zoologischer Anzeiger, 2024)

Strong climate mitigation potential of rewetting oil palm plantations on tropical peatlands - Nisa Novita; Adibtya Asyhari; Rasis P. Ritonga; Adi Gangga; Gusti Z. Anshari; Joni Jupesta; Jennifer C. Bowen; Nurul Silva Lestari; J. Boone Kauffman; Alison M. Hoyt; Clarice R. Perryman; Israr Albar; et al. (Science of The Total Environment, 2024)

Pinus cembroides, and P. orizabensis grafts, a viable option for pink pine nut production - Sandra L. Castro-Garibay; Omegar Cruz-Arvizu; Isaí Monroy-González; Alma D. Abarca-Cervantes; Iris J. Cruz-Larios; Marcelina Arguello-Hernández (New Forests, 2024)

Tilapia as a model fish for biomonitoring of metal pollution in dams associated with mining watersheds: contrasting diagnosis from different tissues and health risk assessment - Federico Páez-Osuna; Aldivar Castro Espinoza; Eduardo Tirado Figueroa; César J. Saucedo Barrón; Magdalena E. Bergés-Tiznado (Environmental Geochemistry and Health, 2024)
Tilapia is a model fish species used as a pollution biomonitor due to its tolerance and availability in many contaminated sites. Blue tilapia Oreochromis aureus specimens (n = 320) were collected in eleven dams influenced by mining in the SE Gulf of California region (dams 1, 2 and, 3 comprise 55 mining sites; dam 4 comprises 8; dams 6, 8, 10, and 11, ≤ 6; and dams 5, 7, and 9 include 19, 20, and 16 mining sites, respectively). Cadmium, Cu, Pb, and Zn concentrations were analyzed in the muscle, liver, gills, and guts to identify metal pollution and evaluate risks and seasonal changes. The distinct tissues exhibited different metal accumulation capacities, therefore allowed develop a diagnosis comparative between the eleven dams. In general, metal concentrations were higher in dams 1, 2, 5, and 9, which are associated with more mining sites in their sub-basins. The four metals exhibited the highest levels in the tilapia liver in dams 1 and 2, which can be related to the present and past mining activity in the lower watershed (55 sites) and the geothermal activity in these dams. In general, Zn exhibited the highest level in the tilapia livers from dams 1, 2, 3, 4, 5, and 10 compared to the maximum mean (220 µg/g) concentrations previously recorded. The non-carcinogenic risks indicated that the Pb risk was enhanced when the intake was ≥ 231.5 g week −1 of tilapia muscle, indicating a potential risk of adverse health effects for the entire population.

Emotional attachment and philosophical worldviews explain human connectedness to nature in abandoned rural Spain - C. López-Zayas; A. J. Castro; J. M. Requena-Mullor; M. D. López-Rodríguez; E. Garau; C. Quintas-Soriano (Sustainability Science, 2024)
Land abandonment and rural depopulation are escalating worldwide, presenting sustainability dilemmas for both rural and urban regions. However, there remains a dearth of research on the sociocultural dimensions of abandonment from a local standpoint. This investigation focuses on a case study conducted in southeastern Spain, wherein a social survey was used to evaluate the perspectives of local communities concerning human–nature interconnectedness, land abandonment, and their impacts on quality of life. A survey campaign was administered in the case study region during the spring of 2021, and 122 surveys were collected. The findings identify, in the context of the progressive abandonment of rural lands in Spain, key factors that explain the desire of local people to inhabit and not abandon rural regions in southeastern Spain. Our results also show a strong connection between people and nature in rural Spain, which is explained by the capacity of locals to form relational values in rural environments and the existence of philosophical worldviews and emotional attachments to rural lifestyles. However, barriers to not abandoning rural environments were also identified, including a lack of professional and economic opportunities. Our results suggest that the mitigation of depopulation in rural areas in Spain requires actions to foster land stewardship and address socioeconomic imbalances.

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Magnetic nanostructured agents for the mitigation of mycotoxins and cyanotoxins in the food chain - Jesús M. González-Jartín; Lisandra de Castro Alves; Y. Piñeiro; Amparo Alfonso; Rebeca Alvariño; Manuel González Gomez; Mercedes R. Vieytes; J. Rivas; Luis M. Botana (Food Chemistry, 2024)

Organophosphate ester flame retardant chemicals and maternal depression during pregnancy - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Max T. Aung; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Tingyu Yang; Mario J. Vigil; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; et al. (Environmental Research, 2024)

Evaluating the utility of combining high resolution thermal, multispectral and 3D imagery from unmanned aerial vehicles to monitor water stress in vineyards - V. Burchard-Levine; J. G. Guerra; I. Borra-Serrano; H. Nieto; G. Mesías-Ruiz; J. Dorado; A. I. de Castro; M. Herrezuelo; B. Mary; E. P. Aguirre; J. M. Peña (Precision Agriculture, 2024)
Purpose High resolution imagery from unmanned aerial vehicles (UAVs) has been established as an important source of information to perform precise irrigation practices, notably relevant for high value crops often present in semi-arid regions such as vineyards. Many studies have shown the utility of thermal infrared (TIR) sensors to estimate canopy temperature to inform on vine physiological status, while visible-near infrared (VNIR) imagery and 3D point clouds derived from red–green–blue (RGB) photogrammetry have also shown great promise to better monitor within-field canopy traits to support agronomic practices. Indeed, grapevines react to water stress through a series of physiological and growth responses, which may occur at different spatio-temporal scales. As such, this study aimed to evaluate the application of TIR, VNIR and RGB sensors onboard UAVs to track vine water stress over various phenological periods in an experimental vineyard imposed with three different irrigation regimes. Methods A total of twelve UAV overpasses were performed in 2022 and 2023 where in situ physiological proxies, such as stomatal conductance (g s ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, and canopy traits, such as LAI, were collected during each UAV overpass. Linear and non-linear models were trained and evaluated against in-situ measurements. Results Results revealed the importance of TIR variables to estimate physiological proxies (g s , Ψ leaf , Ψ stem ) while VNIR and 3D variables were critical to estimate LAI. Both VNIR and 3D variables were largely uncorrelated to water stress proxies and demonstrated less importance in the trained empirical models. However, models using all three variable types (TIR, VNIR, 3D) were consistently the most effective to track water stress, highlighting the advantage of combining vine characteristics related to physiology, structure and growth to monitor vegetation water status throughout the vine growth period. Conclusion This study highlights the utility of combining such UAV-based variables to establish empirical models that correlated well with field-level water stress proxies, demonstrating large potential to support agronomic practices or even to be ingested in physically-based models to estimate vine water demand and transpiration.

Beyond counting calls: estimating detection probability for Antarctic blue whales reveals biological trends in seasonal calling - Franciele R. de Castro; Danielle V. Harris; Susannah J. Buchan; Naysa Balcazar; Brian S. Miller (Frontiers in Marine Science, 2024)
We explore the utility of estimating the density of calls of baleen whales for better understanding acoustic trends over time. We consider as a case study stereotyped ‘song’ calls of Antarctic blue whales ( Balaenoptera musculus intermedia ) on their Antarctic feeding grounds over the course of a year-long, continuous recording from 2014. The recording was made in the Southern Ocean from a deep-water autonomous hydrophone moored near the seafloor in the Eastern Indian sector of the Antarctic. We estimated call density seasonally via a Monte-Carlo simulation based on the passive sonar equation, and compared our estimates to seasonal estimates of detection rate, which are commonly reported in acoustic studies of Antarctic blue whales. The resulting seasonal call densities at our Antarctic site were strongly influenced by seasonally varying noise levels, which in turn yielded seasonal differences in detection range. Incorporating the seasonal estimates of detection area into our analysis revealed a pattern of call densities in accord with historic (non-acoustic) knowledge of Antarctic blue whale seasonal distribution and migrations, a pattern that differed from seasonal detection rates. Furthermore, our methods for estimating call densities produced results that were more statistically robust for comparison across sites and time and more meaningful for interpretation of biological trends compared to detection rates alone. These advantages came at the cost of a more complex analysis that accounts for the large variability in detection range of different sounds that occur in Antarctic waters, and also accounts for the performance and biases introduced by automated algorithms to detect sounds. Despite the additional analytical complexities, broader usage of call densities, instead of detection rates, has the potential to yield a standardized, statistically robust, biologically informative, global investigation of acoustic trends in baleen whale sounds recorded on single hydrophones, especially in the remote and difficult to access Antarctic.

Bows and arrows in South America: Advances and debates - Erik J. Marsh; Silvina Celeste Castro; Lucía Yebra; Valeria Cortegoso (Quaternary International, 2024)

Spearthrower or bow? Hafted projectile points from the Americas refine comparative baselines for tracking projectile technologies - Erik J. Marsh; Lucía Yebra; Silvina Celeste Castro; Valeria Cortegoso (Quaternary International, 2024)

The effects of the decline in tourism during the COVID-19 lockdown on the wild mammal community in forest surrounding a theme park on the Mexican Caribbean - Jonathan Pérez-Flores; Edwin Hernández-Pérez; Holger Weissenberger; Javier Carballo-Soto; Elba M. López-Castro; Flor J. Ávila-Flores (Journal for Nature Conservation, 2024)

Deadwood decomposition in burnt mediterranean pine reforestations across an elevation gradient: A 15-year study - R. Juan-Ovejero; M.P. Reyes-Martín; A. Elghouat; A.B. Leverkus; S. Seibold; J. Castro (Forest Ecology and Management, 2024)

WITHDRAWN: Floral scents in the root-holoparasitic plants of the Lennoaceae (Boraginales) - Nadia Castro-Cárdenas; Pactli F. Ortega-González; Francisco J. Espinosa-García; Daniel Sánchez; Yolanda M. García-Rodríguez; Sonia Vázquez-Santana (Flora, 2024)

Towards scaling up of the electrochemical production of Caro’s acid: Electrode size and/or stacking? - M. Pilar Castro; Miguel A. Montiel; Ismael F. Mena; J. Gäbler; D. Barton; Cristina Sáez; Manuel A. Rodrigo (Chemical Engineering Journal, 2024)

A case study of depolymerization in silicates: Melting of quartz and zircon crystallization at high pressure - A. Sánchez-Navas; S. Melchor; J. Ortega-Castro; I. Vidal-Daza; A. Castro (Chemical Geology, 2024)

The IGCP 714 Project “3GEO – Geoclimbing & Geotrekking in Geoparks” – Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2024)
The IGCP 714 project “3GEO – Geoclimbing & Geotrekking in Geoparks ” is financed by the International Geoscience Programme (IGCP) and supported by the International Union of Geological Sciences (IUGS). In this paper, we report on the results of the first phase of the project focused on the criteria to be adopted to select geodiversity sites equipped for climbing or trekking. The selection of geoclimbing sites and geotrekking routes is aimed at combining multimedia tools and outdoor activities for Geosciences promotion and conservation in UNESCO Global Geoparks, aspiring geoparks or geoparks project, and also in protected areas featuring geoheritage sites. Indeed, both outdoor activities and multimedia tools favour the pursuing of many of the United Nations Sustainable Development Goals (e.g., 3, 4, 8, 11). An international consortium of geoscientists from 12 different countries selected, through the proposed procedure, 22 geoclimbing sites, and then they also detected 30 geotrekking routes mirroring Earth geodiversity. At some test sites (geoclimbing and geotrekking) multimedia tools and digital outcrop models have been developed through different methodological approaches (e.g., Structure from Motion and Multi-View Stereo photogrammetry), to open the way to the second part of the project still in progress. These sites and the relative virtual models are herein also shown. The final aim of the IGCP 714 project is indeed to create an open data repository (digital outcrop models, videos, virtual tours, photos, scientific information, and interpretations) to upload data of the selected sites to mirror Earth geodiversity for different users including tourists and school groups.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Weed species classification with UAV imagery and standard CNN models: Assessing the frontiers of training and inference phases - G.A. Mesías-Ruiz; I. Borra-Serrano; J.M. Peña; A.I. de Castro; C. Fernández-Quintanilla; J. Dorado (Crop Protection, 2024)

A comparative analysis of OpenET for evaluating evapotranspiration in California almond orchards - Kyle Knipper; Martha Anderson; Nicolas Bambach; Forrest Melton; Zac Ellis; Yun Yang; John Volk; Andrew J. McElrone; William Kustas; Matthew Roby; Will Carrara; Sebastian Castro; et al. (Agricultural and Forest Meteorology, 2024)

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Bioactive compounds isolated from the bark of Aesculus glabra Willd - Miriam Velazquez Cruz; Eric Salinas-Arellano; Ines Castro Dionicio; Jonathan G. Jeyaraj; Nathan P. Mirtallo Ezzone; Esperanza J. Carcache de Blanco (Phytochemistry Letters, 2024)

A Review on the State of the Art in Frugivory and Seed Dispersal on Islands and the Implications of Global Change - Manuel Nogales; Kim R. McConkey; Tomás A. Carlo; Debra M. Wotton; Peter J. Bellingham; Anna Traveset; Aarón González-Castro; Ruben Heleno; Kenta Watanabe; Haruko Ando; Haldre Rogers; Julia H. Heinen; et al. (The Botanical Review, 2024)
We provide an overview of the current state of knowledge of island frugivory and seed dispersal and identify knowledge gaps that are important for fundamental research on—and applied conservation of—island ecosystems. We conducted a systematic literature search of frugivory and seed dispersal on islands, omitting large, continental islands. This revealed a total of 448 studies, most (75%) published during the last two decades, especially after 2010. Nearly 65% of them were focused on eight archipelagos. There is a paucity of studies in Pacific archipelagos near Asia and Australia, and in the Indian Ocean. Data on island frugivory and seed dispersal are diverse but highly uneven in geographic and conceptual coverage. Despite their limited biodiversity, islands are essential reservoirs of endemic plants and animals and their interactions. Due to the simplicity of insular ecosystems, we can assess the importance of seed dispersal theory and mechanisms at species and community levels. These include the ecological and biogeographical meaning and prevalence of non-standard mechanisms of seed dispersal on islands; the seed dispersal effectiveness and the relative roles of different frugivore guilds (birds and reptiles being the most important); and patterns of community organization and their drivers as revealed by interaction networks. Island systems are characterized by the extinction of many natives and endemics, and high rates of species introductions. Therefore, understanding how these losses and additions alter seed dispersal processes has been a prevailing goal of island studies and an essential foundation for the effective restoration and conservation of islands.

Welfare assessment of Thoroughbred horses naturally infected with gastrointestinal parasites in Southern Brazil: Quantifying the host-parasite relationship - L.S. Abrahão Pires; C. Abrahão; L.L. Dias de Castro; J. Hammerschmidt; J. Antunes; C.F.M. Molento; M.B. Molento (Journal of Equine Veterinary Science, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Screw reactor design for potato peel pretreatment using the steam explosion - Paula A. Ramirez-Cabrera; Juan J. Lozada-Castro; Carlos A. Guerrero-Fajardo (Bioresource Technology, 2024)

Carotenoid skin ornaments as flexible indicators of male foraging behavior in a marine predator: Variation among Mexican colonies of brown booby (Sula leucogaster) - Nathan P. Michael; Roxana Torres; Andreanna J. Welch; Jonathan Felis; Josh Adams; Mario Erandi Bonillas-Monge; Samantha Hodgson; Laura Lopez-Marquez; Alejandro Martínez-Flores; Gala Enidh Castro-Mejias; Anne E. Wiley (Marine Biology, 2024)
Carotenoid-dependent ornaments can reflect animals’ diet and foraging behaviors. However, this association should be spatially flexible and variable among populations to account for geographic variation in optimal foraging behaviors. We tested this hypothesis using populations of a marine predator (the brown booby, Sula leucogaster ) that forage across a gradient in ocean depth in and near the Gulf of California. Specifically, we quantified green chroma for two skin traits (foot and gular color) and their relationship to foraging location and diet of males, as measured via global positioning system tracking and stable carbon isotope analysis of blood plasma. Our three focal colonies varied in which foraging attributes were linked to carotenoid-rich ornaments. For gular skin, our data showed a shift from a benthic prey-green skin association in the shallow waters in the north to a pelagic prey-green skin association in the deepest waters to the south. Mean foraging trip duration and distance of foraging site from coast also predicted skin coloration in some colonies. Finally, brown booby colonies varied in which trait (foot versus gular skin color) was associated with foraging metrics. Overall, our results indicate that male ornaments reflect quality of diet and foraging–information that may help females select mates who are adapted to local foraging conditions and therefore, are likely to provide better parental care. More broadly, our results stress that diet-dependent ornaments are closely linked to animals’ environments and that we cannot assume ornaments or ornament signal content are ubiquitous within species, even when ornaments appear similar among populations.

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Organophosphate ester additives and microplastics in benthic compartments from the Loire estuary (French Atlantic coast) - J. Castro-Jiménez; Y. Aminot; N. Bely; C. Pollono; B.I.T. Idjaton; L. Bizzozero; O. Pierre-Duplessix; N.N. Phuong; J. Gasperi (Marine Pollution Bulletin, 2024)

A methodological approach for integrating human emotions in protected areas management: Insights from SE Spain - Enrica Garau; Juan M. Requena-Mullor; Cristina Quintas-Soriano; María D. López-Rodríguez; Irene Otamendi-Urroz; Mariano Oyarzabal; Antonio J. Castro (Landscape and Urban Planning, 2024)

The key role played by mesoporous alumina as binder for obtaining ultra-hard CaO based pellets for thermochemical heat storage leveraging the CaO/CaCO3 cycle - D. Castro-Yáñez; M. Erans; A. Peral; R. Sanz; J. González-Aguilar; M. Romero; L. Briones; E.S. Sanz-Pérez; J.M. Escola (Journal of Cleaner Production, 2024)

Increasing auditory intensity enhances temporal but deteriorates spatial accuracy in a virtual interception task - J. Walter Tolentino-Castro; Anna Schroeger; Rouwen Cañal-Bruland; Markus Raab (Experimental Brain Research, 2024)

Age, growth and mortality characteristics of the Thumbprint Emperor (Lethrinus harak) in Zanzibar - Tumu Ali Mussa; Saleh A.S Yahya; Jose J Castro; Leonard J Chauka (Western Indian Ocean Journal of Marine Science, 2024)
The growth parameters of Lethrinus harak were studied in Zanzibar water from 308 samples collected between June 2019 to May 2020 at Unguja Ukuu and Mkokotoni landing sites. The annulus count indicated that the majority of fishes captured were of three and four years old and very few were five, six, and seven years of age with a mean length of 17.69 cm, 21.04 cm, 24.18 cm, 25.86 cm, and 28.15, respectively. The number of rings was counted on the whole otolith and the growth rings were revealed to be formed annually, with the opaque margins generated from December to February and the hyaline ones during the rest of the year. The growth parameters were estimated as L∞=34.22cm, K=0.25 year-1, and t0=0.00. The total mortality (Z) was estimated as 0.68 year-1 and natural mortality (M) was estimated using Pauly's equation, as 0.65 per year-1 and fishing mortality (F) was 0.03 year-1, which gives an exploitation rate (E) of 0.04 year-1. Although these values indicate the species to be underexploited, the absence of older individuals 15 years and smaller below three years might have affected our findings.

Urban environment during pregnancy and lung function, wheezing, and asthma in school-age children. The generation R study - Alicia Abellan; Charline Warembourg; Sara M. Mensink-Bout; Albert Ambros; Montserrat de Castro; Serena Fossati; Mònica Guxens; Vincent WV. Jaddoe; Mark J. Nieuwenhuijsen; Martine Vrijheid; Susana Santos; Maribel Casas; et al. (Environmental Pollution, 2024)

Analysis of gaseous emission and particle number size distributions in metal casting processes with binder jetting moulds - C. Blanco-Alegre; A.I. Calvo; M.Á. Castro-Sastre; A.I. Fernández-Abia; P. Rodríguez-González; F. Oduber; A. Castro; J. Barreiro; R. Fraile (Building and Environment, 2024)

Effects of parity, seasonal heat stress, and colostrum collection time postpartum on colostrum quality of Holstein cattle in an arid region - L. Avendaño-Reyes; U. Macías-Cruz; M. A. Sánchez-Castro; F. Anzures-Olvera; R. Vicente-Pérez; M. Mellado; R. Zamorano-Algándar; P. H. Robinson; V. J. Castañeda-Bustos; A. López-Baca (International Journal of Biometeorology, 2024)

Chemical prospection and antioxidant activity of Humiria balsamifera (Aubl.) A. St. Hil. AND Hymenaea courbaril L. - Jhuliana Monteiro de Matos; Andressa Rose Castro Costa; Marciel Nascimento Justino; Marcos Bispo Pinheiro Camara; Osmar Luis Silva Vasconcelos; J. C. Marques; Clenilma Marques Brandão; Georgiana Eurides de Carvalho Marques (Natural Product Research, 2024)

Integrated cyclostratigraphy of the Cau core (SE Spain) - A timescale for climate change during the early Aptian Anoxic Event (OAE 1a) and the late Aptian - Rafael Martínez-Rodríguez; Sietske J. Batenburg; José M. Castro; Ginés A. de Gea; Luis M. Nieto; Pedro A. Ruiz-Ortiz; Stuart Robinson (Global and Planetary Change, 2024)

Bacterial nanocellulose spheres coated with meta acrylic copolymer: Vaccinium meridionale swartz extract delivery for colorectal cancer chemoprevention - M. Osorio; L. Posada; E. Martínez; V. Estrada; G. Quintana; Maria E. Maldonado; S. Peresin; J. Orozco; C. Castro (Food Hydrocolloids, 2024)

Prenatal exposures to organophosphate ester metabolites and early motor development in the MADRES cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Xinci Chen; Tingyu Yang; Mario J. Vigil; Helen B. Foley; Kurunthachalam Kannan; Morgan Robinson; Brendan Grubbs; Deborah Lerner; Nathana Lurvey; Laila Al-Marayati; et al. (Environmental Pollution, 2024)

A spatial framework for improved sanitation to support coral reef conservation - Caitlin D. Kuempel; Jacqueline Thomas; Amelia S. Wenger; Stacy D. Jupiter; Andrés F. Suárez-Castro; Nabeela Nasim; Carissa J. Klein; Ove Hoegh-Guldberg (Environmental Pollution, 2024)

Surface circulation in Todos Santos Bay, Baja California, México - Reginaldo Durazo; Xavier Flores-Vidal; Rubén Castro; Francisco J. Ocampo-Torres; Johanna Saavedra; Isaac Rodríguez-Padilla; Marco Larrañaga (Continental Shelf Research, 2024)

Urban socio-ecosystem renewal: an ecosystem services assessment approach - M. LopezDeAsiain; J. M. Castro Bonaño; M. Borrallo-Jiménez; R. Mora Esteban (International Journal of Environmental Science and Technology, 2024)
Using a novel approach based on the urban ecosystem services approach, this research explores the relation between socio-economic, architectonic and ecological factors in urban renewal processes. This deductive conceptual approach is based on the definition of an urban diagnosis and intervention model based on the concept of urban socio-ecosystemic services. This conceptual approach is applied to three research cases in Andalusia (Spain) neighbourhoods linked to participatory urban renewal processes. A model is inductively defined from these analysed case studies: the socio-ecosystemic services model, based on the conceptual frame, the development of particular instruments and the definition of a participatory methodological strategy. The results obtained in these urban workshops show that the socio-ecosystem model better integrates the relationships between the architectural, socio-economic and ecological dimensions in addressing the need for urban services and infrastructure and the quality of life in neighbourhoods. Citizens can formulate their needs and perceptions of the neighbourhood beyond traditional quantitative variables (i.e. number of car parks, average size of dwellings, population density, etc.), incorporating aspects such as urban landscape, air quality, urban noise, shaded rest areas and children’s spaces. All these perceptions are collected and transformed into proposals for neighbourhood improvement, which are assessed and prioritized by the citizens. Together with participatory processes, this approach can be considered as the key to success in urban renewal strategies in neighbourhoods. However, it is necessary to develop indicators and metrics of the relationships between the socio-economic and ecological dimensions that allow a more integrated study of the model at different urban scales.

Understanding how environmental degradation, microclimate, and management shape honey production across different spatial scales - Nicolás A. Barahona; Pablo M. Vergara; Alberto J. Alaniz; Mario A. Carvajal; Sergio A. Castro; Madelaine Quiroz; Claudia M. Hidalgo-Corrotea; Andrés Fierro (Environmental Science and Pollution Research, 2024)

Feeding ecology of the African cuttlefish Sepia bertheloti (Cephalopoda: Sepiidae) in western Africa - Airam Guerra-Marrero; Ana Espino-Ruano; Lorena Couce-Montero; David Jiménez-Alvarado; José J. Castro (Fisheries Research, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

Enzymatic de-esterification and depolymerization of apple pomace (Malus domestica var. Blanca de Asturias) pectin impacts lipid digestion in vitro - B.E. Morales-Contreras; L. Wicker; W. Rosas-Flores; J.A. Gallegos-Infante; J.C. Contreras-Esquivel; J. Morales-Castro (Food Hydrocolloids, 2024)

Decreased DNA repair capacity caused by exposure to metal mixtures is modulated by the PARP1 rs1136410 variant in newborns from a polluted metropolitan area - Marvin Paz-Sabillón; Nereida Montes-Castro; Luisa Torres-Sánchez; Luz M. Del Razo; Emilio J. Córdova; Betzabet Quintanilla-Vega (Environmental Research, 2024)

Air quality disparities mapper: An open-source web application for environmental justice - Ethan McFarlin; Falco J. Bargagli-Stoffi; Edgar Castro; Joel Schwartz; Francesca Dominici; Heresh Amini (Environmental Modelling & Software, 2024)

Biocidal and synergistic effect of three types of biologically synthesised silver/silver chloride nanoparticles - Antonio J. Muñoz; Francisco Espínola; Encarnación Ruiz; Manuel Moya; Eulogio Castro (World Journal of Microbiology and Biotechnology, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Macroinvertebrate communities reveal regional asymmetries in riverine ecosystems along a gradient of water availability in hydrologically distinct years - Joana Isabel Santos; Carlos Silva; Fernando J. M. Gonçalves; Joana Luísa Pereira; Bruno Branco Castro (Aquatic Sciences, 2024)
Climate change has been increasing the frequency and severity of drought periods. There is a need to understand how this water scarcity affects aquatic communities. The main aim of this work was to compare the macroinvertebrate communities and their bioindicator value (ecological status sensu the Water Framework Directive) in three Regions [northeast (N), central (C) and south (S)] of Portugal along a water availability and climate gradient, in two consecutive years that reflect hydrologically distinct scenarios (2018 versus 2019). The period prior to sampling (summer and autumn 2017) was extremely dry and hot, whereas climatic fluctuations in 2018–2019 (when the sampling occurred) were closer to the norm. A total of 28 sampling sites were surveyed in streams of Regions where water scarcity is differentially constitutive. The results showed a consistent environmental and ecological gradient in both years, despite the background differences. A coinciding mineralization, temperature, riparian cover and water availability gradient clearly separated Regions C (wettest) and S (driest), with Region N occupying an intermediate position. Region C had overall higher ecological quality (prevalence of sensitive organisms) in both years. Despite our a priori expectations that 2018 would represent a much more stressful condition, with larger differences across Regions (because of their constitutive background), the data suggest that macroinvertebrate communities may be resilient or adapted, to some degree, to hydrological fluctuations. Signs of more favourable conditions in 2019 were also observed (general improvement in ecological status). Studies across hydrological and climatic gradients (in time and space) are particularly important where water availability is becoming more challenging.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Sweet potato flour (Ipomoea batatas) as natural antioxidant on carcass yield and meat physicochemical characteristics of Creole chickens of Mexico and Cobb 500 - Cesar A. Pérez Torres; Fernando González Cerón; Rafael J. Macedo Barragán; Arturo Pro Martínez; Mauricio Arredondo Castro; Diana A. Gutiérrez Arenas (Tropical Animal Health and Production, 2023)

Quantification of soil N2O and CH4 fluxes using the flux gradient method on a drainage water managed farm on the eastern shore of Maryland - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agricultural and Forest Meteorology, 2023)

Discussion on different numerical treatments on the loss of hyperbolicity for the two-layer shallow water system - M.J. Castro Díaz; E.D. Fernández-Nieto; J. Garres-Díaz; T. Morales de Luna (Advances in Water Resources, 2023)

Community metabarcoding reveals the relative role of environmental filtering and spatial processes in metacommunity dynamics of soil microarthropods across a mosaic of montane forests - Víctor Noguerales; Emmanouil Meramveliotakis; Adrián Castro‐Insua; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Isaac Overcast; Hélène Morlon; Brent C. Emerson; Alfried P. Vogler; Anna Papadopoulou (Molecular Ecology, 2023)
Disentangling the relative role of environmental filtering and spatial processes in driving metacommunity structure across mountainous regions remains challenging, as the way we quantify spatial connectivity in topographically and environmentally heterogeneous landscapes can influence our perception of which process predominates. More empirical data sets are required to account for taxon‐ and context‐dependency, but relevant research in understudied areas is often compromised by the taxonomic impediment. Here we used haplotype‐level community DNA metabarcoding, enabled by stringent filtering of amplicon sequence variants (ASVs), to characterize metacommunity structure of soil microarthropod assemblages across a mosaic of five forest habitats on the Troodos mountain range in Cyprus. We found similar β diversity patterns at ASV and species (OTU, operational taxonomic unit) levels, which pointed to a primary role of habitat filtering resulting in the existence of largely distinct metacommunities linked to different forest types. Within‐habitat turnover was correlated to topoclimatic heterogeneity, again emphasizing the role of environmental filtering. However, when integrating landscape matrix information for the highly fragmented Quercus alnifolia habitat, we also detected a major role of spatial isolation determined by patch connectivity, indicating that stochastic and niche‐based processes synergistically govern community assembly. Alpha diversity patterns varied between ASV and OTU levels, with OTU richness decreasing with elevation and ASV richness following a longitudinal gradient, potentially reflecting a decline of genetic diversity eastwards due to historical pressures. Our study demonstrates the utility of haplotype‐level community metabarcoding for characterizing metacommunity structure of complex assemblages and improving our understanding of biodiversity dynamics across mountainous landscapes worldwide.

Report on the first two confirmed autochthonous cases of West Nile virus encephalitis in Catalonia, Spain - Carles García-Cervera; Simona Mihaela Iftimie; Miguel J. Martínez; Ana Vázquez González; Sandra Parra-Pérez; Laia Revuelta-López-Cordón; Joan Gil-Toral; Rosa Mercè Vileu Vallverdu; Ana Martínez Mateo; Ana Felisa López-Azcona; Isabel Pujol-Bajador; Frederic Ballester-Bastardie; et al. (Infectious Diseases, 2023)

Understanding socioecological interaction networks in Marine Protected Areas to inform management - Silvia de Juan; Andres Ospina-Alvarez; Antonio J. Castro; Emilio Fernández; Gonzalo Méndez-Martínez; Jone Molina; Pablo Pita; Ana Ruiz-Frau; Gabriela de Abreu; Sebastian Villasante (Ocean & Coastal Management, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Land transformation changes people´s values of ecosystem services in Las Vegas agrarian landscapes of Madrid Spain - Irene Pérez-Ramírez; Juan Miguel Requena-Mullor; Antonio J. Castro; Marina García-Llorente (Land Use Policy, 2023)

Identification of potential invasive alien species in Spain through horizon scanning - Carlos Cano-Barbacil; Martina Carrete; Pilar Castro-Díez; Miguel Delibes-Mateos; Josep A. Jaques; Marta López-Darias; Manuel Nogales; Joan Pino; Macarena Ros; Anna Traveset; Xavier Turon; Montserrat Vilà; et al. (Journal of Environmental Management, 2023)

Reconstructing depositional environments through cave interior facies: The case of Galería Complex (Sierra de Atapuerca, Spain) - I. Campaña; A. Benito-Calvo; A. Pérez-González; A.I. Ortega; A. Álvaro-Gallo; L. Miguens-Rodríguez; J. Iglesias-Cibanal; J.M. Bermúdez de Castro; E. Carbonell (Geomorphology, 2023)

Basking in the sun: how mosses photosynthesise and survive in Antarctica - Hao Yin; Alicia V. Perera-Castro; Krystal L. Randall; Johanna D. Turnbull; Melinda J. Waterman; Jodie Dunn; Sharon A. Robinson (Photosynthesis Research, 2023)
The Antarctic environment is extremely cold, windy and dry. Ozone depletion has resulted in increasing ultraviolet-B radiation, and increasing greenhouse gases and decreasing stratospheric ozone have altered Antarctica’s climate. How do mosses thrive photosynthetically in this harsh environment? Antarctic mosses take advantage of microclimates where the combination of protection from wind, sufficient melt water, nutrients from seabirds and optimal sunlight provides both photosynthetic energy and sufficient warmth for efficient metabolism. The amount of sunlight presents a challenge: more light creates warmer canopies which are optimal for photosynthetic enzymes but can contain excess light energy that could damage the photochemical apparatus. Antarctic mosses thus exhibit strong photoprotective potential in the form of xanthophyll cycle pigments. Conversion to zeaxanthin is high when conditions are most extreme, especially when water content is low. Antarctic mosses also produce UV screening compounds which are maintained in cell walls in some species and appear to protect from DNA damage under elevated UV-B radiation. These plants thus survive in one of the harshest places on Earth by taking advantage of the best real estate to optimise their metabolism. But survival is precarious and it remains to be seen if these strategies will still work as the Antarctic climate changes.

Comparing RNA extraction methods to face the variations in RNA quality using two human biological matrices - J. Ortega-Pinazo; M. J. Pacheco-Rodríguez; P. J. Serrano-Castro; B. Martínez; M. J. Pinto-Medel; J. M. Gómez-Zumaquero; A. Lago-Sampedro; B. García-Díaz; Guillermo Estivill-Torrús; Pedro Emilio Ferro Gallego (Molecular Biology Reports, 2023)

Binge drinking leads to an oxidative and metabolic imbalance in skeletal muscle during adolescence in rats: endocrine repercussion - Inés Romero-Herrera; Fátima Nogales; Javier Diaz-Castro; Jorge Moreno-Fernandez; María del Carmen Gallego-Lopez; Julio J. Ochoa; Olimpia Carreras; María Luisa Ojeda (Journal of Physiology and Biochemistry, 2023)
Binge drinking (BD) is an especially pro-oxidant model of alcohol consumption, mainly used by adolescents. It has recently been related to the hepatic IR-process. Skeletal muscle is known to be involved in insulin action and modulation through myokine secretion. However, there is no information on muscle metabolism and myokine secretion after BD exposure in adolescents. Two experimental groups of adolescent rats have been used: control and BD-exposed one. Oxidative balance, energy status and lipid, and protein metabolism have been analyzed in muscle, together with myokine serum levels (IL-6, myostatin, LIF, IL-5, fractalkine, FGF21, irisin, BDNF, FSTL1, apelin, FABP3, osteocrin, osteonectin (SPARC), and oncostatin). In muscle, BD affects the antioxidant enzyme balance leading to lipid and protein oxidation. Besides, it also increases the activation of AMPK and thus contributes to decrease SREBP1 and pmTOR and to increase FOXO3a expressions, promoting lipid and protein degradation. These alterations deeply affect the myokine secretion pattern. This is the first study to examine a general myokine response after exposure to BD. BD not only caused a detrimental imbalance in myokines related to muscle turnover, decreased those contributing to increase IR-process, decreased FST-1 and apelin and their cardioprotective function but also reduced the neuroprotective BDNF. Consequently, BD leads to an important metabolic and energetic disequilibrium in skeletal muscle, which contributes to exacerbate a general IR-process.

Age, growth, and feeding of boarfish, Capros aper (Linnaeus, 1758) in the Southwest of the Iberian Peninsula - J. Castro-Gutiérrez; A. García-González; C. Rodríguez-García; Á. R. Domínguez-Bustos; R. Cabrera-Castro (Marine Biology Research, 2023)

Whose values count? A review of the nature valuation studies with a focus on justice - M Schaafsma; S Ahn; AJ Castro; N Dendoncker; A Filyushkina; D González-Jiménez; Mariaelena Huambachano; N Mukherjee; TH Mwampamba; J Ngouhouo-Poufoun; I Palomo; R Pandit; et al. (Current Opinion in Environmental Sustainability, 2023)

The pitfalls of plural valuation - Sander Jacobs; Eszter Kelemen; Patrick O’Farrell; Adrian Martin; Marije Schaafsma; Nicolas Dendoncker; Ram Pandit; Tuyeni H Mwampamba; Ignacio Palomo; Antonio J Castro; Mariaelena A Huambachano; Anna Filyushkina; et al. (Current Opinion in Environmental Sustainability, 2023)

Five steps towards transformative valuation of nature - Mette Termansen; Sander Jacobs; Ram Pandit; Tuyeni H. Mwampamba; Nicolas Dendoncker; Marije Schaafsma; Victoria Contreras; Davide González-Jiménez; Haripriya Gundimeda; Heera Lee; Anna Filyushkina; Mariaelena Huambachano; et al. (Current Opinion in Environmental Sustainability, 2023)

Age, growth, and population structure of the African cuttlefish Sepia bertheloti based on beak microstructure - Airam Guerra-Marrero; Aurora Bartolomé; Lorena Couce-Montero; Ana Espino-Ruano; David Jiménez-Alvarado; José J. Castro; Catalina Perales-Raya (Marine Biology, 2023)
In this study, we explored the feasibility of using the beaks of the African cuttlefish Sepia bertheloti for age estimation and growth analysis. The rostrum sagittal section (RSS) of the lower beak was the most suitable region in the species. It was applied in samples caught off Morocco and Guinea-Bissau between June 2018 and January 2020. A maximum life expectancy of around 14 months was observed (specifically 419 days for cuttlefishes from Morocco and 433 from Guinea-Bissau). The males presented greater longevity, as the maximum age of the females was between 9 and 11 months. Sepia bertheloti showed a negative allometric growth; however, the exponential model better describes each population growth. By sexes, the males of both locations followed an asymptotic growth model while the females exhibited a non-asymptotic growth. The growth rates were different between locations, with the highest values in Guinea-Bissau. The males, in turn, grew faster for both study locations. In Guinea-Bissau, these growth differences were influenced by the hatching season since individuals born between autumn and winter were the fastest-growing. Samples from Morocco did not show growth differences between the hatching season and other seasons. These results indicate that the RSS of lower beaks are suitable for estimating the age, growth pattern, and population structure of Sepia bertheloti .

Multi-analytical characterization of an oncoid from a high altitude hypersaline lake using techniques employed in the Mars2020 and Rosalind Franklin missions on Mars - J. Huidobro; J.M. Madariaga; D. Carrizo; J.L. Laserna; F. Rull; J. Martínez-Frías; J. Aramendia; L. Sánchez-García; L. García-Gómez; F.A. Vignale; M.E. Farías; M. Veneranda; et al. (Analytica Chimica Acta, 2023)

P21-22: Evaluation of the neurotoxicity and electrophysiological effect of new ixodicidal carbamates in a murine model - A. G. Martínez González; S. M. Gómez Castro; J. F. Lazcano Reyes; V. Vázquez Valadez; M. Muñoz Guzmán; E. Angeles; F. Alba Hurtado; M. G. Prado Ochoa (Toxicology Letters, 2023)

Diverse values of nature shape human connection to dryland landscapes in Spain - Youssra El Ghafraoui; Cristina Quintas-Soriano; Manuel Pacheco-Romero; Beatriz E. Murillo-López; Antonio J. Castro (Journal of Arid Environments, 2023)

Varietal response to soybean target spot (Corynespora cassiicola) in the Brazilian Neotropical Savannah - Érica de Castro Costa; Justino J. Dias-Neto; Lincoln V. A. S. Bizerra; Nédio Tormen; Pierce A. Paul; Adalberto C. Café-Filho (Phytoparasitica, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Modulating cyclic nucleotides pathways by bioactive compounds in combatting anxiety and depression disorders - Citlaly Gutiérrez-Rodelo; Shirlley Elizabeth Martínez-Tolibia; Guadalupe Elide Morales-Figueroa; Josué Arturo Velázquez-Moyado; J Alberto Olivares-Reyes; Andrés Navarrete-Castro (Molecular Biology Reports, 2023)
Anxiety and depression disorders are highly prevalent neurological disorders (NDs) that impact up to one in three individuals during their lifetime. Addressing these disorders requires reducing their frequency and impact, understanding molecular causes, implementing prevention strategies, and improving treatments. Cyclic nucleotide monophosphates (cNMPs) like cyclic adenosine monophosphate (cAMP), cyclic guanosine monophosphate (cGMP), cyclic uridine monophosphate (cUMP), and cyclic cytidine monophosphate (cCMP) regulate the transcription of genes involved in neurotransmitters and neurological functions. Evidence suggests that cNMP pathways, including cAMP/cGMP, cAMP response element binding protein (CREB), and Protein kinase A (PKA), play a role in the physiopathology of anxiety and depression disorders. Plant and mushroom-based compounds have been used in traditional and modern medicine due to their beneficial properties. Bioactive compound metabolism can activate key pathways and yield pharmacological outcomes. This review focuses on the molecular mechanisms of bioactive compounds from plants and mushrooms in modulating cNMP pathways. Understanding these processes will support current treatments and aid in the development of novel approaches to reduce the prevalence of anxiety and depression disorders, contributing to improved outcomes and the prevention of associated complications. Graphical abstract

The role of emotions in human–nature connectedness within Mediterranean landscapes in Spain - Irene Otamendi-Urroz; Cristina Quintas-Soriano; Berta Martín-López; Mónica Expósito-Granados; Daniela Alba-Patiño; Emilio Rodríguez-Caballero; Marina García-Llorente; Antonio J. Castro (Sustainability Science, 2023)
Landscapes can lead to different emotions towards nature that in turn shape people’s environmental behavior and decision processes. This study explores the role of emotions that Mediterranean landscapes foster in people and to what extent these emotions are associated with human–nature connectedness (HNC). We conducted 176 face-to-face surveys to explore HNC and the diversity of emotions associated with a suite of landscapes in Southeast Spain. Results revealed that Marine and Coastal Protected Areas received the highest number of positive emotions, whereas Greenhouses and Non-Protected Littoral were linked to negative emotions. We propose a framework for classifying emotional landscapes according to four groups: emotionally positive, negative, polarized or neutral. Results showed that emotions might play a key role in shaping HNC in Spanish Mediterranean landscapes and may be used as a common ground for understanding roots underpinning human decisions and actions that lead to sustainable management or landscape degradation.

Binary fluoride and As(V) adsorption in water using pleco fish bone chars - Sergio A. Cruz-Briano; Nahum A. Medellin-Castillo; Pablo Delgado-Sanchez; Guillermo J. Castro-Larragoitia; Roberto Leyva-Ramos; Miguel A. Cortina-Rangel; Gladis J. Labrada-Delgado; Diana E. Villela-Martinez; Alfredo I. Flores-Rojas; Lázaro A. Gonzalez-Fernandez; Hilda G. Cisneros-Ontiveros (Environmental Science and Pollution Research, 2023)

A new methodology for kerogen maturity estimation based on Raman spectroscopy and chemometric analysis - J. Aramendia; M. Tuite; K. Castro; J.M. Madariaga (Science of The Total Environment, 2023)

First record of partial albinism in the critically endangered Angelshark ( Squatina squatina ) (Linnaeus, 1758) - David Jimenez‐Alvarado; Eva Meyers; Airam Guerra‐Marrero; Ana Espino‐Ruano; Lorena Couce‐Montero; Joanna Barker; Michael Sealey; Héctor Toledo; Belén Caro; Charlotte Pike; David M.P. Jacoby; Lucy Mead; et al. (Journal of Fish Biology, 2023)
We report the first case of partial albinism in the Critically Endangered angelshark, Squatina squatina . The encounter with this specimen took place while SCUBA diving on the beach of Tufia, located on the east coast of the island of Gran Canaria on 2 April 2021. This is also the first confirmed finding of an albino elasmobranch specimen in the Canary Island archipelago.

Use of granules and free salts for Fe and Zn fortification of leafy vegetables: Improvements in trace element bioaccessibility and fulfillment of Dietary Reference Intakes - J. Martínez-Castro; F. Cámara-Martos; A. Moreno-Ortega; M. Victorio-Sánchez; A. Krstova; J. Almeida Lopes; F. Pérez-Rodríguez (Journal of Trace Elements in Medicine and Biology, 2023)

Dereplication of Siparuna brasiliensis extract with in vivo anti-inflammatory activity - Leandro A. Castro; Nerilson M. Lima; Gracimério J. Guarneire; Gabriela P. Carli; Allyne Aparecida S. Castro; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Boniek Gontijo Vaz; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Emerging microalgae-based biofuels: Technology, life-cycle and scale-up - B.B. Marangon; I.B. Magalhães; A.S.A.P. Pereira; T.A. Silva; R.C.N. Gama; J. Ferreira; J.S. Castro; L.R. Assis; J.F. Lorentz; M.L. Calijuri (Chemosphere, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Epigenetic regulation of collagen in the mare's placenta: putative relationship with maternal age - Manuel A. Vasconcelos; Yat Wong; Joana Alpoim-Moreira; Maria R. Rebordão; Maria J. Fradinho; Ana L. Costa; Miguel Bliebernicht; Fidel O. Castro; Elisabete Silva; Graça M. Ferreira-Dias (Journal of Equine Veterinary Science, 2023)

Efficacy of progressive versus severe energy restriction on body composition and strength in concurrent trained women - Salvador Vargas-Molina; Diego A. Bonilla; Jorge L. Petro; Leandro Carbone; Manuel García-Sillero; José Manuel Jurado-Castro; Brad J. Schoenfeld; Javier Benítez-Porres (European Journal of Applied Physiology, 2023)
Purpose This study evaluated the concurrent training (CT) effect in combination with either progressive energy restriction (PER) or severe energy restriction (SER) on body composition and strength-related variables in resistance-trained women. Methods Fourteen women (29.5 ± 3.8 years; 23.8 ± 2.8 kg·m −2 ) were randomly assigned to a PER ( n = 7) or SER ( n = 7) group. Participants performed an 8-week CT program. Pre- and post-intervention measures of fat mass (FM) and fat-free mass (FFM) were assessed by dual-energy X-ray absorptiometry and strength-related variables were assessed through 1-repetition maximum (in the squat and bench press) and countermovement jump. Results Significant reductions in FM were observed in PER and SER (Δ = − 1.7 ± 0.4 kg; P = < 0.001; ES = − 0.39 and Δ = − 1.2 ± 0.6 kg; P = 0.002; ES = − 0.20, respectively). After correcting FFM for fat-free adipose tissue (FFAT), no significant differences for this variable were found either in PER (Δ = − 0.3 ± 0.1; P = 0.071; ES = − 0.06) or in SER (Δ = − 0.2 ± 0.1; P = 0.578; ES = − 0.04). There were no significant changes in the strength-related variables. No between-group differences were found in any of the variables. Conclusion A PER has similar effects to a SER on body composition and strength in resistance-trained women performing a CT program. Given that PER is more flexible and thus may enhance dietary adherence, it might be a better alternative for FM reduction compared to SER.

Environmental and biotic filters interact to shape the coexistence of native and introduced bees in northern Patagonian forests - Pablo M. Vergara; Andrés Fierro; Mario A. Carvajal; Alberto J. Alaniz; Francisco Zorondo-Rodríguez; María C. Cifuentes; Sergio A. Castro (Agriculture, Ecosystems & Environment, 2023)

Assessing high quality agricultural lands through the ecosystem services lens: Insights from a rapidly urbanizing agricultural region in the western United States - Sarah Halperin; Antonio J. Castro; Cristina Quintas-Soriano; Jodi S. Brandt (Agriculture, Ecosystems & Environment, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Oral formulation of Wnt inhibitor complex reduces inflammation and fibrosis in intraperitoneal implants in vivo - Ana Luíza de Castro Santos; Natália Jordana Alves da Silva; Celso Tarso Rodrigues Viana; Letícia Cristine Cardoso dos Santos; Gabriel Henrique Costa da Silva; Sérgio Ricardo Aluotto Scalzo Júnior; Pedro Augusto Carvalho Costa; Walison Nunes da Silva; Itamar Couto Guedes de Jesus; Alexander Birbrair; Mariana T. Q. de Magalhães; Frédéric Frézard; et al. (Drug Delivery and Translational Research, 2023)

Assessment of eutrophication from phosphorus remobilization after resuspension of coastal sediments from an urban tropical estuary - Christiane do N. Monte; Ana Paula de Castro Rodrigues; Matheus Cavalcante Silva; Luana J. S. Ferreira; Gustavo Monte; Carla Semiramis Silveira; Renato Campello Cordeiro; Wilson Machado (Environmental Science and Pollution Research, 2023)

Worker versus Employer Perspectives on Safety in the Forestry Services Industry - A. B. de Castro; Carl Wilmsen; Sara Post; Marcy J. Harrington; Diane Bush (Journal of Agromedicine, 2023)

Bioaccessibility of glucosinolates, isothiocyanates and inorganic micronutrients in cruciferous vegetables through INFOGEST static in vitro digestion model - J. Martínez-Castro; A. de Haro-Bailón; S. Obregón-Cano; I.Mª. García Magdaleno; A. Moreno Ortega; F. Cámara-Martos (Food Research International, 2023)

Assessment of vapor pressure deficit variability and trends in Spain and possible connections with soil moisture - I. Noguera; S.M. Vicente-Serrano; D. Peña-Angulo; F. Domínguez-Castro; C. Juez; M. Tomás-Burguera; J. Lorenzo-Lacruz; C. Azorin-Molina; A. Halifa-Marín; B. Fernández-Duque; A. El Kenawy (Atmospheric Research, 2023)

TiO2−MWCNT nanohybrid: Cytotoxicity, protein corona formation and cellular internalisation in RTG-2 fish cell line - Gabriela H. Da Silva; Lidiane Silva Franqui; Marcelo A. De Farias; Vera Lucia S.S. De Castro; Hugh J. Byrne; Diego S.T. Martinez; Regina T.R. Monteiro; Alan Casey (Aquatic Toxicology, 2023)

Farmers’ perceptions and acceptance of crossbred guinea pigs in Mantaro Valley, Peru - J. I. Cedano-Castro; R. Jiménez; A. Huamán; G. Gutiérrez Reynoso; M. Wurzinger (Tropical Animal Health and Production, 2023)
This study aimed at assessing farmers’ perceptions and acceptance of the proposed breeding strategy of Instituto Veterinario de Investigaciones Tropicales y de Altura (IVITA), located in the Central Andes of Peru. A total of 34 farmers, who had received guinea pigs from IVITA, were interviewed. The questionnaire was performed in Spanish language and covered topics about the guinea pig production, feeding, mating system, training, the main products, perception and acceptance of crossbred lines (“cuy RG”), and the farmers’ comment about the terminal crossbred animal (“cuy G”). The preferred feeding strategy was a combination of forage and supplement. All farmers implemented a controlled mating system. Most farmers had received training on feeding, reproduction, management, equipment, and facilities. The main product is animals for slaughter. The 82.40% of farmers reported that they do not purchase guinea pigs from IVITA anymore, because they are highly susceptibility to lymphadenitis, which is a highly contagious disease and causes swollen lymph nodes and affects the meat quality. Most of the respondents classified the “cuy RG” and “cuy G” as suitable for meat production and were satisfied with the performance of the animals. Therefore, 58.80% of respondents already recommended “cuy RG” to other farmers. However, 17.70% of the respondents would not recommend these animals because they are susceptible to disease, especially lymphadenitis. Therefore, IVITA should engage in more structured dialogue with farmers and regularly include their opinion in future improvement of its breeding strategies. This could help to reach higher acceptance rates by farmers.

Combined coagulation-electrocoagulation process using biocoagulant from the Opuntia ficus-indica for treatment of cheese whey wastewater - Hugo G. J. Pacheco; Naysha Y. Elguera; Midwar Ancco; Antonio E. L. F. Castro; Maria E. B. Meza; Vitor C. Almeida (Environmental Monitoring and Assessment, 2023)

Incorporating pressure–volume traits into the leaf economics spectrum - Miquel Nadal; María J. Clemente‐Moreno; Alicia V. Perera‐Castro; Margalida Roig‐Oliver; Yusuke Onoda; Javier Gulías; Jaume Flexas (Ecology Letters, 2023)
In recent years, attempts have been made in linking pressure–volume parameters and the leaf economics spectrum to expand our knowledge of the interrelationships among leaf traits. We provide theoretical and empirical evidence for the coordination of the turgor loss point and associated traits with net CO 2 assimilation ( A n ) and leaf mass per area (LMA). We measured gas exchange, pressure–volume curves and leaf structure in 45 ferns and angiosperms, and explored the anatomical and chemical basis of the key traits. We propose that the coordination observed between mass‐based A n , capacitance and the turgor loss point ( π tlp ) emerges from their shared link with leaf density (one of the components of LMA) and, specially, leaf saturated water content (LSWC), which in turn relates to cell size and nitrogen and carbon content. Thus, considering the components of LMA and LSWC in ecophysiological studies can provide a broader perspective on leaf structure and function.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Venom comparisons of endemic and micro-endemic speckled rattlesnakes Crotalus mitchellii, C. polisi and C. thalassoporus from Baja California Peninsula - Gustavo Arnaud-Franco; Emmanuel Ríos-Castro; Andrea Velasco-Suárez; Francisco J. García-de León; Luis F. Beltrán; Alejandro Carbajal-Saucedo (Toxicon, 2023)

Cross-sectoral impacts of the 2018–2019 Central European drought and climate resilience in the German part of the Elbe River basin - Tobias Conradt; Henry Engelhardt; Christoph Menz; Sergio M. Vicente-Serrano; Begoña Alvarez Farizo; Dhais Peña-Angulo; Fernando Domínguez-Castro; Lars Eklundh; Hongxiao Jin; Boris Boincean; Conor Murphy; J. Ignacio López-Moreno (Regional Environmental Change, 2023)
The 2018–2019 Central European drought was probably the most extreme in Germany since the early sixteenth century. We assess the multiple consequences of the drought for natural systems, the economy and human health in the German part of the Elbe River basin, an area of 97,175 km 2 including the cities of Berlin and Hamburg and contributing about 18% to the German GDP. We employ meteorological, hydrological and socio-economic data to build a comprehensive picture of the drought severity, its multiple effects and cross-sectoral consequences in the basin. Time series of different drought indices illustrate the severity of the 2018–2019 drought and how it progressed from meteorological water deficits via soil water depletion towards low groundwater levels and river runoff, and losses in vegetation productivity. The event resulted in severe production losses in agriculture (minus 20–40% for staple crops) and forestry (especially through forced logging of damaged wood: 25.1 million tons in 2018–2020 compared to only 3.4 million tons in 2015–2017), while other economic sectors remained largely unaffected. However, there is no guarantee that this socio-economic stability will be sustained in future drought events; this is discussed in the light of 2022, another dry year holding the potential for a compound crisis. Given the increased probability for more intense and long-lasting droughts in most parts of Europe, this example of actual cross-sectoral drought impacts will be relevant for drought awareness and preparation planning in other regions.

A letter to the editor about the article “The modularity codes” - Omar Paredes; Elsa Magaña-Cuevas; Sorpresa Lora-Castro; Juan D. Serna-Grilló; D.Y. De la Mora; Diana Ríos Patiño; Rebeca Romo-Vázquez; J. Alejandro Morales (Journal of Theoretical Biology, 2023)

A social study of the technicians dealing with refrigerant gases: Diagnosis of the behaviours, knowledge and importance attributed to the F-gases - Graça Martinho; Paulo J. Castro; Pedro Santos; Ana Alves; João M.M. Araújo; Ana B. Pereiro (International Journal of Refrigeration, 2023)

Age validation in early stages of Sepia officinalis from beak microstructure - Airam Guerra-Marrero; Catalina Perales-Raya; Fedor Lishchenko; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Marine Biology, 2023)
This is the first study addressing validation of the early growth stages (including the first increment) in the beaks of juvenile cuttlefishes. The age validation in juveniles of Sepia officinalis was performed by comparison of the number of increments observed in the rostrum surface of lower jaws with their true age. A total of 159 individuals were reared at 18 ºC and 21 ºC, with ages up to 31 days from hatching. The number of growth increments in the beak was counted and contrasted with the days of life after hatching, validating the hypothesis of one increment of growth corresponding to one day of life. The mean coefficient of variation between readings (measuring precision) was 2.95 ± 5.98%. The growth of the reading area (rostrum surface) and the periodicity of increment deposition showed no difference between the two culture temperatures and therefore daily deposition was confirmed at these temperatures.

Macroinvertebrate community structure and ecological status in Portuguese streams across climatic and water scarcity gradients - Joana Isabel Santos; Carlos Silva; Fernando J. M. Gonçalves; Joana Luísa Pereira; Bruno Branco Castro (Hydrobiologia, 2023)
Climatic and hydrological variation is of utmost importance in regions of the globe facing water scarcity and river intermittency (e.g. areas under Mediterranean influence). The main aim of this study was to compare the macroinvertebrate community structure and its bioindicator value (i.e. waterbody ecological status) in streams from three Portuguese regions (Regions C, N and S), representing distinct climatic features and water availability scenarios. Results showed that, overall, sampling sites differed in their climatic, hydromorphological and physical and chemical features, and environmental (abiotic) and ecological (community dissimilarities) gradients among regions were clearly identified. Sites from Regions C (wettest) and S (driest) represented non-overlapping clusters of samples, both in terms of their environmental context and ecological (dis)similarity; sites from Region N occupied an intermediate position, and their macroinvertebrate community was highly variable locally. This coincided with overall higher ecological quality and uniformity in Region C, whereas Regions N and S were more heterogeneous and generally presented lower ecological quality. Our data showed that climate (and associated water scarcity) is coupled with other environmental drivers of the macroinvertebrate community structure, highlighting a shared influence of the three environmental components (climatic, hydromorphological, and physical and chemical) in the modulation of macroinvertebrate communities.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Neogene-Quaternary evolution of the La Baja Guajira basin, Colombia: Burial and thermal history with implications on petroleum systems - Leidy Castro-Vera; Ralf Littke; Stefan Back; Rocío Bernal-Olaya; Martin Reyes; J. Alejandro Mora-Bohórquez; A. Johamna Romero (Journal of South American Earth Sciences, 2023)

A clustering approach to analyse the environmental and energetic impacts of Atlantic recipes - A Galician gastronomy case study - Cristina Cambeses-Franco; Sara González-García; Mar Calvo-Malvar; Alfonso J. Benítez-Estévez; Rosaura Leis; Juan Sánchez-Castro; Francisco Gude; Gumersindo Feijoo; María Teresa Moreira (Journal of Cleaner Production, 2023)

Risk scores’ performance and their impact on operative decision-making in left-sided endocarditis: a cohort study - A. Fernández-Cisneros; M. Hernández-Meneses; J. Llopis; E. Sandoval; D. Pereda; J. Alcocer; C. Barriuso; M. Castellá; J. Ambrosioni; J. M. Pericàs; B. Vidal; C. Falces; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The accuracy of contemporary risk scores in predicting perioperative mortality in infective endocarditis (IE) remains controversial. The aim is to evaluate the performance of existent mortality risk scores for cardiovascular surgery in IE and the impact on operability at high-risk thresholds. A single-center retrospective review of adult patients diagnosed with acute left-sided IE undergoing surgery from May 2014 to August 2019 ( n = 142) was done. Individualized risk calculation was obtained according to the available mortality risk scores: EuroScore I and II, PALSUSE, Risk-E, Costa, De Feo-Cotrufo, AEPEI, STS-risk, STS-IE, APORTEI, and ICE-PCS scores. A cross-validation analysis was performed on the score with the best area under the curve (AUC). The 30-day survival was 96.5% (95%CI 91–98%). The score with worse area under the curve (AUC = 0.6) was the STS-IE score, while the higher was for the RISK-E score (AUC = 0.89). The AUC of the majority of risk scores suggested acceptable performance; however, statistically significant differences in expected versus observed mortalities were common. The cross-validation analysis showed that a large number of survivors (> 75%) would not have been operated if arbitrary high-risk threshold estimates had been used to deny surgery. The observed mortality in our cohort is significantly lower than is predicted by contemporary risk scores. Despite the reasonable numeric performance of the analyzed scores, their utility in judging the operability of a given patient remains questionable, as demonstrated in the cross-validation analysis. Future guidelines may advise that denial of surgery should only follow a highly experienced Endocarditis Team evaluation.

Revision of TD1 and TD2 stratigraphic sequence of Gran Dolina cave (Sierra de Atapuerca, Spain) - I. Campaña; A. Benito-Calvo; A. Pérez-González; A. Álvaro-Gallo; L. Miguens-Rodríguez; J. Iglesias-Cibanal; J. M. Bermúdez de Castro; E. Carbonell (Journal of Iberian Geology, 2022)
Gran Dolina is a cavity infilled by at least 25 m of Pleistocene sediments divided into 12 lithostratigraphic units and 19 sedimentary facies. These sedimentary facies have been divided into allochthonous facies, defined as sediment inputs from the outside, and autochthonous facies, defined as sediments generated within the karst; but this division has been challenged in recent works. In this study, TD1 and TD2 units of Gran Dolina have been detailed studied and the use of autochthonous facies has been assessed. For that purpose, we have studied the stratigraphic excavation profile, combining field observation with laboratory sedimentary analysis (sieving, laser diffraction, and XRD) to characterize the texture and structure of the sediments. Based on these studies, a total of 8 sedimentary facies have been identified. Consequently, TD1 unit has been separated into two sub-units and 13 layers, while the TD2 unit has been divided into three sub-units. The facies associations indicate a succession of phreatic and vadose phases that would define together epiphreatic conditions inside the cave, related to the transition between Arlanzón valley terraces T3 and T4. Interior facies (and entrance facies for allochthonous facies) is proposed to define Gran Dolina's sediments since the facies analyses indicate transport by underground flows.

Bradyrhizobium occurrence in nodules of perennial horsegram - Mayan Blanc Amaral; Tamiris dos Santos Lopes; Caroline Bueno Feder; Thiago Gonçalves Ribeiro; Rafael Sanches Pacheco; Thiago Neves Teixeira; Edevaldo de Castro Monteiro; Israel Oliveira Ramalho; Robert de O. Macedo; Robert M. Boddey; Jerri Edson Zilli; Bruno J. R. Alves (Brazilian Journal of Microbiology, 2022)

Marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef: Strengthening management and preparedness - Eduardo Cuevas; María de los Angeles Liceaga-Correa; Abigail Uribe-Martínez; Sandra A. Gallegos-Fernández; Félix Moncada-Gavilán; Raúl J. González-Díaz-Mirón; Melania C. López-Castro; Vicente Guzmán-Hernández; Martha López (Frontiers in Marine Science, 2022)
Marine turtles are of the highest ecological concern in terms of conservation and restoration programs and marine territorial ordering. Marine resource-extracting industries have severe negative impacts on their populations and their habitats. Thus, private industries and decision makers require the best and most robust spatially explicit scientific knowledge for a sustainable and responsible operation and government administration. Therefore, the identification of marine turtle hotspots is a strategic milestone for ecosystem management and an integral ecological knowledge about any region. We identified and delimited marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef. We analyzed satellite-tracked data of 178 individuals belonging to four marine turtle species. We used Brownian bridge movement models to estimate space use surfaces and map algebra to weight and merge layers of multiple species, life stages, and movement phases. The Yucatan Peninsula and central Veracruz in Mexico, along with the Florida Keys and Louisiana coast in the US, harbor the primary hotspots where marine turtles aggregate. We defined four primary hotspots used for migration in the western Gulf of Mexico, around the Yucatan Peninsula, a northern route following the Loop Current, and a southern one towards Gorda Bank, Central America. This study is the largest assessment of marine turtle hotspots in Mexico and Cuba and supports strategies for reinforcing regional management actions for their conservation, as well as a stronger response and preparedness for tackling anthropic threats to these species. This milestone contributes to extending the knowledge frontiers about these species to a new level.

Use of a recombinant positive control in the diagnostic of canine Ehrlichiosis from 16sRNA gen of Ehrlichia canis in Mexico City - S. E. Acevedo-Monroy; J. M. Méndez-Alemán; I. Castro-Mendoza; M. A. Mojica-Sánchez; A. Verdugo-Rodríguez (Archives of Microbiology, 2022)

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Evaluating different metrics from the thermal-based two-source energy balance model for monitoring grapevine water stress - Héctor Nieto; María Mar Alsina; William P. Kustas; Omar García-Tejera; Fan Chen; Nicolas Bambach; Feng Gao; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Lynn G. McKee; Einara Zahn; et al. (Irrigation Science, 2022)
Precision irrigation management requires operational monitoring of crop water status. However, there is still some controversy on how to account for crop water stress. To address this question, several physiological, several physiological metrics have been proposed, such as the leaf/stem water potentials, stomatal conductance, or sap flow. On the other hand, thermal remote sensing has been shown to be a promising tool for efficiently evaluating crop stress at adequate spatial and temporal scales, via the Crop Water Stress Index (CWSI), one of the most common indices used for assessing plant stress. CWSI relates the actual crop evapotranspiration ET (related to the canopy radiometric temperature) to the potential ET (or minimum crop temperature). However, remotely sensed surface temperature from satellite sensors includes a mixture of plant canopy and soil/substrate temperatures, while what is required for accurate crop stress detection is more related to canopy metrics, such as transpiration, as the latter one avoids the influence of soil/substrate in determining crop water status or stress. The Two-Source Energy Balance (TSEB) model is one of the most widely used and robust evapotranspiration model for remote sensing. It has the capability of partitioning ET into the crop transpiration and soil evaporation components, which is required for accurate crop water stress estimates. This study aims at evaluating different TSEB metrics related to its retrievals of actual ET, transpiration and stomatal conductance, to track crop water stress in a vineyard in California, part of the GRAPEX experiment. Four eddy covariance towers were deployed in a Variable Rate Irrigation system in a Merlot vineyard that was subject to different stress periods. In addition, root-zone soil moisture, stomatal conductance and leaf/stem water potential were collected as proxy for in situ crop water stress. Results showed that the most robust variable for tracking water stress was the TSEB derived leaf stomatal conductance, with the strongest correlation with both the measured root-zone soil moisture and stomatal conductance gas exchange measurements. In addition, these metrics showed a better ability in tracking stress when the observations are taken early after noon.

Application of the vineyard data assimilation (VIDA) system to vineyard root-zone soil moisture monitoring in the California Central Valley - Fan Chen; Fangni Lei; Kyle Knipper; Feng Gao; Lynn McKee; Maria del Mar Alsina; Joseph Alfieri; Martha Anderson; Nicolas Bambach; Sebastian J. Castro; Andrew J. McElrone; Karrin Alstad; et al. (Irrigation Science, 2022)

Inter-annual variability of land surface fluxes across vineyards: the role of climate, phenology, and irrigation management - N. Bambach; W. Kustas; J. Alfieri; F. Gao; J. Prueger; L. Hipps; L. McKee; S. J. Castro; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Irrigation and other agricultural management practices play a key role in land surface fluxes and their interactions with atmospheric processes. California’s Central Valley agricultural productivity is strongly linked to water availability associated with conveyance infrastructure and groundwater, but greater scrutiny over agricultural water use requires better practices particularly during extended and severe drought conditions. The future of irrigated agriculture in California is expected to be characterized neither by perpetual scarcity nor by widespread abundance. Thus, further advancing irrigation technologies and improving management practices will be key for California’s agriculture sustainability. In this study, we present micrometeorological observations from the Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project. Daily, seasonal, and inter-seasonal surface flux patterns and relationships across five vineyards over three distinct California wine production regions were investigated. Vineyard actual evapotranspiration showed significant differences at the sub-daily and daily scale when comparisons across wine production regions and varieties were performed. Water use in vineyards in the Central Valley was about 70% greater in comparison to the vineyards at the North Coast area due to canopy size, atmospheric demand, and irrigation inputs. Inter-annual variability of surface fluxes was also significant, even though, overall weather conditions (i.e., air temperature, vapor pressure deficit, wind speed, and solar radiation) were not significantly different. Thus, not only irrigation but also other management practices played a key role in seasonal water use, and given these differences, we conclude that further advancing ground-based techniques to quantify crop water use at an operational scale will be key to facing California’s agriculture present and future water challenges.

Application of a remote-sensing three-source energy balance model to improve evapotranspiration partitioning in vineyards - Vicente Burchard-Levine; Héctor Nieto; William P. Kustas; Feng Gao; Joseph G. Alfieri; John H. Prueger; Lawrence E. Hipps; Nicolas Bambach-Ortiz; Andrew J. McElrone; Sebastian J. Castro; Maria Mar Alsina; Lynn G. McKee; et al. (Irrigation Science, 2022)
Improved accuracy of evapotranspiration (ET) estimation, including its partitioning between transpiration (T) and surface evaporation (E), is key to monitor agricultural water use in vineyards, especially to enhance water use efficiency in semi-arid regions such as California, USA. Remote-sensing methods have shown great utility in retrieving ET from surface energy balance models based on thermal infrared data. Notably, the two-source energy balance (TSEB) has been widely and robustly applied in numerous landscapes, including vineyards. However, vineyards add an additional complexity where the landscape is essentially made up of two distinct zones: the grapevine and the interrow, which is often seasonally covered by an herbaceous cover crop. Therefore, it becomes more complex to disentangle the various contributions of the different vegetation elements to total ET, especially through TSEB, which assumes a single vegetation source over a soil layer. As such, a remote-sensing-based three-source energy balance (3SEB) model, which essentially adds a vegetation source to TSEB, was applied in an experimental vineyard located in California’s Central Valley to investigate whether it improves the depiction of the grapevine-interrow system. The model was applied in four different blocks in 2019 and 2020, where each block had an eddy-covariance (EC) tower collecting continuous flux, radiometric, and meteorological measurements. 3SEB’s latent and sensible heat flux retrievals were accurate with an overall RMSD ~ 50 W/m 2 compared to EC measurements. 3SEB improved upon TSEB simulations, with the largest differences being concentrated in the spring season, when there is greater mixing between grapevine foliage and the cover crop. Additionally, 3SEB’s modeled ET partitioning (T/ET) compared well against an EC T/ET retrieval method, being only slightly underestimated. Overall, these promising results indicate 3SEB can be of great utility to vineyard irrigation management, especially to improve T/ET estimations and to quantify the contribution of the cover crop to ET. Improved knowledge of T/ET can enhance grapevine water stress detection to support irrigation and water resource management.

Evapotranspiration uncertainty at micrometeorological scales: the impact of the eddy covariance energy imbalance and correction methods - N. Bambach; W. Kustas; J. Alfieri; J. Prueger; L. Hipps; L. McKee; S. J. Castro; J. Volk; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Under ideal conditions, evapotranspiration ( ET ) fluxes derived through the eddy covariance (EC) technique are considered a direct measure of actual ET . Eddy covariance flux measurements provide estimates at a temporal frequency that allows examining sub-daily, daily, and seasonal scale processes and relationships between different surface fluxes. The Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project has collected micrometeorological and biophysical data to ground-truth new remote sensing tools for fine-tuning vineyard irrigation management across numerous sites since 2013. This rich dataset allows us to quantify the impact of different approaches to estimate daily ET fluxes, while accounting for energy imbalance. This imbalance results from the lack of agreement between the total available energy and turbulent fluxes derived by the EC technique. We found that different approaches to deal with this energy imbalance can lead to uncertainty in daily ET estimates of up to 50%. Over the growing season, this uncertainty can lead to considerable biases in crop water use estimates, which in some cases were equivalent to ~ 1/3rd of the total growing season applied irrigation We analyzed ET uncertainty relative to atmospheric meteorological, stability, and advective conditions, and highlight the importance of recognizing limitations of micrometeorological observational techniques, considered state of the art, to quantify ET for model validation and field-scale monitoring. This study provides a framework to quantify daily ET estimates’ uncertainty and expected reliability when using the eddy covariance technique for ground-truthing or model validation purposes.

Morita–Baylis–Hillman adducts derived from thymol: synthesis, in silico studies and biological activity against Giardia lamblia - Francisco J. S. Xavier; Andressa B. Lira; Gabriel C. Verissimo; Fernanda S. de S. Saraiva; Abrahão A. de Oliveira Filho; Elaine M. de Souza-Fagundes; Margareth de F. F. M. Diniz; Maria A. Gomes; Aleff C. Castro; Fábio P. L. Silva; Claudio G. Lima-Junior; Mário L. A. A. Vasconcellos (Molecular Diversity, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Behavioral Response of the Leaf-Cutting Ant Atta cephalotes (Hymenoptera: Formicidae) to Trichoderma sp. - K. M. Cotazo-Calambas; Andrea Niño-Castro; S. M. Valencia-Giraldo; J. S. Gómez-Díaz; J. Montoya-Lerma (Journal of Insect Behavior, 2022)

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Hiding behind the rocks: rediscovery of Connarus beyrichii (Connaraceae), an endangered species endemic to montane outcrops of southeast Brazil - Cássio A. P. Toledo; Eve J. Lucas; Vinicius Castro Souza (Kew Bulletin, 2022)

Do telemetry harnesses affect giant anteater (Myrmecophaga tridactyla) behavior and welfare? - Alessandra Bertassoni; Daniela Caixeta-Oliveira; Juliana Macedo Magnino Silva; Victor Gonçalves de Castro; Guilherme Lopes do Amaral; Débora Regina Yogui; Danilo Kluyber; Arnaud L. J. Desbiez (European Journal of Wildlife Research, 2022)

Genetic diversity of Chlamydia pecorum detected in sheep flocks from Mexico - M. M. Limón-González; R. Hernández-Castro; F. Martínez-Hernández; J. Xicohtencatl-Cortes; H. Ramírez-Alvarez; E. G. Palomares-Resendiz; E. Díaz-Aparicio (Brazilian Journal of Microbiology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Voronoi-Based Discrete Element Analyses to Assess the Influence of the Grain Size and Its Uniformity on the Apparent Fracture Toughness of Notched Rock Specimens - J. Justo; H. Konietzky; J. Castro (Rock Mechanics and Rock Engineering, 2022)
The fracture toughness reflects the rock resistance to crack propagation, and therefore represents an important parameter for rock fracture assessments. From a strict point of view, the real fracture toughness ( $$\it {K}_{\mathrm{\it IC}}$$ K IC ) corresponds to a cracked situation in which the notch radius is theoretically equal to zero. However, most of the defects in rocks have a finite radius and, therefore, should be studied as notch-type defects. Here, the notch effect is numerically studied together with the influence of the grain size and the sorting coefficient (grain size uniformity) on the apparent fracture toughness ( $$\it {K}_{\mathrm{\it IN}}$$ K IN ). To this end, several four-point bending tests with different U-shaped notch radii, mean grain sizes and degrees of uniformity in grain size and shape have been simulated using the Discrete Element Method. In order to represent the grains of the rocks, the Voronoi tessellation is used to create randomly sized and distributed polygonal blocks. These Voronoi polygons have been defined, on the one hand, by an average edge length of 1, 2 and 3 mm, and, on the other hand, by a different number of iterations ( $$n$$ n ) in the relaxation process during the generation of the polygons, which defines the grain size uniformity. The numerical analyses performed and the interpretation of the results show a clear notch effect in all the studied cases, as the apparent fracture toughness ( $$\it {K}_{\mathrm{\it IN}}$$ K IN ) increases with notch radius. Finally, the obtained stress fields at the notch tip have been compared to those obtained from the traditional finite element method.

A large-scale comparison of reproduction and recruitment of the stalked barnacle Pollicipes pollicipes across Europe - Alba Aguión; Teresa Cruz; José Luis Acuña; Caroline Broudin; João J. Castro; Dominique Davoult; Jesus Dubert; Joana N. Fernandes; Katja J. Geiger; David Jacinto; David Mateus; Carlota Muñiz; et al. (Marine Biology, 2022)
Understanding large-scale spatial and temporal patterns of marine populations is a central goal in ecology, which has received renewed attention under climate change. However, few studies explore the large-scale dynamics of populations using standardized protocols and during the same time frames. We studied the phenology and intensity of reproduction and recruitment for the intertidal stalked barnacle Pollicipes pollicipes over an European scale and described their potential linkages with environmental variables. This species supports profitable fisheries in the Iberian Peninsula (Spain and Portugal). In Brittany (France), we had observed a significant lower reproductive effort (long non-breeding season, short breeding period in summer) and low values of recruitment intensity. This pattern may be related to the fact that Brittany corresponds to the northern limit of the distribution of this species in continental Europe. On the Iberian Peninsula, the most different region was Galicia (Spain), with Asturias (Spain) and SW Portugal being more similar. In Galicia, we have observed a contradictory pattern characterized by the absence of a non-breeding period and by a shorter recruitment season than observed in other Iberian regions. Our results suggest that air temperature, SST and chlorophyll-a might be related to the variability in reproduction and recruitment patterns of P. pollicipes . Moreover, spring and early summer upwelling in SW Portugal and Galicia might be inhibiting recruitment in this period. At the northern limit, the expected increase in performance under climate change might facilitate the recovery of populations after exploitation, increasing the resilience of the resource to fishing pressure.

Polyethylene microplastics and substrate availability can affect emergence responses of the freshwater insect Chironomus sancticaroli - Gleyson B. Castro; Aline C. Bernegossi; Mayara C. Felipe; Allan P. Ogura; Mara R. de Lima e Silva; Juliano J. Corbi (Ecotoxicology, 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Ambio fit for the 2020s - Erik Andersson; Wiebren J. Boonstra; Maricela de la Torre Castro; Alice C. Hughes; Ulrik Ilstedt; Arne Jernelöv; Bengt-Gunnar Jonsson; Zahra Kalantari; Carina Keskitalo; Emma Kritzberg; Thomas Kätterer; Jeffrey A. McNeely; et al. (Ambio, 2022)

Micropropagation of Catasetum integerrimum Hook (Orchidaceae) through seed germination and direct shoot regeneration from pseudobulbs and roots - Luis J. Castillo-Pérez; Angel Josabad Alonso-Castro; Javier Fortanelli-Martínez; Candy Carranza-Álvarez (In Vitro Cellular & Developmental Biology - Plant, 2022)

Sea Ice and Substratum Shape Extensive Kelp Forests in the Canadian Arctic - Karen Filbee-Dexter; Kathleen A. MacGregor; Camille Lavoie; Ignacio Garrido; Jesica Goldsmit; Laura Castro de la Guardia; Kimberly L. Howland; Ladd E. Johnson; Brenda Konar; Christopher W. McKindsey; Christopher J. Mundy; Robert W. Schlegel; et al. (Frontiers in Marine Science, 2022)
The coastal zone of the Canadian Arctic represents 10% of the world’s coastline and is one of the most rapidly changing marine regions on the planet. To predict the consequences of these environmental changes, a better understanding of how environmental gradients shape coastal habitat structure in this area is required. We quantified the abundance and diversity of canopy forming seaweeds throughout the nearshore zone (5–15 m) of the Eastern Canadian Arctic using diving surveys and benthic collections at 55 sites distributed over 3,000 km of coastline. Kelp forests were found throughout, covering on average 40.4% (±29.9 SD) of the seafloor across all sites and depths, despite thick sea ice and scarce hard substrata in some areas. Total standing macroalgal biomass ranged from 0 to 32 kg m –2 wet weight and averaged 3.7 kg m –2 (±0.6 SD) across all sites and depths. Kelps were less abundant at depths of 5 m compared to 10 or 15 m and distinct regional assemblages were related to sea ice cover, substratum type, and nutrient availability. The most common community configuration was a mixed assemblage of four species: Agarum clathratum (14.9% benthic cover ± 12.0 SD), Saccharina latissima (13% ± 14.7 SD), Alaria esculenta (5.4% ± 1.2 SD), and Laminaria solidungula (3.7% ± 4.9 SD). A. clathratum dominated northernmost regions and S. latissima and L. solidungula occurred at high abundance in regions with more open water days. In southeastern areas along the coast of northern Labrador, the coastal zone was mainly sea urchin barrens, with little vegetation. We found positive relationships between open water days (days without sea ice) and kelp biomass and seaweed diversity, suggesting kelp biomass could increase, and the species composition of kelp forests could shift, as sea ice diminishes in some areas of the Eastern Canadian Arctic. Our findings demonstrate the high potential productivity of this extensive coastal zone and highlight the need to better understand the ecology of this system and the services it provides.

Assessing Caffeine and Linear Alkylbenzene Sulfonate Effects on Molting and Reproduction of Daphnia magna by Quantitative and Qualitative Approaches - Mara R. de Lima e Silva; Aline C. Bernegossi; Gleyson B. Castro; Allan P. Ogura; Juliano J. Corbi; Mayara C. Felipe (Water, Air, & Soil Pollution, 2022)

Transcriptional regulation of cell growth and reprogramming of systemic response in wheat (Triticum turgidum subsp. durum) seedlings by Bacillus paralicheniformis TRQ65 - Luis A. Chaparro-Encinas; Fannie I. Parra-Cota; Abraham Cruz-Mendívil; Gustavo Santoyo; Juan J. Peña-Cabriales; Luciano Castro-Espinoza; Sergio de los Santos-Villalobos (Planta, 2022)

Impact of Dietary Condensed Tannins and Haemonchus contortus Infection in Growing Sheep: Effects on Nutrient Intake, Digestibility, and the Retention of Energy and Nitrogen - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; L. A. Sarmiento-Franco; J. Ventura-Cordero; P. G. González-Pech; J. J. Vargas-Magaña; J. F. J. Torres-Acosta (Acta Parasitologica, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Megabenthic communities distributed in the outer margins of the Yucatan shelf and their relationship to environmental variables - J Rubio-Polania; D Torruco-Gómez; A González-Solís; R Rodríguez-Canul; M Améndola-Pimenta; I Mariño-Tapia; J Herrera-Silveira; F Árcega-Cabrera; V Ceja-Moreno; J Romo-Alvarado; I Lizarraga-Castro; C Gutiérrez-Solís (Marine Biology Research, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

A new species of Hoplias malabaricus species complex ( Characiformes: Erythrinidae ) from the Crepori River , Amazon basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González‐Castro; Mendelsohn F. B. Souza; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Journal of Fish Biology, 2022)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral‐line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii‐iv, 7–8 anal‐fin rays, ii‐iv, 12–15 caudal‐fin rays, last vertical series of scales on the base of caudal‐fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species‐group by means of landmark‐based morphometrics and DNA Barcoding ( Cytochrome c Oxidase I gene ). An identification key to species of the H. malabaricus species complex is provided.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A framework for assessing coupling and de-coupling trajectories in river social-ecological systems - Cristina Quintas-Soriano; Jodi Brandt; Colden V. Baxter; Elena M. Bennett; Juan Miguel Requena-Mullor; Antonio J. Castro (Sustainability Science, 2022)
The degree of coupling between the social and ecological components of social-ecological systems is seen as fundamental to understanding their functioning, interactions and trajectories. Yet, there is limited work about how to empirically understand the degree of coupling between social and ecological systems, nor the processes by which the degree of coupling could change over time. Here, we introduce a conceptual framework for characterizing trajectories over time of coupling and de-coupling in social-ecological river systems. We analyze two conceptual scenarios describing coupling and de-coupling trajectories in a social-ecological system and define a series of key concepts for understanding social-ecological system trajectories. We tested these coupling and de-coupling trajectories theory by linking these concepts to empirical case examples of two river social-ecological systems in the western United States. Finally, we propose a quantitative approach with the potential for evaluating the level of social-ecological coupling and de-coupling trajectories in other SES contexts. This paper represents an advancing on the identification of specific actions that explain current SES trajectories and immediate actions to reinforce or shift the trajectory.

Development, nutrition, and rearing practices of relevant catfish species (Siluriformes) at early stages - Enric Gisbert; Ronald Kennedy Luz; Ignacio Fernández; Pravata K. Pradhan; Maria Salhi; Mansour T. Mozanzadeh; Aditya Kumar; Yannis Kotzamanis; Diana Castro‐Ruiz; Martin Bessonart; Maria J. Darias (Reviews in Aquaculture, 2022)
Catfish (Siluriformes) are important species for aquaculture worldwide, with an annual production in 2018 of ca . 6 million t. This review focuses on reassessing larval development, first feeding, and early rearing practices of the most important farmed catfish species, along with some candidate species for aquaculture diversification: Pangasianodon hypophthalmus (Pangasiidae), Clarias gariepinus (Clariidae), Ictalurus punctatus (Ictaluridae), Pseudoplatystoma spp. (Pimelodidae), Heteropneustes fossilis (Heteropneustidae), Rhamdia quelen (Heptapteridae), Ompok bimaculatus (Siluridae), and Lophiosilurus alexandri (Pseudopimelodidade). These species are initially reared indoors from one day to two weeks and are then transferred to fertilised outdoor ponds where they either feed on natural zooplankton or compound feeds. With the exception of C. gariepinus , I. punctatus , R. quelen and P. hypophthalmus , consistent and reliable fry production is a bottleneck that limits the expansion of farming of other species, such as Pseudoplatystoma spp., H. fossilis , O. bimaculatus , and L. alexandri . Rearing systems (extensive, semi‐extensive, intensive) and feeding protocols vary with species and geographical regions. Cannibalism and size heterogeneity are common, and these features create problems for larval and fry rearing of catfish species. Information about their nutritional requirements is required for the formulation of compound feeds that can guarantee high survival and good growth of catfish fries. However, such knowledge for most species is scarce, although some data are available for I. punctatus . Further genomic resources might allow fine‐tuning rearing success. This review describes some successes in this field, and also highlights gaps in knowledge to guide future research that can promote the development of catfish aquaculture.

Can Rubber Crop Systems Recover Termite Diversity in Previously Degraded Pastures in the Colombian Amazon Region? - Daniel Castro; Tiago F. Carrijo; Francisco J. Serna; Clara P. Peña-Venegas (Neotropical Entomology, 2021)

Green and Golden Obsidian of “Cerro de Las Navajas”, Hidalgo (Mexico): Geoarchaeological Heritage That Deserves International Recognition - Miguel A. Cruz-Pérez; Carles Canet; Alejandro Pastrana; Silvia Domínguez-Peláez; Lucero Morelos-Rodríguez; Luis Carcavilla; Erika Salgado-Martínez; Peter Krieger; Eduardo J. García-Alonso; Raymundo G. Martínez-Serrano; Sara I. Franco; Telma G. Castro-Romero; et al. (Geoheritage, 2021)

Effects of visual blur and contrast on spatial and temporal precision in manual interception - Anna Schroeger; J. Walter Tolentino-Castro; Markus Raab; Rouwen Cañal-Bruland (Experimental Brain Research, 2021)
The visual system is said to be especially sensitive towards spatial but lesser so towards temporal information. To test this, in two experiments, we systematically reduced the acuity and contrast of a visual stimulus and examined the impact on spatial and temporal precision (and accuracy) in a manual interception task. In Experiment 1, we blurred a virtual, to-be-intercepted moving circle (ball). Participants were asked to indicate (i.e., finger tap) on a touchscreen where and when the virtual ball crossed a ground line. As a measure of spatial and temporal accuracy and precision, we analyzed the constant and variable errors, respectively. With increasing blur, the spatial and temporal variable error, as well as the spatial constant error increased, while the temporal constant error decreased. Because in the first experiment, blur was potentially confounded with contrast, in Experiment 2, we re-ran the experiment with one difference: instead of blur, we included five levels of contrast matched to the blur levels. We found no systematic effects of contrast. Our findings confirm that blurring vision decreases spatial precision and accuracy and that the effects were not mediated by concomitant changes in contrast. However, blurring vision also affected temporal precision and accuracy, thereby questioning the generalizability of the theoretical predictions to the applied interception task.

Evaluation of Bacillus spp. isolates as potential biocontrol agents against charcoal rot caused by Macrophomina phaseolina on common bean - Yolani de J. Bojórquez-Armenta; Guadalupe A. Mora-Romero; Melina López-Meyer; Ignacio E. Maldonado-Mendoza; Claudia Castro-Martínez; Cecilia de los A. Romero-Urías; Jesús D. Cordero-Ramírez; Juan C. Martínez-Álvarez (Journal of General Plant Pathology, 2021)

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Activation of C–C motif chemokine receptor 2 modulates testicular macrophages number, steroidogenesis, and spermatogenesis progression - A. F. A. Figueiredo; N. T. Wnuk; C. P. Vieira; M. F. F. Gonçalves; M. R. G. Brener; A. B. Diniz; M. M. Antunes; H. M. Castro-Oliveira; G. B. Menezes; G. M. J. Costa (Cell and Tissue Research, 2021)

Multi-target drug with potential applications: violacein in the spotlight - Nelson Durán; Gerson Nakazato; Marcela Durán; Ignasio R. Berti; Guillermo R. Castro; Danijela Stanisic; Marcelo Brocchi; Wagner J. Fávaro; Carmen V. Ferreira-Halder; Giselle Z. Justo; Ljubica Tasic (World Journal of Microbiology and Biotechnology, 2021)

Amazonia as the Origin and Diversification Area of Didelphidae (Mammalia: Metatheria), and a Review of the Fossil Record of the Clade - Mariela C. Castro; Murilo J. Dahur; Gabriel S. Ferreira (Journal of Mammalian Evolution, 2021)
Didelphidae is the largest New World radiation of marsupials, and is mostly represented by arboreal, small- to medium-sized taxa that inhabit tropical and/or subtropical forests. The group originated and remained isolated in South America for millions of years, until the formation of the Isthmus of Panama. In this study, we present the first reconstruction of the biogeographic history of Didelphidae including all major clades, based on parametric models and stratified analyses over time. We also compiled all the pre-Quaternary fossil records of the group, and contrasted these data to our biogeographic inferences, as well as to major environmental events that occurred in the South American Cenozoic. Our results indicate the relevance of Amazonia in the early diversification of Didelphidae, including the divergence of the major clades traditionally ranked as subfamilies and tribes. Cladogeneses in other areas started in the late Miocene, an interval of intense shifts, especially in the northern portion of Andes and Amazon Basin. Occupation of other areas continued through the Pliocene, but few were only colonized in Quaternary times. The comparison between the biogeographic inference and the fossil records highlights some further steps towards better understanding the spatiotemporal evolution of the clade. Finally, our results stress that the early history of didelphids is obscured by the lack of Paleogene fossils, which are still to be unearthed from low-latitude deposits of South America.

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

Counting Enchytraeus crypticus Juveniles in Chronic Exposures: An Alternative Method for Ecotoxicity Studies Using Tropical Artificial Soil - Mayara C. Felipe; Aline C. Bernegossi; Fernanda R. Pinheiro; Gleyson B. Castro; Lidia Moura; Marcelo Zaiat; Juliano J. Corbi (Bulletin of Environmental Contamination and Toxicology, 2021)

Sudden cessation of fluoxetine before alcohol drinking reinstatement alters microglial morphology and TLR4/inflammatory neuroadaptation in the rat brain - Jesús Aranda; María del Mar Fernández-Arjona; Francisco Alén; Patricia Rivera; Leticia Rubio; Inés Smith-Fernández; Francisco Javier Pavón; Antonia Serrano; Pedro J. Serrano-Castro; Fernando Rodríguez de Fonseca; Juan Suárez (Brain Structure and Function, 2021)
Preclinical studies on the effects of abrupt cessation of selective serotonin reuptake inhibitors (SSRIs), a medication often prescribed in alcohol use disorder (AUD) patients with depression, results in alcohol consumption escalation after resuming drinking. However, a potential neuroinflammatory component on this escalation remains unexplored despite the immunomodulatory role of serotonin. Here, we utilized a rat model of 14-daily administration of the SSRI fluoxetine (10 mg/kg/day) along alcohol self-administration deprivation to study the effects of fluoxetine cessation on neuroinflammation after resuming alcohol drinking. Microglial morphology and inflammatory gene expression were analyzed in prelimbic cortex, striatum, basolateral amygdala and dorsal hippocampus. Results indicated that alcohol drinking reinstatement increased microglial IBA1 immunoreactivity and altered morphometric features of activated microglia (fractal dimension, lacunarity, density, roughness, and cell area, perimeter and circularity). Despite alcohol reinstatement, fluoxetine cessation modified microglial morphology in a brain region-specific manner, resulting in hyper-ramified (spatial complexity of branching), reactive (lower heterogeneity and circularity)-like microglia. We also found that microglial cell area correlated with changes in mRNA expression of chemokines ( Cx3cl1/fractalkine , Cxcl12 / SDF1α , Ccl2/MCP1 ), cytokines ( IL1β , IL6 , IL10 ) and the innate immune toll-like receptor 4 ( TLR4 ) in dorsal hippocampus. Specifically, TLR4 correlated with microglial spatial complexity assessed by fractal dimension in striatum, suggesting a role in process branching. These findings suggest that alcohol drinking reinstatement after fluoxetine treatment cessation disturbs microglial morphology and reactive phenotype associated with a TLR4/inflammatory response to alcohol in a brain region-specific manner, facts that might contribute to alcohol-induced damage through the promotion of escalation of alcohol drinking behavior.

Association of NFκβ, TNFα, IL-6, IL-1β, and LPL Polymorphisms with Type 2 Diabetes Mellitus and Biochemical Parameters in a Mexican Population - O. C. Martínez-Ramírez; D. A. Salazar-Piña; Ramos-García M. de Lorena; C. Castro-Hernández; L. Casas-Ávila; J. A. Portillo-Jacobo; J. Rubio (Biochemical Genetics, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Aerenchyma, gas diffusion, and catalase activity in Typha domingensis: a complementary model for radial oxygen loss - Vinícius P. Duarte; Marcio P. Pereira; Felipe F. Corrêa; Evaristo M. de Castro; Fabricio J. Pereira (Protoplasma, 2021)

Reactive Orange 16 dye degradation in anaerobic and aerobic MBBR coupled with ozonation: addressing pathways and performance - F. D. Castro; J. P. Bassin; T. L. M. Alves; G. L. Sant’Anna; M. Dezotti (International Journal of Environmental Science and Technology, 2021)

COVID-19 Impacts on Beaches and Coastal Water Pollution at Selected Sites in Ecuador, and Management Proposals Post-pandemic - Franklin I. Ormaza-Gonzaìlez; Divar Castro-Rodas; Peter J. Statham (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has obliged Governments all around the world to implement confinement and social distancing measures. Leisure and business activities on beaches and in ports have restricted direct and indirect contamination from, for example, plastics, hydrocarbon spillage, microbiological loads, and noise levels. This has led to temporarily improved environmental conditions, and the beaches having conditions closer to Marine Protected Areas. Here we report some impacts that have been studied using local surveys and qualitative observations in Ecuador at the popular beaches and ports of Salinas, Manta, and Galapagos. Satellite data support this information. Online surveys were carried out at critical moments of the pandemic: May (15th) and just after when measures were relaxed a little, but within lockdown in July (21st) 2020. Respondents were asked to compare conditions before and during the pandemic lockdown. Most (97–99%) suggested that beaches had significantly improved from visual observations during confinement. On a scale from 1 (worst) to 5 (best), the beaches of Salinas and Manta respectively were rated 2.2 and 2.8 (less than acceptable) before quarantine, and 4.5 and 4.3 after; results from the second survey (after 18 weeks of restrictions) were much the same. Replies from Galapagos showed a similar trend but with less marked differences. In addition to the beaches having less plastic and garbage, more fish, and large marine organisms, including humpback whales ( Megaptera novaeangliae ), dolphin (bottlenose, Tursiops truncatus) , and manta ray ( Manta sp.) were observed near to shore. At Galapagos beaches, turtles, sea lions, and sharks were observed many more times than pre COVID. Quantitative satellite data on Chlorophyl and attenuation coefficient (Kd, 490 nm) support the qualitative survey data that there is an improvement in coastal environment quality. Here we recommend that this unique opportunity resulting from the COVID-19 pandemic is used locally, regionally and globally to construct baseline data sets that include information on physical, chemical, biological, and microbiological factors in coastal zones. These parameters can then help establish an effective Coastal Zone Management Plan based on beach description and quality (water standards, noise pollution), as well as the human dimension (tourist load, cultural heritage, and economic value indices). This data and information gathering ideally should be done before the beaches become more heavily used again as the pandemic recedes.

Prey items of baleen whale species off the coast of Chile from fecal plume analysis - Susannah J. Buchan; Paulina Vásquez; Carlos Olavarría; Leonardo R. Castro (Marine Mammal Science, 2021)

Be quick or be dead: high temperatures reduce Aedes aegypti (Diptera: Culicidae) larval development time and pyriproxyfen larvicide efficiency in laboratory conditions - Lidia Moura; Barbara L. de Nadai; Aline C. Bernegossi; Mayara C. Felipe; Gleyson B. Castro; Juliano J. Corbi (International Journal of Tropical Insect Science, 2021)

FOXP2 expression and gray matter density in the male brains of patients with schizophrenia - Julio Sanjuán; Xochitl Helga Castro-Martínez; Gracián García-Martí; Javier González-Fernández; Roberto Sanz-Requena; Josep María Haro; J. Javier Meana; Luis Martí-Bonmatí; Juan Nacher; Noelia Sebastiá-Ortega; Javier Gilabert-Juan; María Dolores Moltó (Brain Imaging and Behavior, 2021)
Common genetic variants of FOXP2 may contribute to schizophrenia vulnerability, but controversial results have been reported for this proposal. Here we evaluated the potential impact of the common FOXP2 rs2396753 polymorphism in schizophrenia. It was previously reported to be part of a risk haplotype for this disease and to have significant effects on gray matter concentration in the patients. We undertook the first examination into whether rs2396753 affects the brain expression of FOXP2 and a replication study of earlier neuroimaging findings of the influence of this genetic variant on brain structure. FOXP2 expression levels were measured in postmortem prefrontal cortex samples of 84 male subjects (48 patients and 36 controls) from the CIBERSAM Brain and the Stanley Foundation Array Collections. High-resolution anatomical magnetic resonance imaging was performed on 79 male subjects (61 patients, 18 controls) using optimized voxel-based morphometry. We found differences in FOXP2 expression and brain morphometry depending on the rs2396753, relating low FOXP2 mRNA levels with reduction of gray matter density. We detected an interaction between rs2396753 and the clinical groups, showing that heterozygous patients for this polymorphism have gray matter density decrease and low FOXP2 expression comparing with the heterozygous controls. This study shows the importance of independent replication of neuroimaging genetic studies of FOXP2 as a candidate gene in schizophrenia. Furthermore, our results suggest that the FOXP2 rs2396753 affects mRNA levels, thus providing new knowledge about its significance as a potential susceptibility polymorphism in schizophrenia.

Effect of Anadenanthera colubrina protease inhibitors as an antiinflamatory mediator - Gracimério J Guarneire; Oswaldo Cardoso Junior; Nerilson Marques Lima; Emanuel Aguilar Santos; Caio Aguiar Schulze; Wellington Pereira Silva; João Pedro Oliveira Batista; Gabriela de Paula Carli; Sandra Br Castro; Caio Cesar S Alves; Alessandra P Carli (Natural Product Research, 2021)

Application of the Theory of Critical Distances for the Fracture Assessment of a Notched Limestone Subjected to Different Temperatures and Mixed Mode with Predominant Mode I Loading Conditions - J. Justo; J. Castro; S. Cicero (Rock Mechanics and Rock Engineering, 2021)

Biotechnological Potential of Eugenol and Thymol Derivatives Against Staphylococcus aureus from Bovine Mastitis - Daiana O. S. Nunes; Rafaelle Vinturelle; Francislene J. Martins; Thiago F. dos Santos; Alessandra Leda Valverde; Carlos Magno R. Ribeiro; Helena C. Castro; Evelize Folly (Current Microbiology, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Pathological characteristics, survival, and risk of breast cancer associated with estrogen and xenobiotic metabolism polymorphisms in Mexican women with breast cancer - O. C. Martínez-Ramírez; C. Castro-Hernández; R. Pérez-Morales; L. Casas-Ávila; Ramos-García M. de Lorena; A. Salazar-Piña; J. Rubio (Cancer Causes & Control, 2021)

Revisiting the paradigm of shark‐driven trophic cascades in coral reef ecosystems - Amelia A. Desbiens; George Roff; William D. Robbins; Brett M. Taylor; Carolina Castro‐Sanguino; Alexandra Dempsey; Peter J. Mumby (Ecology, 2021)
Global overfishing of higher‐level predators has caused cascading effects to lower trophic levels in many marine ecosystems. On coral reefs, which support highly diverse food webs, the degree to which top‐down trophic cascades can occur remains equivocal. Using extensive survey data from coral reefs across the relatively unfished northern Great Barrier Reef (nGBR), we quantified the role of reef sharks in structuring coral reef fish assemblages. Using a structural equation modeling (SEM) approach, we explored the interactions between shark abundance and teleost mesopredator and prey functional group density and biomass, while explicitly accounting for the potentially confounding influence of environmental variation across sites. Although a fourfold difference in reef shark density was observed across our survey sites, this had no impact on either the density or biomass of teleost mesopredators or prey, providing evidence for a lack of trophic cascading across nGBR systems. Instead, many functional groups, including sharks, responded positively to environmental drivers. We found reef sharks to be positively associated with habitat complexity. In turn, physical processes such as wave exposure and current velocity were both correlated well with multiple functional groups, reflecting how changes to energetic conditions and food availability, or modification of habitat affect fish distribution. The diversity of species within coral reef food webs and their associations with bottom‐up drivers likely buffers against trophic cascading across GBR functional guilds when reef shark assemblages are depleted, as has been demonstrated in other complex ecosystems.

Estimation of genetic parameters for four Peruvian guinea pig lines - J. I. Cedano-Castro; R. Jiménez; A. Huamán; B. Fuerst-Waltl; M. Wurzinger; G. Gutiérrez (Tropical Animal Health and Production, 2021)

Assessing Markovian Models for Seismic Hazard and Forecasting - Q. J. Gutierrez Peña; F. A. Nava Pichardo; E. Glowacka; R. R. Castro Escamilla; V. H. Márquez Ramírez (Pure and Applied Geophysics, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Molecular sexing of Xenarthra: a tool for genetic and ecological studies - Carmen Elena Barragán-Ruiz; Eliana Paviotti-Fischer; Karen Giselle Rodríguez-Castro; Arnaud L. J. Desbiez; Pedro Manoel Galetti (Conservation Genetics Resources, 2021)

Bacterial Nanocellulose Mulch as a Potential Greener Alternative for Urban Gardening in the Small-Scale Food Production of Onion Plants - L. Cárcamo; S. Sierra; M. Osorio; J. Velásquez-Cock; L. Vélez-Acosta; C. Gómez-Hoyos; C. Castro; R. Zuluaga; P. Gañán (Agricultural Research, 2021)

d-Lactate and intestinal fatty acid-binding protein are elevated in serum in patients with acute ischemic stroke - Carlos R. Camara-Lemarroy; Nicolás Escobedo-Zúñiga; Francisco J. Guzmán-de la Garza; Jorge Castro-Garza; Javier Vargas-Villarreal; Fernando Góngora-Rivera (Acta Neurologica Belgica, 2021)

Hepatitis C treatment outcome in former or current intravenous drug users coinfected with HIV, with or without directly observed therapy - R. Sarmento-Castro; J. Méndez; A. Horta; C. Gonçalves; O. Vasconcelos; J. Seabra; M. Abreu; M. J. Gonçalves; M. J. Santos; A. P. Tavares (Infectious Diseases, 2021)

An interdisciplinary assessment of private conservation areas in the Western United States - Cristina Quintas-Soriano; Dainee M. Gibson; Jodi S. Brandt; María D. López-Rodríguez; Javier Cabello; Pedro A. Aguilera; Antonio J. Castro (Ambio, 2021)
Conservation easements are the fastest growing private conservation strategy in the United States. However, mechanisms to assess private land conservation as well as their support by the general public are not well understood. This study uses the ecosystem services framework for assessing existing private lands in Idaho and identifies areas for future conservation easements. Using conservation targets of the land trust as a guide for selecting ecosystem services, we (a) mapped the spatial delivery of conservation targets across public and private lands, (b) explored public awareness in terms of social importance and vulnerability, and (c) mapped future priority areas by characterizing conservation bundles. We found that public lands provided the highest levels of conservation targets, and we found no difference in conservation target provision between private areas and conservation easements. The spatial characterization of conservation target bundles identified potential future priority areas for conservation easements, which can guide planning of land trust conservation efforts.

Proximal sensors for monitoring seasonal changes of feeding sites selected by grazing ewes - João Serrano; E. Sales-Baptista; Shakib Shahidian; J. Marques da Silva; I. Ferraz de Oliveira; J. Lopes de Castro; Alfredo Pereira; M. Cancela d’Abreu; Mário de Carvalho (Agroforestry Systems, 2021)

Molecular docking and pharmacophoric modelling of 1,5-disubstituted tetrazoles as inhibitors of two proteins present in cancer, the ABL and the mutated T315I kinase - Erik Díaz-Cervantes; Carlos J. Cortés-García; Luis Chacón-García; Abel Suárez-Castro (In Silico Pharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Constraining Euler Deconvolution Solutions Through Combined Tilt Derivative Filters - Fabrício R. Castro; Saulo P. Oliveira; Jeferson de Souza; Francisco J. F. Ferreira (Pure and Applied Geophysics, 2020)

Escitalopram as a modulator of proopiomelanocortin, kisspeptin, Kiss1R and MCHR1 gene expressions in the male rat brain - Artur Pałasz; Aneta Piwowarczyk-Nowak; Aleksandra Suszka-Świtek; Katarzyna Bogus; Łukasz Filipczyk; Alessandra Della Vecchia; Kinga Mordecka-Chamera; Itiana Castro Menezes; John J. Worthington; Marek Krzystanek; Ryszard Wiaderkiewicz (Molecular Biology Reports, 2020)
Neuropeptides are important, multifunctional regulatory factors of the nervous system, being considered as a novel, atypical sites of antidepressants action. It has already been proven that some of them, such as selective serotonin reuptake inhibitors (SSRI), are able to affect peptidergic pathways in various brain regions. Despite these reports, there is so far no reports regarding the effect of treatment with SSRIs on brain proopiomelanocortin (POMC), kisspeptin, Kiss1R and MCHR1 gene expression. In the current study we examined POMC, kisspeptin, Kiss1R and MCHR1 mRNA expression in the selected brain structures (hypothalamus, hippocampus, amygdala, striatum, cerebellum and brainstem) of rats chronically treated with a 10 mg/kg dose of escitalopram using quantitative Real-Time PCR. Long-term treatment with escitalopram led to the upregulation of MCHR1 expression in the rat amygdala. Kisspeptin mRNA level was also increased in the amygdala, but Kiss1R mRNA expressions were elevated in the hippocampus, hypothalamus and cerebellum. POMC mRNA expressions were in turn decreased in the hippocampus, amygdala, cerebellum and brainstem. These results may support the hypothesis that these neuropeptides may be involved in the site-dependent actions of SSRI antidepressants. This is the first report of the effects of escitalopram on POMC, kisspeptin, Kiss1R and MCHR1 in animal brain. Our findings shed a new light on the pharmacology of SSRIs and may contribute to a better understanding of the alternative, neuropeptide-dependent modes of antidepressant action.

Update on the use of Pristina longiseta Ehrenberg, 1828 (Oligochaeta: Naididae) as a toxicity test organism - Gleyson B. Castro; Fernanda R. Pinheiro; Mayara C. Felipe; Aline C. Bernegossi; Douglas Girolli; Guilherme R. Gorni; Juliano J. Corbi (Environmental Science and Pollution Research, 2020)

Effects of Polyethylene Microplastics on Freshwater Oligochaeta Allonais inaequalis (Stephenson, 1911) Under Conventional and Stressful Exposures - Gleyson B. Castro; Aline C. Bernegossi; Fernanda R. Pinheiro; Mayara C. Felipe; Juliano J. Corbi (Water, Air, & Soil Pollution, 2020)

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Rodrigo Zacca; Vânia Neves; Tiago da Silva Oliveira; Susana Soares; Luís Manuel Pinto Lopes Rama; Flávio Antônio de Souza Castro; João Paulo Vilas-Boas; David B. Pyne; Ricardo J. Fernandes (European Journal of Applied Physiology, 2020)

Correction to: Canopy dynamics in a tropical Atlantic forest mosaic in southeastern Brazil - Flávia P. Nunes; Silvana A. B. Castro; J. P. Lemos-Filho; Queila S. Garcia (Brazilian Journal of Botany, 2020)

Canopy dynamics in a tropical Atlantic forest mosaic in southeastern Brazil - Flávia P. Nunes; Silvana A. B. Castro; J. P. Lemos-Filho; Queila S. Garcia (Brazilian Journal of Botany, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Multi-Year Density Variation of Queen Conch (Aliger gigas) on Serrana Bank, Seaflower Biosphere Reserve, Colombia: Implications for Fisheries Management - Néstor E. Ardila; Hernando Hernández; Astrid Muñoz-Ortiz; Óscar J. Ramos; Erick Castro; Nacor Bolaños; Anthony Rojas; Juan A. Sánchez (Frontiers in Marine Science, 2020)

Aerobic processes for bioleaching manganese and silver using microorganisms indigenous to mine tailings - B. Huerta-Rosas; I. Cano-Rodríguez; Z. Gamiño-Arroyo; F. I. Gómez-Castro; F. R. Carrillo-Pedroza; P. Romo-Rodríguez; J. F. Gutiérrez-Corona (World Journal of Microbiology and Biotechnology, 2020)

Nutritional evaluation and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon - Marianela Cobos; Sheyla Pérez; Janeth Braga; Gabriel Vargas-Arana; Leenin Flores; Jae D. Paredes; J. Dylan Maddox; Jorge L. Marapara; Juan C. Castro (World Journal of Microbiology and Biotechnology, 2020)

Hit and sunk: provenance and alterations of ceramics from seventeenth century Angra D shipwreck - J. G. Iñañez; J. Bettencourt; I. Pinto Coelho; A. Teixeira; G. Arana; K. Castro; U. Sanchez-Garmendia (Archaeological and Anthropological Sciences, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

The use of an Allonais inaequalis reproduction test as an ecotoxicological bioassay - M. C. Felipe; A. C. Bernegossi; G. B. Castro; F. R. Pinheiro; B. L. Nadai; B. N. Cardoso-Silva; J. J. Corbi (Ecotoxicology, 2020)

A Global Review of Ligustrum Lucidum (OLEACEAE) Invasion - Romina D. Fernandez; Sergio J. Ceballos; Roxana Aragón; Agustina Malizia; Lía Montti; Juan I. Whitworth-Hulse; Pilar Castro-Díez; H. Ricardo Grau (The Botanical Review, 2020)

Persistence of Lymphocystis Disease Virus (LCDV) in Seawater - Rocío Leiva-Rebollo; Alejandro M. Labella; Estefanía J. Valverde; Dolores Castro; Juan J. Borrego (Food and Environmental Virology, 2020)

Polymorphism in Conservative Structures? The Scapulocoracoids in Skates Genus Psammobatis (Chondrichthyes, Arhynchobatidae) and the Validity of P. parvacauda - E. Mabragaña; M. González-Castro; V. Gabbanelli; D. M. Vazquez; J. M. Díaz de Astarloa (Frontiers in Marine Science, 2020)

Role of VEGFs in metabolic disorders - M. di Somma; M. Vliora; E. Grillo; B. Castro; E. Dakou; W. Schaafsma; J. Vanparijs; M. Corsini; C. Ravelli; E. Sakellariou; S. Mitola (Angiogenesis, 2020)

Sun Protection Habits and Sunburn in Elite Aquatics Athletes: Surfers, Windsurfers and Olympic Sailors - Guillermo De Castro-Maqueda; J. V. Gutierrez-Manzanedo; J. G. Ponce-González; J. R. Fernandez-Santos; M. Linares-Barrios; M. De Troya-Martín (Journal of Cancer Education, 2020)

A comparison of machine and deep-learning algorithms applied to multisource data for a subtropical forest area classification - C. Sothe; C. M. De Almeida; M. B. Schimalski; V. Liesenberg; L. E. C. La Rosa; J. D. B. Castro; R. Q. Feitosa (International Journal of Remote Sensing, 2020)

Electrocutions in free-living black-tufted marmosets (Callithrix penicillata) in anthropogenic environments in the Federal District and surrounding areas, Brazil - Alexandra A. B. G. Pereira; Bianca Dias; Sarah I. Castro; Marina F. A. Landi; Cristiano B. Melo; Tais M. Wilson; Gabriela R. T. Costa; Pedro H. O. Passos; Alessandro P. Romano; Matias P. J. Szabó; Márcio B. Castro (Primates, 2020)

Chloroplast and nuclear ribosomal cistron phylogenomics in a group of closely related sections in Salvia subg. Calosphace - Edgar I. Olvera-Mendoza; Grant T. Godden; Juan Carlos Montero-Castro; J. Mark Porter; Sabina I. Lara-Cabrera (Brazilian Journal of Botany, 2020)

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Climate change favors rice production at higher elevations in Colombia - F. Castro-Llanos; G. Hyman; J. Rubiano; J. Ramirez-Villegas; H. Achicanoy (Mitigation and Adaptation Strategies for Global Change, 2019)

Analysis of single nucleotide polymorphisms (SNPs) associated with antibiotic resistance genes in Chilean Piscirickettsia salmonis strains - Jaime Figueroa; Diana Castro; Fernando Lagos; Carlos Cartes; Adolfo Isla; Alejandro J. Yáñez; Rubén Avendaño‐Herrera; Denise Haussmann (Journal of Fish Diseases, 2019)
The aetiological agent of Piscirickettsiosis is Piscirickettsia salmonis, a Gram‐negative intracellular pathogen, and high doses of antibiotics have regularly been employed to treat this infection. Seven florfenicol and/or oxytetracycline resistance genes ( tet pump , tetE , Tclor/flor , Tbcr , TfloR , ompF and mdtN ) were identified in strains by in silico genome analyses. Later, the number of single nucleotide polymorphisms (SNPs) and its relationship with the resistance to these antibiotics were identified and analysed, using the original LF‐89 strain as reference. Trials to determine and compare the minimum inhibitory concentration (MIC) of oxytetracycline and florfenicol in each strain, as well as to quantify the gPCR transcripts levels in the selected genes, were performed. Therefore, variations in the resistance to both antibiotics were observed, where the strain with fewer SNPs showed the highest susceptibility. Consistently, the in silico 3D analyses of proteins encoded by the selected genes revealed structural changes, evident in the sequences with the highest number of SNPs. These results showed that the bacterial resistance to oxytetracycline was mainly linked to the presence of SNPs in relevant sites, antibiotic resistance genes and an OmpF porin, leading to important changes in the protein structure.

Criollo goats limit their grass intake in the early morning suggesting a prophylactic self-medication behaviour in a heterogeneous vegetation - R. A. Torres-Fajardo; P. G. González-Pech; C. A. Sandoval-Castro; J. Ventura-Cordero; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

Consumer attitudes toward food crops developed by CRISPR/Cas9 in Costa Rica - Andrés Gatica-Arias; Marta Valdez-Melara; Griselda Arrieta-Espinoza; Federico J. Albertazzi-Castro; Johnny Madrigal-Pana (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Multi-model inference as criterion to determine differences in growth patterns of distinct Crassostrea gigas stocks - F. J. Reynaga-Franco; E. A. Aragón-Noriega; J. M. Grijalva-Chon; R. Castro-Longoria; J. A. Arreola-Lizárraga; R. H. Barraza-Guardado; J. Chávez-Villalba (Aquaculture International, 2019)

Eurypsychrophilic Pseudomonas spp. isolated from Venezuelan tropical glaciers as promoters of wheat growth and biocontrol agents of plant pathogens at low temperatures - Johnma J. Rondón; María M. Ball; Luz Thais Castro; Luis Andrés Yarzábal (Environmental Sustainability, 2019)

Using Large-Eddy Simulation and Wind-Tunnel Data to Investigate Peak-to-Mean Concentration Ratios in an Urban Environment - J. M. Santos; N. C. Reis; I. P. Castro; E. V. Goulart; Z. T. Xie (Boundary-Layer Meteorology, 2019)

Biostimulation of crude oil-polluted soils: influence of initial physicochemical and biological characteristics of soil - C. Calvo; A. Rodríguez-Calvo; T. Robledo-Mahón; M. Manzanera; J. González-López; E. Aranda; G. A. Silva-Castro (International Journal of Environmental Science and Technology, 2019)

Gymnopodium floribundum fodder as a model for the in vivo evaluation of nutraceutical value against Haemonchus contortus - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; J. Ventura-Cordero; L. A. Sarmiento-Franco; R. H. Santos-Ricalde; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Echeveria sonianevadensis (Crassulaceae), una nueva especie del Volcán Nevado de Colima del occidente de México y una clave para la serie Gibbiflorae - H. David Jimeno-Sevilla; J. Antonio Vázquez-García; Miguel Ángel Muñiz-Castro; Ignacio García-Ruiz; Gerardo Hernández-Vera; y José Villa Castillo (Brittonia, 2019)

Effects of alternative silvicultural systems on litter decomposition and nutrients dynamics in sub-Antarctic forests - N. Oro Castro; A. Moretto; L. J. Selzer; J. Escobar (Agroforestry Systems, 2019)

Historical photographs of captures of recreational fishers indicate overexploitation of nearshore resources at an oceanic island - David Jiménez‐Alvarado; Airam Sarmiento‐Lezcano; Airam Guerra‐Marrero; Fernando Tuya; Ángelo Santana Del Pino; Michael J. Sealey; José J. Castro (Journal of Fish Biology, 2019)
In this study, we used a historical collection of photographs taken by recreational fishers from 1940 to 2014, at the island of Gran Canaria, to show both a significant decrease in the mean total length of Epinephelus marginatus and a concurrent change in the composition of captures. Before 1980, the mean total length of fish caught and photographed was c . 100 cm, while after 2009 this was typically E. marginatus (an apex predator), but currently the majority of catches are of omnivorous species, in particular the parrotfish, Sparisoma cretense and seabreams Diplodus spp. Overall, integration of these results indicates a qualitative and quantitative variation in captures of recreational fishers, probably as a sign of change in ecological balances and the overfished status of many target species.

Temporal and spatial predictions of effect of alternative fishing policies for the Gran Canaria marine ecosystem - Lorena Couce Montero; Villy Christensen; Alberto Bilbao Sieyro; Yeray Pérez González; David Jiménez‐Alvarado; José J. Castro (Journal of Fish Biology, 2019)
In this paper we consider what may happen to the marine ecosystem of Gran Canaria Island within the 2030 horizon, if fishing strategies different from those currently in place were implemented and we evaluate the effect of, for example, reduction of recreational–artisanal fishing, limitation of catches ( e.g . total allowable catches, TAC), or spatial distribution of fishing sectors. From all scenarios tested, only those that significantly reduce the high effort of the recreational fishing would allow the recovery of the most exploited stocks in the marine ecosystem in the short and medium‐term. Moreover, the best management strategy, in contribution to abundance, was obtained with a scenario that has a spatial partition of exploitation rights between artisanal and recreational fishermen and includes no‐fishing zones (NTZ). This work is a first attempt to use spatial and temporal models to assess the effectiveness of alternative fishery policies in the Canary Islands.

Speciation and periodic restricted environments. The case of genus Ononis L. (subsections Natrix and Viscosae ) - I. Castro; J. Rocha; C. Costa; G. Costa; R. Ramírez-Rodríguez; F. Amich; V. Carnide; A. L. Crespí (Plant Biosystems, 2019)

System Failure: Work Organization and Injury Outcomes among Latino Forest Workers - Carl Wilmsen; A. Butch de Castro; Diane Bush; Marcy J. Harrington (Journal of Agromedicine, 2019)

Two New Species of the Spittlebug Genus Ocoaxo Fennah (Hemiptera: Cercopidae) from Mexico, and Keys for the Groups, Group Three, and First Subgroup - U Castro-Valderrama; G S Carvalho; D C Peck; J M Valdez-Carrasco; J Romero Nápoles (Neotropical Entomology, 2019)

Total synthesis of the linear and angular 3-methylated regioisomers of the marine natural product Kealiiquinone and biological evaluation of related Leucetta sp. alkaloids on human breast cancer - César R. Solorio-Alvarado; Velayudham Ramadoss; Rocío Gámez-Montaño; Juan R. Zapata-Morales; Angel J. Alonso-Castro (Medicinal Chemistry Research, 2019)

Production of benzyl carbonyl (rose aroma) from whey and its effect on pollutant load removal - L. Conde Báez; J. Castro Rosas; J. R. Villagómez Ibarra; I. Palma Quiroz; J. B. Páez Lerma; C. A. Gómez Aldapa (Environment, Development and Sustainability, 2019)

Draft genome sequence of Lactobacillus plantarum C4 (CECT 9567), a potential probiotic strain isolated from kefir - Soumi De Montijo-Prieto; David J. Castro; Jose C. Reina; Maria Jimenez-Valera; Alfonso Ruiz-Bravo (Archives of Microbiology, 2019)

Sea surface temperature‐related response of precipitation in northern South America according to a WRF multi‐decadal simulation - J. Alejandro Martinez; Paola A. Arias; Chris Castro; Hsin‐I Chang; Carlos A. Ochoa‐Moya (International Journal of Climatology, 2019)
Precipitation, low‐level flow and atmospheric moisture transport fields over the Intra‐Americas region from a Weather Research and Forecasting model (WRF) multi‐decadal simulation are presented. The period of analysis is 1982–2012, and the focus is on mean monthly states and their variability. WRF results are compared to global precipitation products and to the Interim Reanalysis from the ECWMF (ERA‐Interim). An analysis of the coupling between precipitation over northern South America and regional scale sea surface temperatures (SSTs) and winds within ERA‐Interim and WRF is also presented. Over land, precipitation biases in WRF are mostly positive, especially over Central America and northern South America. This bias is associated with an excess in atmospheric moisture convergence in WRF compared to ERA‐Interim, which in turn is related to stronger low‐level circulation structures and differences in the moisture transport field between WRF and ERA‐Interim at the regional scale. The largest differences in the flow are observed over the eastern Pacific, where the flow is correlated with precipitation over southern Mexico, Central America and northern South America during the boreal summer. During early winter, correlation patterns of WRF precipitation and SST anomalies over the tropical Pacific are substantially weaker over western Texas and northwestern South America compared to the coupling between the global precipitation products and observed SSTs. For northwestern South America, the low correlation seems to be associated to a lack of coupling between regional scale winds and SST anomalies. During the boreal summer, the coupling between Caribbean SSTs and precipitation over parts of Mexico and Central America is stronger in WRF compared to observation‐based products.

Assessing Risks from Harbor Dredging to the Northernmost Population of Diamondback Terrapins Using Acoustic Telemetry - T. Castro-Santos; M. Bolus; A. J. Danylchuk (Estuaries and Coasts, 2019)

Analysis of a complex slope failure in a granodiorite quarry bench - Leandro R. Alejano; María Veiga; Ignacio Pérez-Rey; Uxía Castro-Filgueira; Javier Arzúa; Álvaro J. Castro-Caicedo (Bulletin of Engineering Geology and the Environment, 2019)

Spatial distribution patterns, abundance and reproductive effort of the starfish Echinaster (Othilia) paucispinus along an environmental gradient in a Caribbean mangrove ecosystem - Wilber J. Bernay-Alfonzo; Raymundo Hurtado-Carreño; Edlin J. Guerra-Castro (Marine Biodiversity, 2019)

Climate change resilience of a globally important sea turtle nesting population - Ana R. Patrício; Miguel R. Varela; Castro Barbosa; Annette C. Broderick; Paulo Catry; Lucy A. Hawkes; Aissa Regalla; Brendan J. Godley (Global Change Biology, 2019)
Few studies have looked into climate change resilience of populations of wild animals. We use a model higher vertebrate, the green sea turtle, as its life history is fundamentally affected by climatic conditions, including temperature‐dependent sex determination and obligate use of beaches subject to sea level rise ( SLR ). We use empirical data from a globally important population in West Africa to assess resistance to climate change within a quantitative framework. We project 200 years of primary sex ratios (1900–2100) and create a digital elevation model of the nesting beach to estimate impacts of projected SLR . Primary sex ratio is currently almost balanced, with 52% of hatchlings produced being female. Under IPCC models, we predict: (a) an increase in the proportion of females by 2100 to 76%–93%, but cooler temperatures, both at the end of the nesting season and in shaded areas, will guarantee male hatchling production; (b) IPCC SLR scenarios will lead to 33.4%–43.0% loss of the current nesting area; (c) climate change will contribute to population growth through population feminization, with 32%–64% more nesting females expected by 2120; (d) as incubation temperatures approach lethal levels, however, the population will cease growing and start to decline. Taken together with other factors (degree of foraging plasticity, rookery size and trajectory, and prevailing threats), this nesting population should resist climate change until 2100, and the availability of spatial and temporal microrefugia indicates potential for resilience to predicted impacts, through the evolution of nest site selection or changes in nesting phenology. This represents the most comprehensive assessment to date of climate change resilience of a marine reptile using the most up‐to‐date IPCC models, appraising the impacts of temperature and SLR , integrated with additional ecological and demographic parameters. We suggest this as a framework for other populations, species and taxa.

The endemic orchids of Mexico: a review - Luis J. Castillo-Pérez; Domingo Martínez-Soto; Juan J. Maldonado-Miranda; Angel J. Alonso-Castro; Candy Carranza-Álvarez (Biologia, 2019)

Hydrographic and Biological Impacts of a Glacial Lake Outburst Flood (GLOF) in a Patagonian Fjord - Erika Meerhoff; Leonardo R. Castro; Fabián J. Tapia; Iván Pérez-Santos (Estuaries and Coasts, 2019)

CHEMICAL CHARACTERIZATION OF A NEW ACIDIFIED REGION TO STUDY OCEAN ACIDIFICATION IN SUBTROPICAL ECOSYSTEMS - Sara González-Delgado; J. Magdalena Casiano; MELCHOR GONZALEZ-DAVILA; David González-Santana; Celso Hernández; Enrique Lozano-Bilbao; Adrian Castro; Carlos Sangil; José Carlos Hernández (Frontiers in Marine Science, 2019)

The PERCEBES project: science for the spatial management of the stalked barnacle fishery in the Atlantic Arc - Katja Geiger; José Luis Acuña; Alba Aguión; Arrontes Julio; Marion Ballenghiem; Yaisel J. Borrell; Caroline Broudin; João Castro; Juliette Chiss; Teresa Cruz; Dominique Davoult; Jesus Dubert; et al. (Frontiers in Marine Science, 2019)

Simulating trophic impacts of recreational fishing scenarios on two oceanic islands using Ecopath with Ecosim - Lorena Couce; Villy Christensen; Alberto Bilbao-Sieyro; Yeray Perez; Jose J. Castro (Frontiers in Marine Science, 2019)

Standardization of catch-per-unit-effort in a multi-gear multi-species fishery - Lorena Couce; Angelo Santana; Alberto Bilbao-Sieyro; Yeray Perez; Jose J. Castro (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

STMS (sequence tagged microsatellite site) molecular markers as a valuable tool to confirm controlled crosses in chickpea (Cicer arietinum L.) breeding programs - C. Caballo; P. Castro; J. Gil; I. Izquierdo; T. Millan; J. Rubio (Euphytica, 2018)

Using floristics, modern systematics and phylogenetics for disentangling biodiversity hotspots across scales: a Mediterranean case study - V. I. Simón-Porcar; M. Escudero; L. Navarro; A. de Castro; J. Lorite; R. Molina-Venegas; J. Arroyo (Plant Biosystems, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Ontogenetic allometry conservatism across five teleost orders - Kathleen M. da Silva Alcântara Castro; Maiara P. do Santos; Marcelo F. G. Brito; Claudio J. Bidau; Pablo A. Martinez (Journal of Fish Biology, 2018)
Geometric morphometrics were used to analyse ontogenetic trajectories in representatives of the Characiformes, Cichliformes, Cyprinodontiformes, Siluriformes, and Tetraodontiformes. It was not possible to differentiate any allometric growth patterns across groups, indicating that a phylogenetically conserved developmental pattern is widespread throughout Teleostei.

Characterizing the growth of Sarcoptes scabiei infrapopulations - Inmaculada Castro; José Espinosa; José E. Granados; Francisco J. Cano-Manuel; Paulino Fandos; Arián Ráez-Bravo; Jorge R. López-Olvera; Ramón C. Soriguer; Jesús M. Pérez (Experimental and Applied Acarology, 2018)

Use of chemometric analyses to assess biological wastewater treatment plants by protozoa and metazoa monitoring - A. Luís Amaral; Cristiano S. Leal; A. Isabel Vaz; J. Carvalho Vieira; Andreia C. Quinteiro; M. Lourdes Costa; L. Miguel Castro (Environmental Monitoring and Assessment, 2018)

Transformation towards sustainable bioenergy systems - Gerardo J. Ruiz-Mercado; Juan Gabriel Segovia-Hernández; Agustín J. Castro-Montoya (Clean Technologies and Environmental Policy, 2018)

Tree influence on soil and pasture: contribution of proximal sensing to pasture productivity and quality estimation in montado ecosystems - João Serrano; Shakib Shahidian; J. Marques Da Silva; E. Sales-Baptista; I. Ferraz De Oliveira; J. Lopes De Castro; Alfredo Pereira; M. Cancela De Abreu; Eliana Machado; Mário de Carvalho (International Journal of Remote Sensing, 2018)

Comparison of Health Communication Channels for Reaching Hispanics About Biobanking: a Pilot Trial - Jessica McIntyre; Julio Jiménez; Yonaira M. Rivera; Steven K. Sutton; Gloria Asencio; Eida M. Castro-Figueroa; Clement K. Gwede; Thomas H. Brandon; Susan T. Vadaparampil; Vani N. Simmons; Johanna Corchado; Laura Moreno; et al. (Journal of Cancer Education, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Notes on the Occurrence of Oligonychus milleri (McGregor) and Oligonychus ununguis (Jacobi) (Acari: Tetranychidae) in Brazil - E B Castro; O C Zanardi; J Garlet; R Ochoa; R J F Feres (Neotropical Entomology, 2018)

Morphological development in the first life phase of Adriatic sturgeon Acipenser naccarii under controlled conditions - R. Cabrera‐Castro; C. Zabala; M. C. Soriguer; A. Domezain; J. A. Hernando (Journal of Fish Biology, 2018)
Early development of the Adriatic sturgeon Acipenser naccarii from its free embryo after hatching (stage 36), until late embryo stage, when the transition to exogenous feeding starts (stage 45) is described. Special emphasis is given to morphological development and description of the different structures that are formed at each life stage. After hatching, free embryos still present embryonic characteristics, little pigmentation and an ovoid yolk sac. The mouth begins to open on the second day post hatch (dph) and is fully open at 3 dph. The head begins to separate from the body at 4 dph and straightens at 6 dph. The first fins to appear are the pectoral fins on the yolk sac and an embryological fin fold that extends from behind the head to the posterior part of the yolk sac. All other fins will develop from this fold. At 7 dph the caudal fin begins to take a heterocercal form and dorsal scutes are observed. This study provides information that will assist aquaculturists by establishing a reference for the normal development of A. naccarii , which may be useful for evaluating the suitability and quality of fish produced for restocking.

Breeding implications of drought stress under future climate for upland rice in Brazil - Julian Ramirez‐Villegas; Alexandre B. Heinemann; Adriano Pereira de Castro; Flávio Breseghello; Carlos Navarro‐Racines; Tao Li; Maria C. Rebolledo; Andrew J. Challinor (Global Change Biology, 2018)
Rice is the most important food crop in the developing world. For rice production systems to address the challenges of increasing demand and climate change, potential and on‐farm yield increases must be increased. Breeding is one of the main strategies toward such aim. Here, we hypothesize that climatic and atmospheric changes for the upland rice growing period in central Brazil are likely to alter environment groupings and drought stress patterns by 2050, leading to changing breeding targets during the 21st century. As a result of changes in drought stress frequency and intensity, we found reductions in productivity in the range of 200–600 kg/ha (up to 20%) and reductions in yield stability throughout virtually the entire upland rice growing area (except for the southeast). In the face of these changes, our crop simulation analysis suggests that the current strategy of the breeding program, which aims at achieving wide adaptation, should be adjusted. Based on the results for current and future climates, a weighted selection strategy for the three environmental groups that characterize the region is suggested. For the highly favorable environment ( HFE , 36%–41% growing area, depending on RCP ), selection should be done under both stress‐free and terminal stress conditions; for the favorable environment ( FE , 27%–40%), selection should aim at testing under reproductive and terminal stress, and for the least favorable environment ( LFE , 23%–27%), selection should be conducted for response to reproductive stress only and for the joint occurrence of reproductive and terminal stress. Even though there are differences in timing, it is noteworthy that stress levels are similar across environments, with 40%–60% of crop water demand unsatisfied. Efficient crop improvement targeted toward adaptive traits for drought tolerance will enhance upland rice crop system resilience under climate change.

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

Usefulness of a single-assay chemiluminescence test (Tularaemia VIRCLIA IgG + IgM monotest) for the diagnosis of human tularemia. Comparison of five serological tests - África Cubero; Carlos Durántez; Ana Almaraz; Luis Fernández-Lago; María P. Gutiérrez; María J. Castro; Miguel A. Bratos; María Simarro; Gabriel A. March; Antonio Orduña (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Genotoxicity of spent pot liner as determined with the zebrafish (Danio rerio) experimental model - Tássia F. D. Castro; Isadora M. Paiva; Aline F. S. Carvalho; Isadora L. Assis; Marcel J. Palmieri; Larissa F. Andrade-Vieira; Silvana Marcussi; Luis D. Solis-Murgas (Environmental Science and Pollution Research, 2018)

Abnormalities in flatfishes of the south‐west Atlantic Ocean - D. L. Castellini; M. González‐Castro; A. Lopez‐Cazorla; J. M. Díaz De Astarloa (Journal of Fish Biology, 2018)
Five adult paralichthyid specimens with various kinds of abnormalities are reported from the south‐west Atlantic Ocean. These abnormal flatfish specimens represent the first records of wholly ambicoloured Paralichthys orbignyanus specimens having a deep notch between the eye and dorsal fin and a partially albinistic specimen having skeletal deformities and only the second record of an almost totally ambicoloured specimen. We also report the first observation of reversal in Paralichthys patagonicus and an almost totally ambicoloured, reversed Xystreurys rasile .

Micropropagation of Asparagus macrorrhizus, a Spanish endemic species in extreme extinction risk - J. J. Regalado; E. Carmona-Martin; M. López-Granero; A. Jiménez-Araujo; P. Castro; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Sedimentary infilling of bedrock-controlled palaeo-embayments off Cape Trafalgar, Strait of Gibraltar (Gulf of Cadiz) - Sandra de Castro; Francisco J. Lobo (Geo-Marine Letters, 2018)

Morpho-environmental strategies in the genus Ononis L. (subsections Natrix and Viscosae ) in Western Mediterranean - J. Rocha; R. Ramírez; M. Díaz; M. Martins; I. García-Cabral; F. Amich; R. Almeida; V. Carnide; I. Castro; A. L. Crespí (Plant Biosystems, 2018)

The evolution of androgen receptor expression and behavior in Anolis lizard forelimb muscles - Michele A. Johnson; Bonnie K. Kircher; Diego J. Castro (Journal of Comparative Physiology A, 2018)

An integrated analysis (microfacies and ichnology) of a shallow carbonate-platform succession: upper Aptian, Lower Cretaceous, Betic Cordillera - L. M. Nieto; M. Reolid; F. J. Rodríguez-Tovar; J. M. Castro; J. M. Molina; P. A. Ruiz-Ortiz (Facies, 2018)

Magnetic nanoparticles as a novel strategy for marine toxins mitigation - Jesús González-Jartín; Inés Rodríguez; Amparo Alfonso; María Sainz; M. Vieytes; Z. Vargas Osorio; L. De Castro Alves; Y. Y. Piñeiro-Redondo; J. Rivas; Luis Botana (Frontiers in Marine Science, 2018)

Exploring Institutional Mechanisms for Scientific Input into the Management Cycle of the National Protected Area Network of Peru: Gaps and Opportunities - M. D. López-Rodríguez; H. Castro; M. Arenas; J. M. Requena-Mullor; A. Cano; E. Valenzuela; J. Cabello (Environmental Management, 2017)

Plume composition and volatile flux of Nyamulagira volcano, Democratic Republic of Congo, during birth and evolution of the lava lake, 2014–2015 - N. Bobrowski; G. B. Giuffrida; S. Arellano; M. Yalire; M. Liotta; L. Brusca; S. Calabrese; S. Scaglione; J. Rüdiger; J. M. Castro; B. Galle; D. Tedesco (Bulletin of Volcanology, 2017)

Remote Sensing of Seagrass Leaf Area Index and Species: The Capability of a Model Inversion Method Assessed by Sensitivity Analysis and Hyperspectral Data of Florida Bay - John D. Hedley; Brandon J. Russell; Kaylan Randolph; Miguel Á. Pérez-Castro; Román M. Vásquez-Elizondo; Susana Enríquez; Heidi M. Dierssen (Frontiers in Marine Science, 2017)

Asparagus macrorrhizus Pedrol, Regalado et López-Encina, an endemic species from Spain in extreme extinction risk, is a valuable genetic resource for asparagus breeding - J. J. Regalado; R. Moreno; P. Castro; E. Carmona-Martin; R. Rodríguez; J. Pedrol; N. Larrañaga; R. Guillén; J. Gil; C. L. Encina (Genetic Resources and Crop Evolution, 2017)

How does temperature influences the development of lactococcosis? Transcriptomic and immunoproteomic in vitro approaches - R Castro; M Reguera‐Brito; G H López‐Campos; M M Blanco; M Aguado‐Urda; J F Fernández‐Garayzábal; A Gibello (Journal of Fish Diseases, 2017)
Lactococcus garvieae is the aetiological agent of lactococcosis, a haemorrhagic septicaemia that affects marine and freshwater fish, with special incidence and economic relevance in farmed rainbow trout. Water temperature is one of the most important predisposing factors in the development of lactococcosis outbreaks. Lactococcosis in trout usually occur when water temperatures rise to about 18 °C, while fish carriers remain asymptomatic at temperatures below 13 °C. The aim of this work was to analyse the differences in the complete transcriptome response of L. garvieae grown at 18 °C and at 13 °C and to identify the immunogenic proteins expressed by this bacterium at 18 °C. Our results show that water temperature influences the expression of L. garvieae genes involved in the lysis of part of the bacterial cell population and in the cold response bacterial adaptation. Moreover, the surface immunogenic protein profile at 18 °C suggests an important role of the lysozyme‐like enzyme, WxL surface proteins and some putative moonlighting proteins (proteins with more than one function, usually associated with different cellular locations) as virulence factors in L. garvieae . The results of this study could provide insights into the understanding of the virulence mechanisms of L. garvieae in fish.

Performance Benchmarking of Tsunami-HySEA Model for NTHMP’s Inundation Mapping Activities - Jorge Macías; Manuel J. Castro; Sergio Ortega; Cipriano Escalante; José Manuel González-Vida (Pure and Applied Geophysics, 2017)

Search and analysis of genes involved in antibiotic resistance in Chilean strains of Piscirickettsia salmonis - C Cartes; A Isla; F Lagos; D Castro; M Muñoz; A Yañez; D Haussmann; J Figueroa (Journal of Fish Diseases, 2017)
Piscirickettsia salmonis is the pathogen causing Piscirickettsiosis. For treatment, the industry mainly uses oxytetracycline and florfenicol, so it is essential to understand the degree of susceptibility of this pathogen to these drugs. But this is still unknown for a large number of P. salmonis strains, as are the molecular mechanisms responsible for greater or lesser susceptibility. However, genes that confer resistance to these antimicrobials have been reported and characterized for this and other bacterial species, among which are membrane proteins that take out the drug. Our results identified differences in the degree of susceptibility to both antibiotics among different Chilean isolated of these bacteria. We analysed 10 available genomes in our laboratory and identified ~140 genes likely to be involved in antibiotic resistance. We analysed six specific genes, which suggests that some of them would eventually be relevant in conferring resistance to both antibiotics, as they encode for specific transporter proteins, which increase the number of transcripts when grown in media with these antibiotics. Our results were corroborated with EtBr permeability analysis, which revealed that the LF ‐89 strain accumulates this compound and has a reduced capacity to expulse it compared with the field strains.

Contribution by vertebrates to seed dispersal effectiveness in the Galápagos Islands: a community‐wide approach - M. Nogales; A. González‐Castro; B. Rumeu; A. Traveset; P. Vargas; P. Jaramillo; J. M. Olesen; R. H. Heleno (Ecology, 2017)
Seed dispersal and seedling recruitment are crucial phases in the life cycle of all spermatophyte plants. The net contribution of seed dispersers to plant establishment is known as seed dispersal effectiveness ( SDE ) and is defined as the product of a quantitative (number of seeds dispersed) and a qualitative (probability of recruitment) component. In Galápagos, we studied the direct contribution to SDE (number of seeds dispersed and effect on seedling emergence) provided by the five island groups of frugivores (giant tortoises, lizards, medium‐sized passerine birds, small non‐finch passerine birds, and finches) in the two main habitats in this archipelago: the lowland and the highland zones, and found 16 vertebrate species dispersing 58 plant species. Data on frequency of occurrence of seeds in droppings and number of seeds dispersed per unit area produced contrasting patterns of seed dispersal. Based on the former, giant tortoises and medium‐sized passerines were the most important seed dispersers. However, based on the latter, small non‐finch passerines were the most important dispersers, followed by finches and medium‐sized passerines. The effect of disperser gut passage on seedling emergence varied greatly depending on both the disperser and the plant species. Although the contribution to SDE provided by different disperser guilds changed across plant species, medium‐sized passerines (e.g., mockingbirds) provided a higher contribution to SDE than lava lizards in 10 out of 16 plant species analysed, whereas lava lizards provided a higher contribution to SDE than birds in five plant species. While both the quantitative and qualitative components addressed are important, our data suggests that the former is a better predictor of SDE in the Galápagos archipelago.

Ecology and recovery plans for the four Spanish endangered endemic butterfly species - M. L. Munguira; J. M. Barea-Azcón; S. Castro-Cobo; E. García-Barros; S. Miteva; J. Olivares; H. Romo (Journal of Insect Conservation, 2017)

Evaluating the predictive power of field variables for species and individual molecular identification on wolf noninvasive samples - Mónia Nakamura; Raquel Godinho; H. Rio-Maior; S. Roque; A. Kaliontzopoulou; J. Bernardo; D. Castro; S. Lopes; F. Petrucci-Fonseca; F. Álvares (European Journal of Wildlife Research, 2017)

The role of epigenetic modifiers in extended cultures of functional hepatocyte-like cells derived from human neonatal mesenchymal stem cells - M. Cipriano; J. C. Correia; S. P. Camões; N. G. Oliveira; P. Cruz; H. Cruz; M. Castro; J. L. Ruas; J. M. Santos; J. P. Miranda (Archives of Toxicology, 2017)

Lymphocystis disease virus: its importance in aquaculture - Juan J. Borrego; Estefania J. Valverde; Alejandro M. Labella; Dolores Castro (Reviews in Aquaculture, 2017)
Lymphocystis disease virus ( LCDV ) is the causative agent of a well‐known fish viral disease that is characterized by hypertrophy of fibroblastic cells in the connective tissue. This viral disease affects more than 125 wild and cultured species of teleost fish from marine and freshwater environments and has a cosmopolitan geographical distribution. In aquaculture systems, the prevalence of LCDV infection is very high, likely reflecting the horizontal transmission of this virus. The incidence rate of the disease may reach 70%, causing significant economic losses for the aquaculture industry. This review provides information on the taxonomy, viral properties, epizootiology and pathogenesis, diagnostic methods and control measures of LCDV infection in fish.

Numerical Study of Blood Clots Influence on the Flow Pattern and Platelet Activation on a Stented Bifurcation Model - P. García Carrascal; J. García García; J. Sierra Pallares; F. Castro Ruiz; F. J. Manuel Martín (Annals of Biomedical Engineering, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

Hydrolytic enzyme-producing microbes in the Antarctic oligochaete Grania sp. (Annelida) - Lorena M. Herrera; César X. García-Laviña; Juan J. Marizcurrena; Odile Volonterio; Rodrigo Ponce de León; Susana Castro-Sowinski (Polar Biology, 2017)

The climate in Zafra from 1750 to 1840: temperature indexes from documentary sources - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2017)

Silver nanoparticles from AgNO3–affinin complex synthesized by an ecofriendly route: chitosan-based electrospun composite production - Fernando Bedolla-Cázares; Perla E. Hernández-Marcelo; Mario A. Gómez-Hurtado; Gabriela Rodríguez-García; Rosa E. del Río; Yliana López-Castro; Juan Pablo García-Merinos; J. Martín Torres-Valencia; J. Betzabe González-Campos (Clean Technologies and Environmental Policy, 2017)

Obtaining advanced generations from Solanum peruvianum PI 126944 in the genetic background of S. lycopersicum by immature seed culture - G. Campos; C. Gisbert; A. Pérez-de-Castro; M. J. Díez (Euphytica, 2017)

Inactivation, lysis and degradation by-products of Saccharomyces cerevisiae by electrooxidation using DSA - Lyliane F. Trigueiro; Larissa M. Silva; Luciana A. B. D. Itto; Thiago M. B. F. Oliveira; Artur J. Motheo; Carlos A. Martínez-Huitle; Janete J. F. Alves; Suely S. L. Castro (Environmental Science and Pollution Research, 2017)

Rapid and Sensitive Detection of Lymphocystis Disease Virus Genotype VII by Loop-Mediated Isothermal Amplification - Estefanía J. Valverde; Irene Cano; Dolores Castro; Richard K. Paley; Juan J. Borrego (Food and Environmental Virology, 2017)

Integrated proteomics and metabolomics suggests symbiotic metabolism and multimodal regulation in a fungal‐endobacterial system - Zhou Li; Qiuming Yao; Stephen P. Dearth; Matthew R. Entler; Hector F. Castro Gonzalez; Jessie K. Uehling; Rytas J. Vilgalys; Gregory B. Hurst; Shawn R. Campagna; Jessy L. Labbé; Chongle Pan (Environmental Microbiology, 2017)
Summary Many plant‐associated fungi host endosymbiotic endobacteria with reduced genomes. While endobacteria play important roles in these tri‐partite plant–fungal–endobacterial systems, the active physiology of fungal endobacteria has not been characterized extensively by systems biology approaches. Here, we use integrated proteomics and metabolomics to characterize the relationship between the endobacterium Mycoavidus sp. and the root‐associated fungus Mortierella elongata . In nitrogen‐poor media, M. elongata had decreased growth but hosted a large and growing endobacterial population. The active endobacterium likely extracted malate from the fungal host as the primary carbon substrate for energy production and biosynthesis of phospho‐sugars, nucleobases, peptidoglycan and some amino acids. The endobacterium obtained nitrogen by importing a variety of nitrogen‐containing compounds. Further, nitrogen limitation significantly perturbed the carbon and nitrogen flows in the fungal metabolic network. M. elongata regulated many pathways by concordant changes on enzyme abundances, post‐translational modifications, reactant concentrations and allosteric effectors. Such multimodal regulations may be a general mechanism for metabolic modulation.

Factors affecting tolerance to herbivory in a calcifying alga on coral reefs - Carolina Castro-Sanguino; Catherine Lovelock; Peter J. Mumby (Marine Biology, 2017)

The effect of resident vegetation cover on abundance and diversity of green lacewings (Neuroptera: Chrysopidae) on olive trees - Mario Porcel; B. Cotes; J. Castro; M. Campos (Journal of Pest Science, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Gastrointestinal nematode infection does not affect selection of tropical foliage by goats in a cafeteria trial - J. Ventura-Cordero; P. G. González-Pech; P. R. Jaimez-Rodriguez; G. I. Ortíz-Ocampo; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2017)

Performance and health of Holstein calves fed different levels of milk fortified with symbiotic complex containing pre- and probiotics - M. I. Marcondes; T. R. Pereira; J. C. C. Chagas; E. A. Filgueiras; M. M. D. Castro; G. P. Costa; A. L. L. Sguizzato; R. D. Sainz (Tropical Animal Health and Production, 2016)

An Olive Tree Pruning Biorefinery for Co-Producing High Value-Added Bioproducts and Biofuels: Economic and Energy Efficiency Analysis - J. M. Romero-García; A. Sanchez; G. Rendón-Acosta; J. C. Martínez-Patiño; E. Ruiz; G. Magaña; E. Castro (BioEnergy Research, 2016)

Nitrogen Use Efficiency for Sugarcane-Biofuel Production: What Is Next? - R. Otto; S. A. Q. Castro; E. Mariano; S. G. Q. Castro; H. C. J. Franco; P. C. O. Trivelin (BioEnergy Research, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Unveiling the influence of the environment on the migration pattern of the Atlantic pomfret ( Brama brama ) in North‐eastern Atlantic waters - M. Quinzán; J. Castro; M. Marín; G. Costas; S. Monserrat; A. Amores; E. Massutí; M. Hidalgo (Fisheries Oceanography, 2016)
Hydroclimatic variability is one of the main factors that drives inter‐annual changes in fish migration patterns. This study analyses the relationship between climate‐oceanographic factors and migration of the Atlantic pomfret ( Brama brama ) in NE Atlantic waters. Geo‐referenced catch data from logbooks of longliners operating in European Atlantic waters from 2002 to 2013 were linked to environmental indices at different temporal and spatial scales. Our results point to a strong influence of temperature at 200 m depth as the key factor along with the upwelling in the Galician ( NW Iberian) waters. However, sea surface temperature ( SST ) indirectly affects the geographical display of Atlantic pomfret migration, and large migrations are observed in scenarios of high SST s in the migratory area ( c . above 14.7°C). Migrations are constrained during years when temperatures are below this threshold. A longer time‐series of annual landings (1950–2013) supports this evidence and highlights the significant influence of temperature at 200‐m depth along with the landings of the previous year. Length frequency distributions suggest an increase in size between consecutive seasons supporting the hypothesis that migration is a feeding strategy and a return to tropical waters of origin for spawning. Our study shows that the temperature of intermediate waters is a key variable in determining the northward migration of the Atlantic pomfret whereas density‐dependence and surface climatic conditions trigger secondary effects on the migration pattern of this species.

Concentrations of Metals, Metalloids, and Chlorinated Pollutants in Blood and Plasma of White Stork (Ciconia ciconia) Nestlings From Spain - M. Pérez-López; I. De la Casa-Resino; D. Hernández-Moreno; J. Galeano; M. P. Míguez-Santiyán; A. de Castro-Lorenzo; M. Otero-Filgueiras; O. Rivas-López; F. Soler (Archives of Environmental Contamination and Toxicology, 2016)

Pollen flow between flowers of the same morph in invasive populations of Oxalis pes-caprae L. in the western Mediterranean region - J. Costa; V. Ferrero; M. Castro; A. Jorge; A. Afonso; J. Loureiro; S. Castro (Plant Biosystems, 2016)

Erratum to: Preliminary study on serum paraoxonase-1 status and chemokine (C-C motif) ligand 2 in hospitalized elderly patients with catheter-associated asymptomatic bacteriuria - S. Iftimie; A. García-Heredia; I. Pujol; F. Ballester; I. Fort-Gallifa; J. M. Simó; J. Joven; J. Camps; A. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Preliminary study on serum paraoxonase-1 status and chemokine (C-C motif) ligand 2 in hospitalized elderly patients with catheter-associated asymptomatic bacteriuria - S. Iftimie; A. García-Heredia; I. Pujol; F. Ballester; I. Fort-Gallifa; J. M. Simó; J. Joven; J. Camps; A. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Maize bushy stunt phytoplasma affects native corn at high elevations in Southeast Mexico - Edel Pérez-López; Chrystel Y. Olivier; Mauricio Luna-Rodríguez; Yesenia Rodríguez; Lourdes G. Iglesias; Alejandro Castro-Luna; Jacel Adame-García; Tim J. Dumonceaux (European Journal of Plant Pathology, 2016)

Subaerial biofilms on granitic historic buildings: microbial diversity and development of phototrophic multi-species cultures - D. Vázquez-Nion; J. Rodríguez-Castro; M. C. López-Rodríguez; I. Fernández-Silva; B. Prieto (Biofouling, 2016)

Landscape influence on the feeding habits of European badger (Meles meles) in arid Spain - J. M. Requena-Mullor; E. López; A. J. Castro; E. Virgós; H. Castro (Mammal Research, 2016)

Radial and tangential migration of telencephalic somatostatin neurons originated from the mouse diagonal area - Luis Puelles; N. Morales-Delgado; P. Merchán; B. Castro-Robles; M. Martínez-de-la-Torre; C. Díaz; J. L. Ferran (Brain Structure and Function, 2016)

Seed‐dispersal networks on the C anaries and the G alápagos archipelagos: interaction modules as biogeographical entities - M. Nogales; R. Heleno; B. Rumeu; A. González‐Castro; A. Traveset; P. Vargas; J. M. Olesen (Global Ecology and Biogeography, 2016)
Aim Mutualistic network parameters, such as modularity and nestedness, show non‐random linkage patterns. Both increase network stability in different ways. Modularity hampers extinction cascades, whereas nestedness resists network disassembly. We explore these parameters in seed‐dispersal networks in two archipelagos and the significance of life history, habitat, geography and phylogeny as drivers of linkage patterns and the applicability of modules as biogeographical entities. Location C anaries ( A tlantic O cean) and G alápagos ( P acific O cean). Methods We compiled data on plant–seed disperser interactions from own observations and the literature, estimated network parameters describing interaction patterns (connectance, nestedness and modularity) and constructed a backbone phylogeny for the analyses. Results The C anarian network was highly nested but weakly modular, whereas the G alápagos network showed the opposite characteristics. Most key network species are native and have a favourable conservation status. Modularity in the C anaries is correlated with habitats (indirectly affected by altitude and orientation), whereas in the G alápagos it mainly reflects the functional roles of species. Main conclusions The divergent link patterns for the archipelagos imply that the highly nested C anarian network is stable against disassembly, whereas the modular G alápagos network may show strong resistance against extinction cascades. This difference may be driven by the specific evolutionary dynamics on the archipelagos.

Effect of galactofucan sulfate of a brown seaweed on induced hepatotoxicity in rats, sodium pentobarbital-induced sleep, and anti-inflammatory activity - Luiza Sheyla Evenni P. Will Castro; Allisson J. Gomes Castro; Marília da S. Nascimento Santos; Thuane de Sousa Pinheiro; Kahena de Quevedo Florentin; Luciana G. Alves; Eliane Marinho Soriano; Renata Mendonça Araújo; Edda Lisboa Leite (Journal of Applied Phycology, 2016)

Particular activation phenotype of T cells expressing HLA-DR but not CD38 in GALT from HIV-controllers is associated with immune regulation and delayed progression to AIDS - Sandra M. Gonzalez; Natalia A. Taborda; Luis A. Correa; Gustavo A. Castro; Juan C. Hernandez; Carlos J. Montoya; Maria T. Rugeles (Immunologic Research, 2016)

Event-related fields evoked by vocal response inhibition: a comparison of younger and older adults - Leidy J. Castro-Meneses; Blake W. Johnson; Paul F. Sowman (Experimental Brain Research, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

The effect of structurally complex corals and herbivory on the dynamics of Halimeda - Carolina Castro-Sanguino; Catherine Lovelock; Peter J. Mumby (Coral Reefs, 2016)

Trophic models and short-term dynamic simulations for benthic-pelagic communities at Banco Chinchorro Biosphere Reserve (Mexican Caribbean): a conservation case - F.A. Rodríguez-Zaragoza; M. Ortiz; F. Berrios; L. Campos; A. de Jesús-Navarrete; J. Castro-Pérez; A. Hernández-Flores; M. García-Rivas; F. Fonseca-Peralta; E. Gallegos-Aguilar (Community Ecology, 2016)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Antinociceptive effect of a novel armed spider peptide Tx3-5 in pathological pain models in mice - Sara M. Oliveira; Cássia R. Silva; Gabriela Trevisan; Jardel G. Villarinho; Marta N. Cordeiro; Michael Richardson; Márcia H. Borges; Célio J. Castro; Marcus V. Gomez; Juliano Ferreira (Pflügers Archiv - European Journal of Physiology, 2016)

Insights into the virulence‐related genes of Edwardsiella tarda isolated from turbot in Europe: genetic homogeneity and evidence for vibrioferrin production - N Castro; C R Osorio; N Buján; J C Fuentes; J Rodríguez; M Romero; C Jiménez; A E Toranzo; B Magariños (Journal of Fish Diseases, 2016)
Edwardsiella tarda has long been known as a pathogen that causes severe economic losses in aquaculture industry. Insights gained on E. tarda pathogenesis may prove useful in the development of new methods for the treatment of infections as well as preventive measures against future outbreaks. In this report, we have established the correlation between the presence of virulence genes, related with three aspects typically involved in bacterial pathogenesis (chondroitinase activity, quorum sensing and siderophore‐mediated ferric uptake systems), in the genome of E. tarda strains isolated from turbot in Europe and their phenotypic traits. A total of 8 genes were tested by PCR for their presence in 73 E. tarda isolates. High homogeneity was observed in the presence/absence pattern of all the strains. Positive results in the amplification of virulence‐related genes were correlated with the detection of chondroitinase activity in agar plates, in vivo AHL production during fish infection and determination of type of siderophore produced by E. tarda . To the best of our knowledge, this is the first study carried out with European strains on potential virulence factors. Furthermore, we demonstrated for the first time that E. tarda produces the siderophore vibrioferrin.

On the Effectiveness of Wastewater Cylindrical Reactors: an Analysis Through Steiner Symmetrization - J. I. Díaz; D. Gómez-Castro (Pure and Applied Geophysics, 2016)

Genetic diversity and population structure of Indo-Pacific sailfish Istiophorus platypterus in the eastern Pacific - Griselma G. Rubio-Castro; Casimiro Quiñonez-Velázquez; Francisco J. García-Rodríguez (Fisheries Science, 2016)

Vocal response inhibition is enhanced by anodal tDCS over the right prefrontal cortex - Leidy J. Castro-Meneses; Blake W. Johnson; Paul F. Sowman (Experimental Brain Research, 2016)

Expression of myostatin in the spotted rose snapper Lutjanus guttatus during larval and juvenile development under cultured conditions - J. Torres‐Velarde; L. Ibarra‐Castro; E. Rodríguez‐Ibarra; I. Sifuentes‐Romero; R. Hernández‐Cornejo; A. García‐Gasca (Journal of Fish Biology, 2015)
In this study, the developmental expression pattern of myostatin ( mstn ) in the spotted rose snapper Lutjanus guttatus under culture conditions is presented. The full coding sequence of mstn from L. guttatus was isolated from muscle tissue, obtaining 1134 nucleotides which encode a peptide of 377 amino acids. The phylogenetic analysis indicated that this sequence corresponds to mstn‐1 . mstn expression was detected in embryonic stages, and maintained at low levels until 28 days post‐hatch, when it showed a significant increase, coinciding with the onset of metamorphosis. After that, expression was fluctuating, coinciding probably with periods of rapid and slow muscle growth or individual growth rates. mstn expression was also analysed by body mass with higher levels detected in smaller animals, irrespective of age. mstn was also expressed in other tissues from L. guttatus , presenting higher levels in brain, eye and gill. In brain for instance, two variants of mstn were isolated, both coding sequences were identical to muscle, except that one of them contained a 75 nucleotide deletion in exon 1, maintaining the reading frame but deleting two conserved cysteine residues. Phylogenetic analysis indicated that this brain variant was also mstn‐1 . The function of this variant is not clear and needs further investigation. These results indicate that mstn‐1 participates in different physiological processes other than muscle growth in fishes.

Impact of freshwater inputs on the spatial structure of benthic macroinvertebrate communities in two landlocked coastal lagoons - P. M. Félix; M. J. Correia; P. Chainho; J. L. Costa; M. L. Chaves; T. Cruz; J. J. Castro; C. Mirra; I. Domingos; A. C. F. Silva; L. Cancela da Fonseca (Hydrobiologia, 2015)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

New tools ( DNA barcoding), old hypothesis: the case of the taxonomic identity of the Argentine hakes (Actinopterygii: Merluccius ) - M. Y. Deli Antoni; M. González‐Castro; J. M. Díaz de Astarloa (Journal of Fish Biology, 2015)
The present study evaluated the possible occurrence of cryptic species among Merluccidae from Argentina by examining sequences of cytochrome c oxidase subunit I ( coI ) mtDNA . This approach can discriminate Merluccius hubbsi and Merluccius australis ; specimens with morphological diagnostic characters of Merluccius patagonicus formed a cohesive cluster with M. hubbsi specimens. BIN analysis confirmed the effectiveness of barcoding within a global context.

Atlantic and Mediterranean synoptic drivers of central Spanish juniper growth - Jan Esper; Janine Großjean; Jesús Julio Camarero; Ana I. García-Cervigón; José M. Olano; J. Fidel González-Rouco; Fernando Domínguez-Castro; Ulf Büntgen (Theoretical and Applied Climatology, 2015)

Study of the somaclonal variation produced by different methods of polyploidization in Asparagus officinalis L. - J. J. Regalado; E. Carmona Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

Relative telomere length is associated with a functional polymorphism in the monoamine oxidase A gene in a South American sample - CÉSAR A. SPECK-HERNÁNDEZ; DIEGO A. OJEDA; LUIS J. CASTRO-VEGA; DIEGO A. FORERO (Journal of Genetics, 2015)

Removal of Decachlorobiphenyl in Vermicomposting Process Amended with Rabbit Manure and Peat Moss - Juan J. Villalobos-Maldonado; Rocío Meza-Gordillo; Norma A. Mancilla-Margalli; Teresa R. Ayora-Talavera; Martha A. Rodríguez-Mendiola; Carlos Arias-Castro; Paola T. Vázquez-Villegas; Federico A. Gutiérrez-Miceli; Víctor M. Ruíz-Valdiviezo (Water, Air, & Soil Pollution, 2015)

Micropropagation of wild species of the genus Asparagus L. and their interspecific hybrids with cultivated A. officinalis L., and verification of genetic stability using EST-SSRs - J. J. Regalado; E. Carmona-Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Evaluation of the Impact of Different Soil Salinization Processes on Organic and Mineral Soils - J. Jesus; F. Castro; A. Niemelä; Maria-Teresa Borges; A. S. Danko (Water, Air, & Soil Pollution, 2015)

Multi-environment multi-QTL association mapping identifies disease resistance QTL in barley germplasm from Latin America - Lucia Gutiérrez; Silvia Germán; Silvia Pereyra; Patrick M. Hayes; Carlos A. Pérez; Flavio Capettini; Andres Locatelli; Natalia M. Berberian; Esteban E. Falconi; Rigoberto Estrada; Dario Fros; Victor Gonza; et al. (Theoretical and Applied Genetics, 2015)

Genetic mapping of QTL for maize weevil resistance in a RIL population of tropical maize - Fernando F. Castro-Álvarez; Manilal William; David J. Bergvinson; Silverio García-Lara (Theoretical and Applied Genetics, 2015)

The climate in Zafra from 1750 to 1840: precipitation - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2015)

Exploring alternative ovarian cancer biomarkers using innovative nanotechnology strategies - Cesar M. Castro; Hyungsoon Im; Christine Le; Hakho Lee; Ralph Weissleder; Michael J. Birrer (Cancer and Metastasis Reviews, 2015)

A cost-effective straightforward protocol for shotgun Illumina libraries designed to assemble complete mitogenomes from non-model species - Marie-Ka Tilak; Fabienne Justy; Mélanie Debiais-Thibaud; Fidel Botero-Castro; Frédéric Delsuc; Emmanuel J. P. Douzery (Conservation Genetics Resources, 2015)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Carbon Flows Through the Pelagic Sub-food Web in Two Basins of the Chilean Patagonian Coastal Ecosystem: the Significance of Coastal–Ocean Connection on Ecosystem Parameters - Héctor J. Pavés; Humberto E. González; Leonardo Castro; José L. Iriarte (Estuaries and Coasts, 2015)

An environmentally friendly method for the determination of triazine herbicides in estuarine seawater samples by dispersive liquid–liquid microextraction - N. Rodríguez-González; E. Beceiro-González; M. J. González-Castro; S. Muniategui-Lorenzo (Environmental Science and Pollution Research, 2015)

Reassessing global change research priorities in mediterranean terrestrial ecosystems: how far have we come and where do we go from here? - E. Doblas‐Miranda; J. Martínez‐Vilalta; F. Lloret; A. Álvarez; A. Ávila; F. J. Bonet; L. Brotons; J. Castro; J. Curiel Yuste; M. Díaz; P. Ferrandis; E. García‐Hurtado; et al. (Global Ecology and Biogeography, 2015)
Aim Mediterranean terrestrial ecosystems serve as reference laboratories for the investigation of global change because of their transitional climate, the high spatiotemporal variability of their environmental conditions, a rich and unique biodiversity and a wide range of socio‐economic conditions. As scientific development and environmental pressures increase, it is increasingly necessary to evaluate recent progress and to challenge research priorities in the face of global change. Location Mediterranean terrestrial ecosystems. Methods This article revisits the research priorities proposed in a 1998 assessment. Results A new set of research priorities is proposed: (1) to establish the role of the landscape mosaic on fire‐spread; (2) to further research the combined effect of different drivers on pest expansion; (3) to address the interaction between drivers of global change and recent forest management practices; (4) to obtain more realistic information on the impacts of global change and ecosystem services; (5) to assess forest mortality events associated with climatic extremes; (6) to focus global change research on identifying and managing vulnerable areas; (7) to use the functional traits concept to study resilience after disturbance; (8) to study the relationship between genotypic and phenotypic diversity as a source of forest resilience; (9) to understand the balance between C storage and water resources; (10) to analyse the interplay between landscape‐scale processes and biodiversity conservation; (11) to refine models by including interactions between drivers and socio‐economic contexts; (12) to understand forest–atmosphere feedbacks; (13) to represent key mechanisms linking plant hydraulics with landscape hydrology. Main conclusions (1) The interactive nature of different global change drivers remains poorly understood. (2) There is a critical need for the rapid development of regional‐ and global‐scale models that are more tightly connected with large‐scale experiments, data networks and management practice. (3) More attention should be directed to drought‐related forest decline and the current relevance of historical land use.

Human T-lymphotropic virus type 2 subtype b in a patient with chronic neurological disorder - Carolina Rosadas; Ana C. P. Vicente; Louise Zanella; Mauro J. Cabral-Castro; José M. Peralta; Marzia Puccioni-Sohler (Journal of NeuroVirology, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Predicting climate change impacts on native and invasive tree species using radial growth and twenty-first century climate scenarios - N. González-Muñoz; J. C. Linares; P. Castro-Díez; U. Sass-Klaassen (European Journal of Forest Research, 2014)

Biogeography and conservation of aquatic fauna in spring-fed tropical canyons of the southern Sonoran Desert, Mexico - Michael T. Bogan; Nohemí Noriega-Felix; Sylvette Leonor Vidal-Aguilar; Lloyd T. Findley; David A. Lytle; Oscar G. Gutiérrez-Ruacho; J. Andrés Alvarado-Castro; Alejandro Varela-Romero (Biodiversity and Conservation, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

Biological and chemical analyses of a laboratory-scale biofilter for oxygenate bioremediation in simulated groundwater - J. Purswani; G. A. Silva-Castro; I. M. Guisado; J. González-López; C. Pozo (International Journal of Environmental Science and Technology, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

Fucose-containing sulfated polysaccharides from brown macroalgae Lobophora variegata with antioxidant, anti-inflammatory, and antitumoral effects - Luiza Sheyla E. P. Will Castro; Thuane S. Pinheiro; Allisson J. G. Castro; Celina M. P. G. Dore; Naissandra B. da Silva; Monique Gabriela das C. Faustino Alves; Marilia S. Nascimento Santos; Edda Lisboa Leite (Journal of Applied Phycology, 2014)

Irrigation water quality and the benefits of implementing good agricultural practices during tomato (Lycopersicum esculentum) production - M. Estrada-Acosta; M. Jiménez; C. Chaidez; J. León-Félix; N. Castro-del Campo (Environmental Monitoring and Assessment, 2014)

Environmental Factors Affecting Germination and Seedling Survival of Carolina Willow (Salix Caroliniana) - Luz M. Castro-Morales; Pedro F. Quintana-Ascencio; John E. Fauth; Kimberli J. Ponzio; Dianne L. Hall (Wetlands, 2014)

The LonB protease controls membrane lipids composition and is essential for viability in the extremophilic haloarchaeon H aloferax volcanii - Micaela Cerletti; María J. Martínez; María I. Giménez; Diego E. Sastre; Roberto A. Paggi; Rosana E. De Castro (Environmental Microbiology, 2014)
Summary Although homologs of the ATP ‐dependent L on protease exist in all domains of life, the relevance of this protease in archaeal physiology remains a mystery. In this study, we have constructed and phenotypically characterized deletion and conditional lon mutants in the model haloarchaeon H aloferax volcanii to elucidate the role of the unusual membrane‐bound LonB protease in archaea. H vlon could be deleted from the chromosome only when a copy of the wild type gene was provided in trans suggesting that L on is essential for survival in this archaeon. Successful complementation of the lethal phenotype of Δ H vlon was attained by expression of the heterologous protease gene N mlon from the haloalkaliphilic archaeon N atrialba magadii , meaning that the biological function of L on is conserved in these organisms. Suboptimal cellular levels of L on protein affected growth rate, cell shape, cell pigmentation, lipid composition and sensitivity to various antibiotics. The contents of bacterioruberins and some polar lipids were increased in the lon mutants suggesting that L on is linked to maintenance of membrane lipid balance which likely affects cell viability in this archaeon. The phenotypes associated to a membrane‐bound LonB protease mutant were examined for the first time providing insight on the relevance of this protease in archaeal physiology.

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Safety and Health Hazard Observations in Hmong Farming Operations - R. L. Neitzel; J. Krenz; A. B. de Castro (Journal of Agromedicine, 2014)

Acquisition of resistant microorganisms and infections in HIV-infected patients admitted to the ICU - N. Cobos-Trigueros; M. Rinaudo; M. Solé; P. Castro; J. Pumarol; C. Hernández; S. Fernández; J. M. Nicolás; J. Mallolas; J. Vila; L. Morata; J. M. Gatell; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Is the effect of farming practices on songbird communities landscape dependent? A case study of olive groves in southern Spain - J. C. Castro-Caro; I. C. Barrio; F. S. Tortosa (Journal of Ornithology, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Advances in surfactants for agrochemicals - Mariano J. L. Castro; Carlos Ojeda; Alicia Fernández Cirelli (Environmental Chemistry Letters, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Positive influence of a natural product as propolis on antioxidant status and lipid peroxidation in senescent rats - Cristina Lisbona; Javier Díaz-Castro; María J. M. Alférez; Isabel M. Guisado; Rafael Guisado; Inmaculada López-Aliaga (Journal of Physiology and Biochemistry, 2013)

Influence of Several Sources and Amounts of Iron on DNA, Lipid and Protein Oxidative Damage During Anaemia Recovery - Javier Díaz-Castro; Yenela García; Inmaculada López-Aliaga; María J. M. Alférez; Silvia Hijano; Aurora Ramos; Margarita S. Campos (Biological Trace Element Research, 2013)

Genetic variability in Sambucus nigra L. clones : a preliminary molecular approach - J. LIMA-BRITO; L. CASTRO; J. COUTINHO; F. MORAIS; L. GOMES; H. GUEDES-PINTO; A. CARVALHO (Journal of Genetics, 2013)

Generating anatomical models of the heart and the aorta from medical images for personalized physiological simulations - J. Weese; A. Groth; H. Nickisch; H. Barschdorf; F. M. Weber; J. Velut; M. Castro; C. Toumoulin; J. L. Coatrieux; M. De Craene; G. Piella; C. Tobón-Gomez; et al. (Medical & Biological Engineering & Computing, 2013)

Detection of a new Os HV ‐1 DNA strain in the healthy P acific oyster, C rassostrea gigas Thunberg, from the G ulf of C alifornia - J M Grijalva‐Chon; R Castro‐Longoria; J Ramos‐Paredes; T L Enríquez‐Espinoza; F Mendoza‐Cano (Journal of Fish Diseases, 2013)

Genetic map of the primocane-fruiting and thornless traits of tetraploid blackberry - P. Castro; E. T. Stafne; J. R. Clark; K. S. Lewers (Theoretical and Applied Genetics, 2013)

Multilocus genetic diversity and historical biogeography of the endemic wall lizard from I biza and F ormentera, P odarcis pityusensis ( S quamata: L acertidae) - V. Rodríguez; R. P. Brown; B. Terrasa; V. Pérez‐Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Molecular Ecology, 2013)
Two monophyletic sister species of wall lizards inhabit the two main groups of B alearic I slands: P odarcis lilfordi from islets and small islands around M allorca and M enorca and P odarcis pityusensis from I biza, F ormentera and associated islets. Genetic diversity within the endangered P . lilfordi has been well characterized, but P . pityusensis has not been studied in depth. Here, 2430 bp of mt DNA and 15 microsatellite loci were analysed from P . pityusensis populations from across its natural range. Two main genetic groupings were identified, although geographical structuring differed slightly between the mt DNA and the nuclear loci. In general, individuals from islets/islands adjacent to the main island of I biza were genetically distinct from those from F ormentera and the associated F reus islands for both mt DNA and the nuclear loci. However, most individuals from the island of I biza were grouped with neighbouring islets/islands for nuclear loci, but with F ormentera and F reus islands for the mitochondrial locus. A time‐calibrated B ayesian tree was constructed for the principal mitochondrial lineages within the B alearics, using the multispecies coalescent model, and provided statistical support for divergence of the two main P . pityusensis lineages 0.111–0.295 Ma. This suggests a mid‐late P leistocene intraspecific divergence, compared with an early P leistocene divergence in P . lilfordi , and postdates some major increases in sea level between 0.4 and 0.6 Ma, which may have flooded F ormentera. The program IM a2 provided a posterior divergence time of 0.089–0.221 Ma, which was similar to the multispecies coalescent tree estimate. More significantly, it indicated low but asymmetric effective gene copy migration rates, with higher migration from F ormentera to I biza populations. Our findings suggest that much of the present‐day diversity may have originated from a late P leistocene colonization of one island group from the other, followed by allopatric divergence of these populations. Subsequent gene flow between these insular groups seems likely to be explained by recent human introductions. Two evolutionary significant units can be defined for P . pityusensis but these units would need to exclude the populations that have been the subjects of recent admixture.

Initial development of a set of introgression lines from Solanum peruvianum PI 126944 into tomato: exploitation of resistance to viruses - O. Julián; J. Herráiz; S. Corella; I. di-Lolli; S. Soler; M. J. Díez; A. Pérez-de-Castro (Euphytica, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Echeveria yalmanantlanensis (Crassulaceae): A new species from Cerro Grande, Sierra de Manantlán, western Mexico - J. Antonio Vázquez-García; David Jimeno-S.; Ramón Cuevas-G.; Miguel Cházaro-B.; Miguel A. Muñiz-Castro (Brittonia, 2013)

Identification and genetic diversity of Rosellinia spp. associated with root rot of coffee in Colombia - Bertha L. Castro; Angela J. Carreño; Narmer F. Galeano; Jolanda Roux; Michael J. Wingfield; Álvaro L. Gaitán (Australasian Plant Pathology, 2013)

Nematode diversity in different microhabitats in a mangrove region - Taciana K. Pinto; Melanie C. V. Austen; Richard M. Warwick; Paul J. Somerfield; André M. Esteves; Francisco J. V. Castro; Verônica G. Fonseca‐Genevois; Paulo J. P. Santos (Marine Ecology, 2013)
Mangroves are highly productive environments that play important ecological and socioeconomic roles; however, they have been impacted to different degrees in most countries worldwide. The knowledge of which organisms inhabit this environment and their ecological interactions is the first step towards its conservation. The natural variability of environmental factors in mangroves provides numerous niches available to different species. Meiofauna have patchy patterns of distribution that are related to the availability of resources. Hence, meiofauna are expected to present a high diversity of different taxa occupying the different microhabitats offered by mangroves. This work aims to test the hypothesis that the assemblage structure of N ematoda varies significantly among mangrove microhabitats and to contribute knowledge on the meiofauna diversity in mangrove environments. This work was carried out in a mangrove region at P ernambuco state, N ortheastern B razil. Qualitative samples were collected in nine microhabitats which show different characteristics mainly in terms of presence of vegetation or another organism and sediment grain size. Univariate and multivariate analysis were applied to Nematoda genera abundance data. Our results demonstrate the existence of significant differences among microhabitats regarding nematode assemblage structure corroborating the hypothesis. Different N ematoda assemblages are present in at least seven microhabitats. These assemblages are composed of nematode genera with different trophic and morphological features, demonstrating a strong relationship between morphological diversity and ecological plasticity. Furthermore, this study also demonstrates the importance of the conservation of this ecosystem and its attributes.

Future sea ice conditions in Western H udson B ay and consequences for polar bears in the 21st century - Laura Castro de la Guardia; Andrew E. Derocher; Paul G. Myers; Arjen D. Terwisscha van Scheltinga; Nick J. Lunn (Global Change Biology, 2013)
The primary habitat of polar bears is sea ice, but in Western H udson B ay ( WH ), the seasonal ice cycle forces polar bears ashore each summer. Survival of bears on land in WH is correlated with breakup and the ice‐free season length, and studies suggest that exceeding thresholds in these variables will lead to large declines in the WH population. To estimate when anthropogenic warming may have progressed sufficiently to threaten the persistence of polar bears in WH , we predict changes in the ice cycle and the sea ice concentration ( SIC ) in spring (the primary feeding period of polar bears) with a high‐resolution sea ice‐ocean model and warming forced with 21st century IPCC greenhouse gas ( GHG ) emission scenarios: B1 (low), A1B (medium), and A2 (high). We define critical years for polar bears based on proposed thresholds in breakup and ice‐free season and we assess when ice‐cycle conditions cross these thresholds. In the three scenarios, critical years occur more commonly after 2050. From 2001 to 2050, 2 critical years occur under B1 and A2, and 4 under A1B; from 2051 to 2100, 8 critical years occur under B1, 35 under A1B and 41 under A2. Spring SIC in WH is high (>90%) in all three scenarios between 2001 and 2050, but declines rapidly after 2050 in A1B and A2. From 2090 to 2100, the mean spring SIC is 84 (±7)% in B1, 56 (±26)% in A1B and 20 (±13)% in A2. Our predictions suggest that the habitat of polar bears in WH will deteriorate in the 21st century. Ice predictions in A1B and A2 suggest that the polar bear population may struggle to persist after ca. 2050. Predictions under B1 suggest that reducing GHG emissions could allow polar bears to persist in WH throughout the 21st century.

Red deer (Cervus elaphus) as a host for the cattle tick Rhipicephalus microplus (Acari: Ixodidae) in Yucatan, Mexico - R. I. Rodríguez-Vivas; M. M. Ojeda-Chi; J. A. Rosado-Aguilar; I. C. Trinidad-Martínez; J. F. J. Torres-Acosta; V. Ticante-Perez; J. M. Castro-Marín; C. A. Tapia-Moo; G. Vázquez-Gómez (Experimental and Applied Acarology, 2013)

The 46359CT polymorphism of DNMT3B is associated with the risk of cervical cancer - Daniel Hernández-Sotelo; Rubén García-Aguilar; Yaneth Castro-Coronel; Jonathan J. Magaña; Marco Antonio Leyva-Vazquez; Luz del Carmen Alarcón-Romero; Esther López-Bayghen; Berenice Illades-Aguiar (Molecular Biology Reports, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Folate metabolite profiling of different cell types and embryos suggests variation in folate one-carbon metabolism, including developmental changes in human embryonic brain - Kit-Yi Leung; Sandra C. P. De Castro; Filipe Cabreiro; Peter Gustavsson; Andrew J. Copp; Nicholas D. E. Greene (Molecular and Cellular Biochemistry, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Transmission of lymphocystis disease virus to cultured gilthead seabream, S parus aurata L ., larvae - I Cano; E J Valverde; E Garcia‐Rosado; M C Alonso; B Lopez‐Jimena; J B Ortiz‐Delgado; J J Borrego; C Sarasquete; D Castro (Journal of Fish Diseases, 2013)
The transmission of lymphocystis disease virus ( LCDV ) to gilthead seabream, S parus aurata L ., larvae was investigated using fertilized eggs from a farm with previous reports of lymphocystis disease. LCDV genome was detected by PCR ‐hybridization in blood samples from 17.5% of the asymptomatic gilthead seabream broodstock analysed. Using the same methodology, eggs spawned from these animals were LCDV positive, as well as larvae hatched from them. The presence of infective viral particles was confirmed by cytopathic effects development on SAF ‐1 cells. Whole‐mount in situ hybridization ( ISH ) and immunohistochemistry ( IHC ) showed the presence of LCDV in the epidermis of larvae hatched from LCDV ‐positive eggs. When fertilized eggs were disinfected with iodine, no viral DNA was detected either in eggs (analysed by PCR ‐hybridization) or in larvae ( PCR ‐hybridization and ISH ). These results suggest the vertical transmission of LCDV , the virus being transmitted on the egg surface. Larvae hatched from disinfected eggs remain LCDV negative during the endotrophic phase, as showed by PCR ‐hybridization, ISH and IHC . After feeding on LCDV ‐positive rotifers, viral antigens were observed in the digestive tract, which suggests that viral entry could be achieved via the alimentary canal, and that rotifers can act as a vector in LCDV transmission to gilthead seabream larvae.

Cellular and humoral immune responses of S enegalese sole, S olea senegalensis ( K aup), following challenge with two P hotobacterium damselae subsp. piscicida strains from different geographical origins - B Costas; P C N P Rêgo; I Simões; J F Marques; M Castro‐Cunha; A Afonso (Journal of Fish Diseases, 2013)
The present study aimed to investigate leucocyte responses to inflammation as well as some innate immune parameters of S enegalese sole, S olea senegalensis , following challenge with two strains of P hotobacterium damselae subsp. piscicida belonging to the E uropean and J apanese clones described for this bacterium. Pathogenicity assays were performed to assess the virulence of each P hotobacterium damselae subsp. piscicida strain for sole. Subsequently, fish were intraperitoneally injected with phosphate‐buffered saline (control) or two concentrations (2 × 10 2 and 2 × 10 6 CFU mL −1 ) of each bacterial strain and sampled after 6 and 24 h. Results showed that the E uropean isolate induces a higher degree of response than the J apanese strain. While blood neutrophilia and monocytosis correlated well with the increase in neutrophil and macrophage numbers in the peritoneal cavity, fish infected with the E uropean isolate presented higher peritoneal cell numbers than fish challenged with the J apanese strain. In addition, alternative complement pathway activity and respiratory burst of head kidney leucocytes increased significantly in fish infected with the E uropean isolate. The enhanced innate immune response displayed by S enegalese sole challenged with the E uropean isolate is probably due to the higher degree of virulence presented by this P hotobacterium damselae subsp. piscicida strain.

Mapping wild pear trees ( Pyrus bourgaeana ) in Mediterranean forest using high-resolution QuickBird satellite imagery - S. Arenas-Castro; Y. Julien; J.C. Jiménez-Muñoz; J.A. Sobrino; J. Fernández-Haeger; D. Jordano-Barbudo (International Journal of Remote Sensing, 2013)

Concentration of ascorbic acid and antioxidant response in early life stages of Engraulis ringens and zooplankton during the spawning seasons of 2006–2009 off central Chile - M. C. Krautz; L. R. Castro; M. González; A. Llanos-Rivera; I. Montes; H. González; R. R. González; J. C. Vera (Marine Biology, 2013)

The first meteorological measurements in the Iberian Peninsula: evaluating the storm of November 1724 - F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2013)

Conventional tillage versus cover crops in relation to carbon fixation in Mediterranean olive cultivation - O. M. Nieto; J. Castro; E. Fernández-Ondoño (Plant and Soil, 2013)

Assessment of genetic diversity and phylogenetic relationships in Asparagus species related to Asparagus officinalis - P. Castro; J. Gil; A. Cabrera; R. Moreno (Genetic Resources and Crop Evolution, 2013)

Western Mediterranean precipitation over the last 300 years from instrumental observations - D. Camuffo; C. Bertolin; N. Diodato; C. Cocheo; M. Barriendos; F. Dominguez-Castro; E. Garnier; M. J. Alcoforado; M. F. Nunes (Climatic Change, 2013)

Population Fluctuation and Damage Caused by Phytophagous Mites on Three Rubber Tree Clones - E B Castro; F M Nuvoloni; C R R Mattos; R J F Feres (Neotropical Entomology, 2013)

Dynamic expression of the sodium-vitamin C co-transporters, SVCT1 and SVCT2, during perinatal kidney development - Francisco Nualart; Tamara Castro; Marcela Low; Juan Pablo Henríquez; Karina Oyarce; Pedro Cisternas; Andrea García; Alejandro J. Yáñez; Romina Bertinat; Viviana P. Montecinos; María Angeles García-Robles (Histochemistry and Cell Biology, 2013)

Cellular localization and levels of pectins and arabinogalactan proteins in olive (Olea europaea L.) pistil tissues during development: implications for pollen–pistil interaction - Cynthia Suárez; Agnieszka Zienkiewicz; Antonio J. Castro; Krzysztof Zienkiewicz; Anna Majewska-Sawka; María Isabel Rodríguez-García (Planta, 2013)

Improving performance of Cytisus striatus on substrates contaminated with hexachlorocyclohexane (HCH) isomers using bacterial inoculants: developing a phytoremediation strategy - C. Becerra-Castro; Á. Prieto-Fernández; P. S. Kidd; N. Weyens; B. Rodríguez-Garrido; M. Touceda-González; M. J. Acea; J. Vangronsveld (Plant and Soil, 2013)

Allele-specific amplification for the detection of ascochyta blight resistance in chickpea - E. Madrid; W. Chen; P. N. Rajesh; P. Castro; T. Millán; J. Gil (Euphytica, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Effect of Storage Conditions on Total Volatile Base Nitrogen Determinations in Fish Muscle Extracts - P. Castro; R. Millán; J. C. Penedo; E. Sanjuán; A. Santana; M. J. Caballero (Journal of Aquatic Food Product Technology, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

The effect of biomaterials and antifungals on biofilm formation by Candida species: a review - M. Cuéllar-Cruz; A. Vega-González; B. Mendoza-Novelo; E. López-Romero; E. Ruiz-Baca; M. A. Quintanar-Escorza; J. C. Villagómez-Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Ticks (Ixodida) on humans from central Panama, Panama (2010–2011) - Sergio E. Bermúdez C.; Angélica Castro; Helen Esser; Yorick Liefting; Gleydis García; Roberto J. Miranda (Experimental and Applied Acarology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

Responses to excess iron in sweet potato: impacts on growth, enzyme activities, mineral concentrations, and anatomy - Janete M. Adamski; Rodrigo Danieloski; Sidnei Deuner; Eugênia J. B. Braga; Luis A. S. de Castro; José A. Peters (Acta Physiologiae Plantarum, 2012)

Phlebodium decumanum is a natural supplement that ameliorates the oxidative stress and inflammatory signalling induced by strenuous exercise in adult humans - Javier Díaz-Castro; Rafael Guisado; Naroa Kajarabille; Carmen García; Isabel M. Guisado; Carlos De Teresa; Julio J. Ochoa (European Journal of Applied Physiology, 2012)

Application of selected microbial consortia combined with inorganic and oleophilic fertilizers to recuperate oil-polluted soil using land farming technology - G. A. Silva-Castro; I. Uad; J. Gónzalez-López; C. G. Fandiño; F. L. Toledo; Concepción Calvo (Clean Technologies and Environmental Policy, 2012)

Recent Progress in Interfacial Tissue Engineering Approaches for Osteochondral Defects - Nathan J. Castro; S. Adam Hacking; Lijie Grace Zhang (Annals of Biomedical Engineering, 2012)

The hisC1 gene, encoding aromatic amino acid aminotransferase-1 in Azospirillum brasilense Sp7, expressed in wheat - Julio Castro-Guerrero; Angelica Romero; José J. Aguilar; Ma. Luisa Xiqui; Jesús O. Sandoval; Beatriz E. Baca (Plant and Soil, 2012)

Further Studies on the Hypothesis of PARP-1 Inhibition as a Strategy for Lessening the Long-Term Effects Produced by Perinatal Asphyxia: Effects of Nicotinamide and Theophylline on PARP-1 Activity in Brain and Peripheral Tissue - C. Allende-Castro; P. Espina-Marchant; D. Bustamante; E. Rojas-Mancilla; T. Neira; M. A. Gutierrez-Hernandez; D. Esmar; J. L. Valdes; P. Morales; P. J. Gebicke-Haerter; M. Herrera-Marschitz (Neurotoxicity Research, 2012)

Treatment of diesel-polluted clay soil employing combined biostimulation in microcosms - G. A. Silva-Castro; L. SantaCruz-Calvo; I. Uad; C. Perucha; J. Laguna; J. Gónzalez-López; C. Calvo (International Journal of Environmental Science and Technology, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Zebrafish (Danio rerio) life-cycle exposure to chronic low doses of ethinylestradiol modulates p53 gene transcription within the gonads, but not NER pathways - J. Soares; L. Filipe C. Castro; M. A. Reis-Henriques; N. M. Monteiro; M. M. Santos (Ecotoxicology, 2012)

Obstructive Sleep Apnea Severity Correlates with Cellular and Plasma Oxidative Stress Parameters and Affective Symptoms - C. M. R. Franco; A. M. J. Lima; L. Ataíde; O. G. Lins; C. M. M. Castro; A. A. Bezerra; M. F. de Oliveira; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Limits of pine forest distribution at the treeline: herbivory matters - A. Herrero; R. Zamora; J. Castro; J. A. Hódar (Plant Ecology, 2012)

Development of a Design Space for a Unit Operation: Illustration Using Compression-Mix Blending Process for the Manufacture of a Tablet Dosage Form - Shiva G. Kapsi; Lan D. Castro; Fran X. Muller; Thomas J. Wrzosek (Journal of Pharmaceutical Innovation, 2012)

Evolutionary Implications of Dental Eruption in Dasypus (Xenarthra) - Martin R. Ciancio; Mariela C. Castro; Fernando C. Galliari; Alfredo A. Carlini; Robert J. Asher (Journal of Mammalian Evolution, 2012)

Agrobacterium rhizogenes-dependent production of transformed roots from foliar explants of pepper (Capsicum annuum): a new and efficient tool for functional analysis of genes - J. Aarrouf; P. Castro-Quezada; S. Mallard; B. Caromel; Y. Lizzi; V. Lefebvre (Plant Cell Reports, 2012)

Concentration of ascorbic acid and innate immune effectors in Engraulis ringens and Strangomera bentincki during their main spawning period (2007–2008) in the Humboldt current system off Chile - M. C. Krautz; L. R. Castro; M. González; J. C. Vera; H. E. González (Marine Biology, 2012)

Using dissolved oxygen concentrations to determine mixed layer depths in the Bellingshausen Sea - K. Castro-Morales; J. Kaiser (Ocean Science, 2012)
Concentrations of oxygen (O2) and other dissolved gases in the oceanic mixed layer are often used to calculate air-sea gas exchange fluxes. The mixed layer depth (zmix) may be defined using criteria based on temperature or density differences to a reference depth near the ocean surface. However, temperature criteria fail in regions with strong haloclines such as the Southern Ocean where heat, freshwater and momentum fluxes interact to establish mixed layers. Moreover, the time scales of air-sea exchange differ for gases and heat, so that zmix defined using oxygen may be different than zmix defined using temperature or density. Here, we propose to define an O2-based mixed layer depth, zmix(O2), as the depth where the relative difference between the O2 concentration and a reference value at a depth equivalent to 10 dbar equals 0.5 %. This definition was established by analysis of O2 profiles from the Bellingshausen Sea (west of the Antarctic Peninsula) and corroborated by visual inspection. Comparisons of zmix(O2) with zmix based on potential temperature differences, i.e., zmix(0.2 °C) and zmix(0.5 °C), and potential density differences, i.e., zmix(0.03 kg m−3) and zmix(0.125 kg m−3), showed that zmix(O2) closely follows zmix(0.03 kg m−3). Further comparisons with published zmix climatologies and zmix derived from World Ocean Atlas 2005 data were also performed. To establish zmix for use with biological production estimates in the absence of O2 profiles, we suggest using zmix(0.03 kg m−3), which is also the basis for the climatology by de Boyer Montégut et al. (2004).

Impact of water quality on bacterioplankton assemblage along Cértima River Basin (central western Portugal) assessed by PCR–DGGE and multivariate analysis - Daniela R. de Figueiredo; Raquel V. Ferreira; Mário Cerqueira; Teresa Condesso de Melo; Mário J. Pereira; Bruno B. Castro; António Correia (Environmental Monitoring and Assessment, 2012)

Functional dissimilarity of melanomacrophage centres in the liver and spleen from females of the teleost fish Prochilodus argenteus - H. J. Ribeiro; M. S. Procópio; J. M. M. Gomes; F. O. Vieira; R. C. Russo; K. Balzuweit; H. Chiarini-Garcia; Antonio Carlos Santana Castro; E. Rizzo; José Dias Corrêa (Cell and Tissue Research, 2011)

Variability of the monthly European temperature and its association with the Atlantic sea‐surface temperature from interannual to multidecadal scales - S. R. Gámiz‐Fortis; M. J. Esteban‐Parra; D. Pozo‐Vázquez; Y. Castro‐Díez (International Journal of Climatology, 2011)
The relationships between the main patterns of variability of the Atlantic sea‐surface temperatures (SSTs) and the European land‐surface temperatures (LSTs) at interannual‐to‐multidecadal time scales are investigated along the period 1872–2004. Principal component analysis (PCA) is used firstly to obtain the main spatio‐temporal patterns of variability of the LSTs and SSTs. Singular Spectral Analysis (SSA) is then used to decompose the time series associated with these patterns into nonlinear trends and quasi‐periodic oscillations, searching for common oscillatory modes to the SSTs and LSTs. The potential predictability of the LSTs based on the SSTs is also analysed. Regarding the SSA results, three robust oscillations of periods around 13.7, 7.5 and 5.2 years, present both in the Atlantic SSTs and north‐western European LSTs, were isolated. These oscillations were found to be associated mainly with a quadripolar SST pattern in the North Atlantic region, usually related to the North Atlantic Oscillation (NAO) atmospheric mode of variability. The predictability study revealed that the SSTs of the Atlantic Ocean are able to account for about 12% of the north‐western European LSTs variance. Additionally, an oscillatory component with period around 3.6 years was identified, but no significant connection between SST and LST was found for this mode. In addition, at this time scale, we find that the El Niño‐Southern Oscillation (ENSO) is leading the Atlantic SST quadripolar pattern by 6 months. Finally, the analysis of the nonlinear trends showed the presence of oscillations with periods around 60–100 years, both in the SSTs and LSTs. At these later time scales, our results reveal that the multidecadal behaviour of the southern European LSTs is related to Atlantic Multidecadal Oscillation (AMO) during the period 1872–1940, unlike the northern and eastern European LSTs, while, during the period 1941–2004, the AMO sign seems to be present in whole Europe. Copyright © 2010 Royal Meteorological Society

Soluble Fas and Fas ligand in HIV/HCV coinfected patients and impact of HCV therapy - M. Guzmán-Fulgencio; J. Berenguer; M. García-Álvarez; D. Micheloud; J. C. López; J. Cosín; I. Fernández de Castro; P. Catalán; P. Miralles; S. Resino (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Erratum to: A segregation distortion locus located on linkage group 4 of the chickpea genetic map - P. Castro; J. Rubio; A. Cabrera; T. Millán; J. Gil (Euphytica, 2011)

A segregation distortion locus located on linkage group 4 of the chickpea genetic map - P. Castro; J. Rubio; A. Cabrera; T. Millán; J. Gil (Euphytica, 2011)

Morphological, morphometric, meristic and osteological evidence for two species of hake (Actinopterygii: Gadiformes: Merluccius ) in Argentinean waters - J. M. Díaz de Astarloa; S. I. Bezzi; M. González Castro; E. Mabragaña; D. Hernández; S. M. Delpiani; D. E. Figueroa; M. B. Cousseau; M. Y. Deli Antoni; L. Tringali (Journal of Fish Biology, 2011)
Morphologically, both classic and landmark‐based morphometry and meristic analyses of 241 specimens of Merluccius , along with the re‐examination of six paratype specimens of Merluccius hubbsi , the holotype and three paratypes of Merluccius patagonicus and the syntype of Merluccius australis revealed the presence of only two species of Merluccius in Argentinean waters. Internal structures (hyomandibula, urohyal and sagitta otolith) of M. hubbsi were compared to those reported for M. patagonicus and were shown to have identical morphology. Type specimens of M. patagonicus showed a complete overlap in morphometric and meristic characters with M. hubbsi , whereas M. australis had a greater number of second dorsal and anal‐fin rays, and more lateral‐line scales. In addition, M. australis had a smaller eye and longer snout than M. hubbsi and M. patagonicus . The results indicate that there is no evidence for a third hake species in Argentinean waters. Merluccius patagonicus is a synonym of M. hubbsi .

Phylogeography and conservation of the bull shark (Carcharhinus leucas) inferred from mitochondrial and microsatellite DNA - S. A. Karl; A. L. F. Castro; J. A. Lopez; P. Charvet; G. H. Burgess (Conservation Genetics, 2011)

Polymorphic microsatellite loci for the Balearic Island Lizard Podarcis lilfordi (Squamata: Lacertidae) - P. Bloor; V. Rodríguez; B. Terrasa; R. P. Brown; V. Pérez-Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Conservation Genetics Resources, 2011)

Infection and mortality of Penaeus vannamei at extreme salinities when challenged with Mexican yellow head virus - F Navarro‐Nava; R Castro‐Longoria; J M Grijalva‐Chon; J Ramos‐Paredes; J De la Rosa‐Vélez (Journal of Fish Diseases, 2011)

Use of Raptors for Biomonitoring of Heavy Metals: Gender, Age and Tissue Selection - I. Castro; J. R. Aboal; J. A. Fernández; A. Carballeira (Bulletin of Environmental Contamination and Toxicology, 2011)

Development of chickpea near-isogenic lines for fusarium wilt - P. Castro; F. Pistón; E. Madrid; T. Millán; J. Gil; J. Rubio (Theoretical and Applied Genetics, 2010)

A new genotype of Lymphocystivirus isolated from cultured gilthead seabream, Sparus aurata L., and Senegalese sole, Solea senegalensis (Kaup) - I Cano; E J Valverde; B Lopez‐Jimena; M C Alonso; E Garcia‐Rosado; C Sarasquete; J J Borrego; D Castro (Journal of Fish Diseases, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Diversity of phytoseiid mites (Acari: Mesostigmata: Phytoseiidae) in the Atlantic Forest of São Paulo - T. M. M. G. De Castro; G. J. De Moraes (Systematics and Biodiversity, 2010)

Cytogenetics of Alismataceae and Limnocharitaceae: CMA/DAPI banding and 45S rDNA sites - L. L. Feitoza; M. I. G. Martins; A. A. J. F. Castro; L. P. Félix; R. Carvalho (Plant Systematics and Evolution, 2010)

Management units of brown trout from Galicia (NW: Spain) based on spatial genetic structure analysis - Román Vilas; C. Bouza; J. Castro; A. López; P. Martínez (Conservation Genetics, 2010)

The western Mediterranean climate: how will it respond to global warming? - Dario Camuffo; C. Bertolin; N. Diodato; M. Barriendos; F. Dominguez-Castro; C. Cocheo; A. della Valle; E. Garnier; M. -J. Alcoforado (Climatic Change, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Detection of infectious pancreatic necrosis virus (IPNV) from asymptomatic redbanded seabream, Pagrus auriga Valenciennes, and common seabream, Pagrus pagrus (L.), using a non‐destructive procedure - B Lopez‐Jimena; E Garcia‐Rosado; C Infante; I Cano; M Manchado; D Castro; J J Borrego; M C Alonso (Journal of Fish Diseases, 2010)
A non‐destructive procedure based on nested RT‐PCR and dot‐blot hybridization has been developed for the detection of asymptomatic IPNV‐carrier fish. The pair of primers designed for RT‐PCR amplified a 599‐bp fragment of the pVP2 region within the polyprotein gene, resulting in the detection of IPNV genotype III.1. The use of a nested RT‐PCR allowed the amplification of IPNV genotypes III.1 and I.2. In addition, a 191‐bp probe was designed for hybridization studies used in combination with the nested RT‐PCR. The application of the nested RT‐PCR to analyse blood samples from asymptomatic redbanded seabream, Pagrus auriga , and common seabream, P. pagrus , specimens showed a 53.1% and 77.8% prevalence of IPNV‐carriers, respectively. The combination of nested RT‐PCR and dot‐blot hybridization increased the detection rates up to 100% for redbanded seabream and 94.4% for common seabream. Therefore, the protocol described in this study is highly sensitive and specific for the detection of IPNV in asymptomatic carrier fish, and, in addition, the results demonstrate the carrier state in two newly cultured sparid species in southern Spain.

Life cycle and behaviour of the predaceous mite Cunaxatricha tarsospinosa (Acari: Prostigmata: Cunaxidae) - Tatiane M. M. G. de Castro; Gilberto J. de Moraes (Experimental and Applied Acarology, 2010)

Histopathology of Rhipicephalus sanguineus (Acari: Ixodidae) ticks fed on resistant hosts - Viviane Aparecida Veronez; Márcio Botelho de Castro; Gervásio H. Bechara; Matias P. J. Szabó (Experimental and Applied Acarology, 2010)

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Seagrass Importance in Food Provisioning Services: Fish Stomach Content as a Link between Seagrass Meadows and Local Fisheries - M De la Torre-Castro; M Björk; J Eklöf; P Rönnbäck (Western Indian Ocean Journal of Marine Science, 2009)

Genotoxic activity of Eucalyptus globulus essential oil in Aspergillus nidulans diploid cells - C. T. Miyamoto; J. Rocha De Sant’anna; C. C. Da Silva Franco; M. M. Cunico; O. G. Miguel; L. C. Côcco; C. I. Yamamoto; C. Corrêa; M. A. A. De Castro-Prado (Folia Microbiologica, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Relationship between geomorphology and contamination with weathered hydrocarbons in an old river levee/marsh association - R. H. Adams; D. Olán-Castro; F. J. Guzmán-Osorio; I. J. Diaz-Ramírez (International Journal of Environmental Science and Technology, 2009)

2D versus 3D in the kinematic analysis of the horse at the trot - F. Miró; R. Santos; J. L. Garrido-Castro; A. M. Galisteo; R. Medina-Carnicer (Veterinary Research Communications, 2009)

Relationship Between pH and Stream Water Total Mercury Concentrations in Shenandoah National Park - C. W. Moore; B. J. Cosby; J. N. Galloway; M. S. Castro (Water, Air, & Soil Pollution, 2009)

High Ag-NOR-site variation associated to a secondary contact in brown trout from the Iberian Peninsula - P. Martínez; J. Castro; B. G. Pardo; C. Bouza; M. Hermida; R. Vilas (Genetica, 2009)

Biology and life cycle of Amblyomma incisum (Acari: Ixodidae) - Matias Pablo J. Szabó; Lucas de F. Pereira; Márcio B. Castro; Marcos V. Garcia; Gustavo S. Sanches; Marcelo B. Labruna (Experimental and Applied Acarology, 2009)

A New Developmental Toxicity Test for Pelagic Fish Using Anchoveta (Engraulis ringens J.) - A. Llanos-Rivera; L. R. Castro; J. Silva; E. Bay-Schmith (Bulletin of Environmental Contamination and Toxicology, 2009)

First isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata (Moreau) - J R López; S Núñez; B Magariños; N Castro; J I Navas; R De La Herran; A E Toranzo (Journal of Fish Diseases, 2009)
The first isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata, is reported. The pathogen was recovered from ulcers of cultured fish, from three different outbreaks. The six isolates obtained were biochemically and serologically characterized and diagnosis was confirmed by polymerase chain reaction using specific primers and partial 16S rRNA gene sequencing. The isolates constituted a homogeneous phenotypic group; however, they belong to two of the different serotypes described within this species. A virulence evaluation of the isolates using Wedge sole fry was also performed.

Cytogenetics of Alismatales s.s.: chromosomal evolution and C-banding - L. L. Feitoza; L. P. Felix; A. A. J. F. Castro; R. Carvalho (Plant Systematics and Evolution, 2009)

Phagocytosis, Oxidative Burst, and Produced Reactive Species are Affected by Iron Deficiency Anemia and Anemia of Chronic Diseases in Elderly - I. M. M. Paino; J. C. Miranda; C. M. Marzocchi-Machado; E. J. Cesarino; F. A. de Castro; A. M. de Souza (Biological Trace Element Research, 2009)

Inhibition of Pichia stipitis fermentation of hydrolysates from olive tree cuttings - Manuel J. Díaz; Encarnación Ruiz; Inmaculada Romero; Cristóbal Cara; Manuel Moya; Eulogio Castro (World Journal of Microbiology and Biotechnology, 2009)

Silage from maize (Zea mays), annual ryegrass (Lolium multiflorum) or their mixture in the dry season feeding of grazing dairy cows in small-scale dairy production systems in the Highlands of Mexico - J. P. Anaya-Ortega; G. Garduño-Castro; A. Espinoza-Ortega; R. Rojo-Rubio; C. M. Arriaga-Jordán (Tropical Animal Health and Production, 2009)

Nitrate content of lettuce ( Lactuca sativa L.) after fertilization with sewage sludge and irrigation with treated wastewater - E. Castro; M.P. Mañas; J. De Las Heras (Food Additives & Contaminants: Part A, 2009)

Application of in situ detection techniques to determine the systemic condition of lymphocystis disease virus infection in cultured gilt‐head seabream, Sparus aurata L. - I Cano; P Ferro; M C Alonso; C Sarasquete; E Garcia‐Rosado; J J Borrego; D Castro (Journal of Fish Diseases, 2009)
Immunohistochemistry (IHC) and in situ hybridization (ISH) techniques have been used for the detection of lymphocystis disease virus (LCDV) in formalin‐fixed, paraffin‐embedded tissues from gilt‐head seabream, Sparus aurata L. Diseased and recovered fish from the same population were analysed. IHC was performed with a polyclonal antibody against a 60‐kDa viral protein. A specific digoxigenin‐labelled probe, obtained by PCR amplification of a 270‐bp fragment of the gene coding the LCDV major capsid protein, was used for ISH. LCDV was detected in skin dermis and gill lamellae, as well as in several internal organs such as the intestine, liver, spleen and kidney using both techniques. Fibroblasts, hepatocytes and macrophages seem to be target cells for virus replication. The presence of lymphocystis cells in the dermis of the skin and caudal fin, and necrotic changes in the epithelium of proximal renal tubules were the only histological alterations observed in fish showing signs of the disease.

The occurrence of Mt Barca flank eruption in the evolution of the NW periphery of Etna volcano (Italy) - S. Branca; P. Del Carlo; M. D. Lo Castro; E. De Beni; J. Wijbrans (Bulletin of Volcanology, 2009)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)

Detection of the yellow‐head virus (YHV) in wild blue shrimp, Penaeus stylirostris , from the Gulf of California and its experimental transmission to the Pacific white shrimp, Penaeus vannamei - R Castro‐Longoria; N Quintero‐Arredondo; J M Grijalva‐Chon; J Ramos‐Paredes (Journal of Fish Diseases, 2008)

Inhibition of Ca2+ influx by surfactant in NR8383 alveolar macrophages - R. Castro; X. H. Sun; X.-B. Liu; J. R. Martinez; G. H. Zhang (Inflammation Research, 2008)

Surfactants in sludge-amended agricultural soils: a review - Alicia Fernández Cirelli; Carlos Ojeda; Mariano J. L. Castro; Miquel Salgot (Environmental Chemistry Letters, 2008)

A Novel Approach for Bioremediation of a Coastal Marine Wastewater Effluent Based on Artificial Microbial Mats - J. Zamora-Castro; J. Paniagua-Michel; C. Lezama-Cervantes (Marine Biotechnology, 2008)

Immunosuppressive properties of surfactant in alveolar macrophage NR8383 - J. Kerecman; S. B. Mustafa; M. M. Vasquez; P. S. Dixon; R. Castro (Inflammation Research, 2008)

Microsatellite variation of cassava (Manihot esculenta Crantz) in home gardens of Chibchan Amerindians from Costa Rica - Oscar J. Rocha; Maria E. Zaldivar; Luis Castro; Emilio Castro; Ramiro Barrantes (Conservation Genetics, 2008)

Vaccination of turbot, Psetta maxima (L.), against the protozoan parasite Philasterides dicentrarchi : effects on antibody production and protection - M L Sanmartín; A Paramá; R Castro; S Cabaleiro; J Leiro; J Lamas; J L Barja (Journal of Fish Diseases, 2008)
The efficacy of a vaccine against the fish pathogen Philasterides dicentrarchi was evaluated in turbot by measuring the production of specific antibodies and duration of protection. Four groups of turbot were vaccinated twice, on days 0 and 30, with phosphate‐buffered saline, mineral oil adjuvant, antigen or antigen plus adjuvant. Specific serum antibodies were determined on day 0 and 1 month after the first and the second vaccinations. Protection was evaluated 1 month after the first vaccination and 1 and 5 months after the second vaccination. Serum antibody titres, measured by enzyme‐linked immunosorbent assay, and protection, assessed by challenges, increased significantly 1 month after the second vaccination in the group injected with antigen plus adjuvant and the protection lasted for at least a further 5 months in this group. The relative protection was 77% and 66% 1 and 5 months after the second vaccination, respectively. Administration of antigen or adjuvant separately had no effect on antibody response or protection. The results indicate that emulsion containing antigen plus adjuvant induced durable protection against P. dicentrarchi after the administration of the two vaccinations, and that this preparation can be used as a vaccine against the pathogen.

Detection of Alpha and Gamma-Proteobacteria in Amblyomma triste (Acari: Ixodidae) from Uruguay - José Manuel Venzal; Agustín Estrada-Peña; Aránzazu Portillo; Atilio J. Mangold; Oscar Castro; Carlos G. de Souza; María L. Félix; Laura Pérez-Martínez; Sonia Santibánez; José A. Oteo (Experimental and Applied Acarology, 2008)

Population genetic structure of Earth's largest fish, the whale shark ( Rhincodon typus ) - A. L. F. CASTRO; B. S. STEWART; S. G. WILSON; R. E. HUETER; M. G. MEEKAN; P. J. MOTTA; B. W. BOWEN; S. A. KARL (Molecular Ecology, 2007)
Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks ( Rhincodon typus ), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype ( h = 0.974 ± 0.008) and nucleotide diversity (π = 0.011 ± 0.006). The control region has the largest length variation yet reported for an elasmobranch (1143–1332 bp). Phylogenetic analyses reveal no geographical clustering of lineages and the most common haplotype was distributed globally. The absence of population structure across the Indian and Pacific basins indicates that oceanic expanses and land barriers in Southeast Asia are not impediments to whale shark dispersal. We did, however, find significant haplotype frequency differences (amova, F ST = 0.107, P

Homogenization of long‐term monthly Spanish temperature data - M. Staudt; M. J. Esteban‐Parra; Y. Castro‐Díez (International Journal of Climatology, 2007)
Reliable time‐series is the basic ingredient when analysing climatic changes. However, the errors in real data are frequently of the same order as the signal being sought. Therefore, the available long‐term monthly series of Spanish minimum and maximum temperatures have been compiled from the late 19th century on, in order to compile a high‐quality data set. The series are organized into climatically homogeneous regional groups and, in each group, the detection and adjustment is based on relative homogeneity and an analysis of the stationarity of the whole set of temperature‐difference series. These series are scanned with moving t , Alexandersson, and Mann–Kendall tests. The detected inhomogeneities are adjusted by weighted averages of the regional series. The method is iterative and advances in steps of detection, adjustment, and actualization. Individual inhomogeneous data are discarded and gaps are filled by similar weighted multiple means. For the analysis of the temperature evolution in the Iberian Peninsula, each region is finally represented by one local series and the regional average. The urban effect on minimum temperatures is adjusted by an empirical method, and for Madrid also by a correction derived from new homogenized data. Generally, rigorous homogeneity cannot be achieved because the initial data quality is deficient in many cases and metadata are sparse. Nevertheless, the data homogeneity and quality has been considerably enhanced: the total error margin in a series is of the order of 0.3 °C–0.4 °C, under consideration of a worst‐case error accumulation. On the other hand, the number of inhomogeneities is considerable and their average amplitude is of the order of 1 °C reflecting the much larger error margin in the raw data. The homogenized dataset compiled constitutes an important basis for the subsequent detection of thermal changes in Spain in the last 130 years, on a clearly higher confidence level than before. Copyright © 2007 Royal Meteorological Society

Flow cytometric and cytogenetic analyses of Iberian Peninsula Festuca spp. - J. Loureiro; D. Kopecký; S. Castro; C. Santos; P. Silveira (Plant Systematics and Evolution, 2007)

Population genetic structure of the stalked barnacle Pollicipes pollicipes (Gmelin, 1789) in the northeastern Atlantic: influence of coastal currents and mesoscale hydrographic structures - J. Quinteiro; J. Rodríguez-Castro; M. Rey-Méndez (Marine Biology, 2007)

Analysis of a secondary contact between divergent lineages of brown trout Salmo trutta L. from Duero basin using microsatellites and mtDNA RFLPs - P. Martínez; C. Bouza; J. Castro; M. Hermida; B. G. Pardo; L. Sánchez (Journal of Fish Biology, 2007)
The analysis of 12 microsatellite loci in 16 native populations of Salmo trutta from Duero basin evidenced a strong genetic differentiation in accordance with the existence of two divergent Atlantic mtDNA lineages, Atlantic (AT) and Duero (DU). These lineages were observed spatially segregated mainly in the Lower‐course and in the inner part of the basin. Unlike previous isozyme information, microsatellite data suggested a more downstream location of the sharpest genetic divergence in Duero basin and a more complex structure in the inward area. Putative hybrid populations evidenced higher Hardy–Weinberg and gametic disequilibria than pure ones (Pisuerga, Lower‐course), not explained by mixture due to differential immigration pattern across the basin. Hybridization indexes suggested a bimodal pattern of hybridization and a higher weight of Pisuerga region in the genetic composition of hybrid samples in accordance with mtDNA data. The results suggested a limited introgression between AT and DU lineages. Taking into account the time of divergence between both lineages, selection and/or genetic incompatibility appeared necessary to explain the genetic structure observed and the ancient location of DU lineage restricted to this area.

Imaging and Force Spectroscopy on Desmoglein 1 Using Atomic Force Microscopy Reveal Multivalent Ca2+-Dependent, Low-Affinity Trans-Interaction - Jens Waschke; Carlos Menendez-Castro; Paola Bruggeman; Rainer Koob; Masayuki Amagai; Hermann J. Gruber; Detlev Drenckhahn; Werner Baumgartner (The Journal of Membrane Biology, 2007)

Assessment of the spread of chestnut ink disease using remote sensing and geostatistical methods - L. Martins; J. Castro; W. Macedo; C. Marques; C. Abreu (European Journal of Plant Pathology, 2007)

Metal Content of the Gulf of California Blue Shrimp Litopenaeus stylirostris (Stimpson) - M. G. Frías-Espericueta; G. Izaguirre-Fierro; F. Valenzuela-Quiñonez; J. I. Osuna-López; D. Voltolina; G. López-López; M. D. Muy-Rangel; W. Rubio-Castro (Bulletin of Environmental Contamination and Toxicology, 2007)

Validation of a QTL for resistance to ascochyta blight linked to resistance to fusarium wilt race 5 in chickpea (Cicer arietinum L.) - M. Iruela; P. Castro; J. Rubio; J. I. Cubero; C. Jacinto; T. Millán; J. Gil (European Journal of Plant Pathology, 2007)

Simulation of the Askervein flow. Part 2: Large-eddy simulations - A. Silva Lopes; J. M. L. M. Palma; F. A. Castro (Boundary-Layer Meteorology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic diversity of Brazilian strains of porcine circovirus type 2 (PCV-2) revealed by analysis of the cap gene (ORF-2) - A. M. Martins Gomes de Castro; A. Cortez; M. B. Heinemann; P. E. Brandão; L. J. Richtzenhain (Archives of Virology, 2007)

Sucrose and starch catabolism in the anther of Lilium during its development: a comparative study among the anther wall, locular fluid and microspore/pollen fractions - Antonio J. Castro; Christophe Clément (Planta, 2007)

An intercomparison of regional climate simulations for Europe: assessing uncertainties in model projections - M. Déqué; D. P. Rowell; D. Lüthi; F. Giorgi; J. H. Christensen; B. Rockel; D. Jacob; E. Kjellström; M. de Castro; B. van den Hurk (Climatic Change, 2007)

Culture of the histophagous ciliate Philasterides dicentrarchi (Ciliophora: Scuticociliatia) in fish tissues - R Castro; A Paramá; J L Barja; J Leiro; M L Sanmartin; J Lamas (Journal of Fish Diseases, 2007)

Interspecific differentiation and intraspecific substructure in two closely related clupeids with extensive hybridization, Alosa alosa and Alosa fallax - P. Alexandrino; R. Faria; D. Linhares; F. Castro; M. Le Corre; R. Sabatié; J. L. Baglinière; S. Weiss (Journal of Fish Biology, 2006)
In this study, the evolutionary relationships within and among populations of European shads, Alosa alosa and Alosa fallax , was investigated. Screening of allelic variation across eight allozyme loci and sequencing 448 bp of the mtDNA cytochrome b gene in 14 rivers throughout the range of the species supported that the two taxa were independent lineages (1·3% net nucleotide divergence) despite extensive hybridization. Genetic diversity and structure was considerably higher in A. fallax than A. alosa and the former species revealed evidence of distinct lineages in the Mediterranean and Atlantic basins. A Bayesian clustering approach combined with gill raker counts verified that individuals of the two species could be assigned to their parent group with relatively high confidence. Evaluation of hybridization in the Lima and Mondego Rivers in Portugal provided evidence that introgression is extensive but is not currently obscuring (through hybrid swarming) the diagnosability of the two species.

Scaling skeletal muscle function to mass in patients with moderate-to-severe COPD - Carla Malaguti; Luiz E. Nery; Simone Dal Corso; Lara Nápolis; Marcelo Bicalho De Fuccio; Marise Castro; J. Alberto Neder (European Journal of Applied Physiology, 2006)

Fate of carbon in upland grassland subjected to liming using in situ 13CO2 pulse-labelling - Bente Foereid; Lorna A. Dawson; David Johnson; J. Ignacio Rangel-Castro (Plant and Soil, 2006)

Optimization of Lipase-catalysed Synthesis of Butyl Butyrate Using a Factorial Design - J. C. Santos; H. F. de Castro (World Journal of Microbiology and Biotechnology, 2006)

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Characterization of Edwardsiella tarda strains isolated from turbot, Psetta maxima (L.) - N Castro; A E Toranzo; J L Barja; S Núñez; B Magariños (Journal of Fish Diseases, 2006)
The biochemical, serological and molecular characteristics of a group of 21 Edwardsiella tarda strains isolated from turbot, Psetta maxima , in two different areas of Europe were analysed and compared with a total of 13 strains of this bacterial species with different geographical and host origins. All the turbot isolates were biochemically identical to the E. tarda strains included as reference. The use of different techniques including microagglutination, dot blot and Western blot of lipopolysaccharides allowed us to determine that all the turbot isolates constitute an homogeneous and distinctive serological group. Genetic analysis by randomly amplified polymorphic DNA (RAPD) analysis demonstrated that although the E. tarda strains from turbot were compiled in a unique group using the primers P3 and P6, two clonal lineages could be detected when oligonucleotides P4 and P5 were employed.

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

Evolutionary analysis of genetic variation observed in citrus tristeza virus (CTV) after host passage - V. Sentandreu; J. A. Castro; M. A. Ayllón; L. Rubio; J. Guerri; F. González-Candelas; P. Moreno; A. Moya (Archives of Virology, 2006)

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Interaction of stannous chloride leads to alteration in DNA, triphosphate nucleotides and isolated bases - José C. P. de Mattos; Claudia Lage; Flávio J. S. Dantas; Milton O. Moraes; Ana P. M. Nunes; Roberto J. A. C. Bezerra; Mauro V. Castro Faria; Alvaro C. Leitão; Adriano Caldeira-de-Araujo (Molecular and Cellular Biochemistry, 2005)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Isolation in cell culture and detection by PCR‐based technology of IPNV‐like virus from leucocytes of carrier turbot, Scophthalmus maximus (L.) - J M Cutrín; C López‐Vázquez; J G Olveira; S Castro; C P Dopazo; I Bandín (Journal of Fish Diseases, 2005)
A non‐destructive procedure was utilized to determine the infectious pancreatic necrosis virus (IPNV) status of an apparently healthy turbot broodstock. Blood samples were used to detect IPNV by reverse transcriptase‐polymerase chain reaction (RT‐PCR), Southern blot hybridization and nested PCR. In addition, viral isolation from turbot leucocytes was performed. Around 22% of the fish were IPNV positive by RT‐PCR, and this increased to close to 60% when nested PCR was performed. The present report supports the use of blood samples for the detection of IPNV‐like viruses in brood fish. In addition, we demonstrate that it is possible to isolate the virus from the blood of carrier fish, as a non‐lethal detection method, although it is much less sensitive than RT‐PCR and nested PCR as a IPNV‐like strain was isolated from only five of the 15 blood sample pools assayed. The viral isolate was identified as type Dry Mills (genogroup I) by means of restriction fragment length polymorphisms and DNA sequencing.

Intracellular S-adenosylhomocysteine increased levels are associated with DNA hypomethylation in HUVEC - Rita Castro; Isabel Rivera; Carla Martins; Eduard A. Struys; Erwin E. W. Jansen; Nuno Clode; Luís M. Graça; Henk J. Blom; Cornelis Jakobs; Isabel Tavares de Almeida (Journal of Molecular Medicine, 2005)

Persistent Organochlorine Pesticide Levels in Breast Adipose Tissue in Women with Malignant and Benign Breast Tumors - S. M. Waliszewski; M. T. Bermudez; R. M. Infanzon; C. S. Silva; O. Carvajal; P. Trujillo; S. Gomez Arroyo; R. Villalobos Pietrini; V. A. Saldanña; G. Melo; S. Esquivel; F. Castro; et al. (Bulletin of Environmental Contamination and Toxicology, 2005)

Linezolid treatment of ventriculoperitoneal shunt infection without implant removal - P. Castro; A. Soriano; C. Escrich; G. Villalba; M. Sarasa; J. Mensa (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

A Methodological Approach to Assess Cross-scale Relations and Interactions in Agricultural Ecosystems of Argentina - Ernesto F. Viglizzo; Aníbal J. Pordomingo; Daniel Buschiazzo; Mónica G. Castro (Ecosystems, 2005)

The inhibitor of apoptosis gene (iap-3) of Anticarsia gemmatalis multicapsid nucleopolyhedrovirus (AgMNPV) encodes a functional IAP - M. Padilha Carpes; M. E. Batista de Castro; E. Filgueiras Soares; A. Guimarães Villela; F. J. Rivera Pinedo; B. Morais Ribeiro (Archives of Virology, 2005)

Potential use of a Yersinia ruckeri O1 auxotrophic aroA mutant as a live attenuated vaccine - A Temprano; J Riaño; J Yugueros; P González; L de Castro; A Villena; J M Luengo; G Naharro (Journal of Fish Diseases, 2005)
The aroA gene of Yersinia ruckeri , which encodes 5‐enolpyruvylshikimate 3‐phosphate synthase, was insertionally inactivated with a DNA fragment containing a kanamycin resistance determinant and reintroduced by allelic exchange into the chromosome of Y. ruckeri 21102 O1 by means of the suicide vector pIVET8. The Y. ruckeri aroA ::Kan r mutant was highly attenuated when inoculated intraperitoneally into rainbow trout, with a 50% lethal dose of >5 × 10 7 CFU. The mutants were not recoverable from the internal organs 48 h post‐inoculation or later. The vaccination of rainbow trout with the AroA mutant as a live vaccine conferred significant protection (relative percentage survival = 90%) against the pathogenic wild‐type strain of Y. ruckeri.

Ancestral origins of the prion protein gene D178N mutation in the Basque Country - Ana B. Rodríguez-Martínez; Christian Barreau; Isabelle Coupry; Jordi Yagüe; Raquel Sánchez-Valle; Luis Galdós-Alcelay; Agustín Ibáñez; Antón Digón; Ignacio Fernández-Manchola; Cyril Goizet; Azucena Castro; Nerea Cuevas; et al. (Human Genetics, 2005)

Behaviour of hatchery‐reared and wild‐caught 4th and 5th stage American lobsters, Homarus americanus - Kathleen M. Castro; J. Stanley Cobb (New Zealand Journal of Marine and Freshwater Research, 2005)
Behavioural deficiencies in 4th and 5th stage hatchery‐reared lobsters were examined using time budget analysis and predator trials. Hatchery‐reared 4th stage lobsters were found to behave differently than wild‐caught lobsters and differences existed between hatchery‐reared lobsters from different sources. Local hatchery‐reared 4th stage lobsters spent less time on shelter and suffered higher predator rates in laboratory trials than both wild‐caught 4th stage and lobsters reared in a hatchery in Maine. Fifth stage hatchery‐reared lobsters spent significantly more time in shelter than their wild‐caught counterparts. These differences may be attributable to the lack of development of proper predator‐avoidance behaviour and need to be understood and corrected to maximise the effect of enhancement projects.

Stable isotope probing analysis of the influence of liming on root exudate utilization by soil microorganisms - J. Ignacio Rangel‐Castro; Ken Killham; Nick Ostle; Graeme W. Nicol; Ian C. Anderson; Charlie M. Scrimgeour; Phil Ineson; Andy Meharg; Jim I. Prosser (Environmental Microbiology, 2005)
Summary Rhizosphere microorganisms play an important role in soil carbon flow, through turnover of root exudates, but there is little information on which organisms are actively involved or on the influence of environmental conditions on active communities. In this study, a 13 CO 2 pulse labelling field experiment was performed in an upland grassland soil, followed by RNA‐stable isotope probing (SIP) analysis, to determine the effect of liming on the structure of the rhizosphere microbial community metabolizing root exudates. The lower limit of detection for SIP was determined in soil samples inoculated with a range of concentrations of 13 C‐labelled Pseudomonas fluorescens and was found to lie between 10 5 and 10 6 cells per gram of soil. The technique was capable of detecting microbial communities actively assimilating root exudates derived from recent photo‐assimilate in the field. Denaturing gradient gel electrophoresis (DGGE) profiles of bacteria, archaea and fungi derived from fractions obtained from caesium trifluoroacetate (CsTFA) density gradient ultracentrifugation indicated that active communities in limed soils were more complex than those in unlimed soils and were more active in utilization of recently exuded 13 C compounds. In limed soils, the majority of the community detected by standard RNA‐DGGE analysis appeared to be utilizing root exudates. In unlimed soils, DGGE profiles from 12 C and 13 C RNA fractions differed, suggesting that a proportion of the active community was utilizing other sources of organic carbon. These differences may reflect differences in the amount of root exudation under the different conditions.

Isolation of lymphocystis disease virus from sole, Solea senegalensis Kaup, and blackspot sea bream, Pagellus bogaraveo (Brünnich) - M C Alonso; I Cano; E Garcia‐Rosado; D Castro; J Lamas; J L Barja; J J Borrego (Journal of Fish Diseases, 2005)
Two viruses were isolated from cultured sole, Solea senegalensis , and wild blackspot sea bream, Pagellus bogaraveo , and preliminarily characterized as lymphocystis disease viruses (LCDVs). Viral isolates were characterized by morphological, biochemical and biophysical properties. In addition, the susceptibility of four fish cell lines was also tested. LCDV isolates developed cytopathic effects on the SAF‐1 cell line at 5 and 6 days post‐infection and reached titres of 10 6 TCID 50 mL −1 . The antigenic and structural protein analysis of the two new LCDV isolates showed identical profiles to that obtained for LCDV strain Leetown NFH (ATCC VR‐342), used as a reference viral strain, and for an LCDV isolate collected from gilt‐head sea bream, Sparus aurata , cultured in southern Spain. Molecular confirmation was performed by polymerase chain reaction. Specific primers for LCDV produced a 270‐bp DNA fragment, the expected size for LCDV.

Flux and turnover of fixed carbon in soil microbial biomass of limed and unlimed plots of an upland grassland ecosystem - J. Ignacio Rangel‐Castro; Jim I. Prosser; Nick Ostle; Charlie M. Scrimgeour; Ken Killham; Andy A. Meharg (Environmental Microbiology, 2005)
Summary The influence of liming on rhizosphere microbial biomass C and incorporation of root exudates was studied in the field by in situ pulse labelling of temperate grassland vegetation with 13 CO 2 for a 3‐day period. In plots that had been limed (CaCO 3 amended) annually for 3 years, incorporation into shoots and roots was, respectively, greater and lower than in unlimed plots. Analysis of chloroform‐labile C demonstrated lower levels of 13 C incorporation into microbial biomass in limed soils compared to unlimed soils. The turnover of the recently assimilated 13 C compounds was faster in microbial biomass from limed than that from unlimed soils, suggesting that liming increases incorporation by microbial communities of root exudates. An exponential decay model of 13 C in total microbial biomass in limed soils indicated that the half‐life of the tracer within this carbon pool was 4.7 days. Results are presented and discussed in relation to the absolute values of 13 C fixed and allocated within the plant–soil system.

Plant species richness and spatial organization at different small scales in western Mediterranean landscapes - J. M. De. Miguel; L. Ramírez-Sanz; I. Castro; M. Costa-Tenorio; M. A. Casado; F. D. Pineda (Plant Ecology, 2005)

Construction and characterization of a plant transformation-competent BIBAC library of the black Sigatoka-resistant banana Musa acuminata cv. Tuu Gia (AA) - E. Ortiz-Vázquez; D. Kaemmer; H-B. Zhang; J. Muth; M. Rodríguez-Mendiola; C. Arias-Castro; Andrew James (Theoretical and Applied Genetics, 2005)

Limited nucleotide divergence over large spatial scales in the asterinid sea star Patiriella exigua - D. J. Colgan; M. Byrne; E. Rickard; L. R. Castro (Marine Biology, 2005)

El Niño–southern oscillation events and associated European winter precipitation anomalies - D. Pozo‐Vázquez; S. R. Gámiz‐Fortis; J. Tovar‐Pescador; M. J. Esteban‐Parra; Y. Castro‐Díez (International Journal of Climatology, 2005)
The winter precipitation anomalies in the European area have been analysed over the period 1900–98 based on the El Niño–Southern oscillation (ENSO) state. A set of winter and autumn ENSO events is first selected using the Sea‐Surface temperature (SST) data of the Niño 3 region, with the constraint that the ENSO event is well developed during the winter and autumn of study, and that it is an extreme event. Cold and warm ENSO events and periods that can be regarded as normal are selected. For the selected winter ENSO events and for the winter following the selected autumn ENSO events, composites of European winter precipitation anomalies have been obtained and compared with each other. A study of the consistency among events of the relationship between ENSO and precipitation anomalies was also carried out. The analysis of the winter precipitation anomalies based on the selected winter ENSO events shows the existence, for the European area and during La Niña events, of a statistically significant precipitation anomaly pattern with positive precipitation anomalies north of the British Isles and in the Scandinavian area and negative anomalies in southern Europe, resembling the precipitation pattern associated with the positive phase of the North Atlantic oscillation (NAO). Particularly, for the southwestern area of the Iberian Peninsula, the negative anomaly reaches 20% of the winter average precipitation. The consistency analysis shows that this precipitation pattern is not the result of a few major events, but rather that it is stable and qualitatively similar to that found during the positive phase of the NAO. A non‐linear response to ENSO is found in the eastern Mediterranean area: negative precipitation anomalies are found, having similar amplitude anomalies, both during El Niño and La Niña events. The analysis of the precipitation anomalies for the winter following the selected autumn ENSO events shows very similar results to those found for the previous analysis, thus suggesting the existence of a potential source of seasonal forecasting of European precipitation. An analysis of the sensitivity of the precipitation anomalies to the strength of the ENSO events shows that, when the strength of the ENSO increases, the magnitude of the rainfall anomalies does not change, but the area influenced and the coherence between events do increase slightly. Copyright © 2005 Royal Meteorological Society

Carbon flow in an upland grassland: effect of liming on the flux of recently photosynthesized carbon to rhizosphere soil - J. Ignacio Rangel‐Castro; Jim I. Prosser; Charlie M. Scrimgeour; Pete Smith; Nick Ostle; Phil Ineson; Andy Meharg; Ken Killham (Global Change Biology, 2004)
The effect of liming on the flow of recently photosynthesized carbon to rhizosphere soil was studied using 13 CO 2 pulse labelling, in an upland grassland ecosystem in Scotland. The use of 13 C enabled detection, in the field, of the effect of a 4‐year liming period of selected soil plots on C allocation from plant biomass to soil, in comparison with unlimed plots. Photosynthetic rates and carbon turnover were higher in plants grown in limed soils than in those from unlimed plots. Higher δ 13 C‰ values were detected in shoots from limed plants than in those from unlimed plants in samples clipped within 15 days of the end of pulse labelling. Analysis of the aboveground plant production corresponding to the 4‐year period of liming indicated that the standing biomass was higher in plots that received lime. Lower δ 13 C‰ values in limed roots compared with unlimed roots were found, whereas no significant difference was detected between soil samples. Extrapolation of our results indicated that more C has been lost through the soil than has been gained via photosynthetic assimilation because of pasture liming in Scotland during the period 1990–1998. However, the uncertainty associated with such extrapolation based on this single study is high and these estimates are provided only to set our findings in the broader context of national soil carbon emissions.

High CO2 Levels in Boreholes at El Teide Volcano Complex (Tenerife, Canary Islands): Implications for Volcanic Activity Monitoring - V. Soler; J. A. Castro-Almazán; R. T. Viñas; A. Eff-Darwich; S. Sánchez-Moral; C. Hillaire-Marcel; I. Farrujia; J. Coello; J. de la Nuez; M. C. Martín; M. L. Quesada; E. Santana (Pure and Applied Geophysics, 2004)

North Atlantic oscillation influence on precipitation, river flow and water resources in the Iberian Peninsula - Ricardo M. Trigo; David Pozo‐Vázquez; Timothy J. Osborn; Yolanda Castro‐Díez; Sonia Gámiz‐Fortis; María Jesus Esteban‐Parra (International Journal of Climatology, 2004)
The Iberian Peninsula precipitation and river flow regimes are characterized by large values of inter‐annual variability, with large disparities between wet and dry years, especially in southern Iberia. This situation is a major problem for water resources management in general, and for the production of hydroelectricity in particular. Hydroelectric production represents, in an average year of precipitation, 20% of the total Spanish electricity production (and 35% for Portuguese production). Its absolute value, however, can vary by a factor of three between wet and dry years. We have assessed the impact of the North Atlantic oscillation (NAO) on winter precipitation and river flow regimes for the three main international Iberian river basins, namely the Douro (north), the Tejo (centre) and the Guadiana (south). Results show that the large inter‐annual variability in the flows of these three rivers is largely modulated by the NAO phenomenon. Throughout most of the 20th century, the January‐to‐March river flow is better correlated with the December to February (DJF) NAO index than is the simultaneous (DJF) river flow. Correlation values for the period 1973–98 are highly significant (−0.76 for Douro, −0.77 for Tejo and −0.79 for Guadiana), being consistently of higher magnitude than those obtained over previous decades. This impact of the NAO on winter river flow was quantified in terms of total Spanish potential hydroelectricity production. The important control exerted by the NAO and the recent positive trend in the NAO index contribute to a significant decrease in the available flow. This reduction represents an important hazard for the two Iberian economies because of its negative impact on water‐dependent resources, such as intensive agriculture and hydroelectric power production. Copyright © 2004 Royal Meteorological Society

Nramp1 deletion does not confer susceptibility to Rhodococcus equi infection in mice - Philippe Gros; Lucero Del Castro; Dianna Meyer; Ronald J. Martens; Noah D. Cohen; Jessica Harrington (Immunogenetics, 2004)

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Accumulation, assembly, and digestibility of amarantin expressed in transgenic tropical maize - Q. Rascón-Cruz; S. Sinagawa-García; J. A. Osuna-Castro; N. Bohorova; O. Paredes-López (Theoretical and Applied Genetics, 2004)

On the Composition of Airborne Particles Influenced by Emissions of the Volcano Popocatépetl in Mexico - J. C. Jiménez; G. B. Raga; D. Baumgardner; T. Castro; I. Rosas; A. Báez; O. Morton (Natural Hazards, 2004)

Gynogenesis Assessment Using Microsatellite Genetic Markers in Turbot ( Scophthalmus maximus ) - J. Castro; C. Bouza; L. Snchez; R. M. Cal; F. Piferrer; P. Martnez (Marine Biotechnology, 2003)

Assessment of regional seasonal rainfall predictability using the CPTEC/COLA atmospheric GCM - J. A. Marengo; I. F. A. Cavalcanti; P. Satyamurty; I. Trosnikov; C. A. Nobre; J. P. Bonatti; H. Camargo; G. Sampaio; M. B. Sanches; A. O. Manzi; C. A. C. Castro; C. D'Almeida; et al. (Climate Dynamics, 2003)

Distribution of virulence genes in clinical and environmental isolates of Aeromonas spp. - M.R. Chacón; M.J. Figueras; G. Castro-Escarpulli; L. Soler; J. Guarro (Antonie van Leeuwenhoek, 2003)

Sequencing and Characterization of Plasmid pUIBI-1 from Bacillus thuringiensis Serovar entomocidus LBIT-113 - Joel E. Lpez-Meza; J. Eleazar Barboza-Corona; M. Cristina Del Rincn-Castro; Jorge E. Ibarra (Current Microbiology, 2003)

Mapping and pyramiding of qualitative and quantitative resistance to stripe rust in barley - A. J. Castro; F. Capettini; A. E. Corey; T. Filichkina; P. M. Hayes; A. Kleinhofs; D. Kudrna; K. Richardson; S. Sandoval-Islas; C. Rossi; H. Vivar (Theoretical and Applied Genetics, 2003)

Environmental Assessment of Agriculture at a Regional Scale in the Pampas of Argentina - E. F. Viglizzo; A. J. Pordomingo; M. G. Castro; F. A. Lertora (Environmental Monitoring and Assessment, 2003)

Nesting characteristics of the olive ridley turtle ( Lepidochelys olivacea ) in Cabo Pulmo, southern Baja California - M. C. Lpez-Castro; R. Carmona; W. J. Nichols (Marine Biology, 2003)

Simulation of the Askervein Flow. Part 1: Reynolds Averaged Navier–Stokes Equations (k ∈ Turbulence Model) - F. A. Castro; J. M. L. M. Palma; A. Silva Lopes (Boundary-Layer Meteorology, 2003)

Detection of an Intracellular Protease Inhibitor in Archaea - Mara I. Gimnez; Jorge J. Snchez; Rosana E. De Castro (Current Microbiology, 2003)

Dermal Exposure to Pesticides in Greenhouses Workers: Discrimination and Selection of Variables for the Design of Monitoring Programs - A. Garrido Frenich; P. A. Aguilera; F. Egea Gonzalez; M. L. Castro Cano; M. Martinez Galera; J. L. Martinez Vidal; M. Soler (Environmental Monitoring and Assessment, 2002)

Recombinagenic effect of cryptolepine inuvsH +//uvsH + anduvsH//uvsH diploid strains ofAspergillus nidulans - S. J. R. Chiuchetta; M. A. A. Castro-Prado (Folia Microbiologica, 2002)

A general theory on fish aggregation to floating objects: An alternative to the meeting point hypothesis - José J. Castro; José A. Santiago; Ana T. Santana-Ortega (Reviews in Fish Biology and Fisheries, 2002)

Effects of extremely hot days on people older than 65 years in Seville (Spain) from 1986 to 1997 - Díaz J.; García R.; F. Velázquez de Castro; Hernández E.; López C.; Otero A. (International Journal of Biometeorology, 2002)

Microbiological and Sanitary Quality of Recreational Seawaters of Southern Portugal - Lidia P. C. Dionisio; Esther Garcia-Rosado; Lourdes Lopez-Cortes; Dolores Castro; Juan J. Borrego (Water, Air, & Soil Pollution, 2002)

Population dynamics of reintroduced forest birds on New Zealand islands - Doug P. Armstrong; R. Scott Davidson; Wendy J. Dimond; John K. Perrott; Isabel Castro; John G. Ewen; Richard Griffiths; Jason Taylor (Journal of Biogeography, 2002)
Aim We studied dynamics of four populations of New Zealand forest birds for 5–9 years after reintroduction to islands. We primarily aimed to predict whether these populations were viable, and what, if any, management was needed to maintain them. However, the small scale of these islands also provided an opportunity to study density‐dependent population growth over a short time frame. Location We studied New Zealand robin (toutouwai, Petroica australis ) and stitchbird (hihi, Notiomystis cincta ) populations reintroduced to Tiritiri Matangi, a 220‐ha offshore island near Auckland, and saddleback (tieke, Philesturnus carunculatus ) and stitchbird populations reintroduced to Mokoia, a 135‐ha island in Lake Rotorua. These islands are free of mammalian predators, but have highly modified habitat following clearing and regeneration. Methods We closely monitored each population, individually marking all or most of the birds and in some cases experimentally manipulated population density or food supply. We used model selection procedures to understand factors affecting survival, fecundity and dispersal, and developed stochastic simulation models. Results The Tiritiri Matangi robin and Mokoia saddleback populations grew without management and appear to be viable. Both showed strong evidence of density‐dependent growth, with fecundity (saddlebacks) and juvenile survival (both populations) declining with increasing density. Neither stitchbird population appears viable without management and supplementation experiments showed reproduction and/or survival to be limited by food supply. The Tiritiri Matangi population appears viable as long as supplementary feeding continues. However, the Mokoia population has a high mortality rate regardless of supplementary feeding, resulting in tenuous viability even with intensive management. Mokoia stitchbirds suffer from infection by Aspergillus fumigatus , a pathogenic fungus that is prevalent in highly modified habitats and more abundant on Mokoia than Tiritiri Matangi. Main conclusions Some forest birds can thrive in regenerating forest on islands and strong evidence of density dependence can be detected in such populations in as little as 5 years. This allows density‐dependent models to be developed, providing guidance when island populations are harvested for further translocations. Other species are limited by food supply in regenerating environments, a problem potentially overcome by management. However, prevalence of A. fumigatus may render highly modified environments uninhabitable by some species regardless of management.

Phytoremediation of polyaromatic hydrocarbons, anilines and phenols - Patricia J. Harvey; Bruno F. Campanella; Paula M. L. Castro; Hans Harms; Eric Lichtfouse; Anton R. Schäffner; Stanislav Smrcek; Daniele Werck-Reichhart (Environmental Science and Pollution Research, 2002)

The occurrence of Ranzania laevis off the Island of Gran Canaria, the Canary Islands, related to sea warming - J. J. Castro; A. G. Ramos (Journal of Fish Biology, 2002)
Catches of the slender sunfish Ranzania laevis were reported off the coastline of the island of Gran Canaria, the Canary Islands, Spain in May‐June 2001, apparently associated with a sudden west‐east warming process of the sea surface in the central Atlantic.

A geochemical and geophysical approach to derive a conceptual circulation model of CO 2 -rich mineral waters: A case study of Vilarelho da Raia, northern Portugal - Marques J.; Monteiro Santos; Graa R.; Castro R.; Aires-Barros L.; L. Mendes Victor (Hydrogeology Journal, 2001)

Hydrogenated fish fat for grazing dairy cows in summer - M. R. Gallardo; S. E. Valtorta; P. E. Leva; H. C. Castro; J. A. Maiztegui (International Journal of Biometeorology, 2001)

Evaluation of 'Anahuac' wheat mutant lines for aluminum tolerance - A. Tulmann Neto; C.E. de Oliveira Camargo; J. Lopes de Castro; A.W.P. Ferreira Filho (Euphytica, 2001)

The impact of deforestation on the hydrological cycle in the western Mediterranean: an ensemble study with two regional climate models - M. A. Gaertner; O. B. Christensen; J. A. Prego; J. Polcher; C. Gallardo; M. Castro (Climate Dynamics, 2001)

A study of NAO variability and its possible non-linear influences on European surface temperature - D. Pozo-Vázquez; M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Díez (Climate Dynamics, 2001)

Allozymic evidence of parapatric differentiation of brown trout ( Salmo trutta L.) within an Atlantic river basin of the Iberian Peninsula - C. Bouza; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 2001)
The genetic variation of brown trout from Duero, one of the main Atlantic Iberian river basins, was assessed at 34 enzymatic loci in 62 native populations. A strong intrabasin differentiation was detected ( G ST = 0.46; range D : 0–0.066), mainly attributable to the existence of two divergent groups of populations within Duero: southern and northern groups. This divergence was mainly a consequence of the unequal distribution of *75 and *100 alleles at s MDH ‐B1,2* isoloci, which were correlated with substantial differences in genetic diversity among regions. The Lower Course region (nearly fixed for the *100 allele) and Pisuerga River (nearly fixed for the *75 allele) showed lower heterozygosities ( H ≈ 0.8%) in contrast with adjacent areas, which evidenced intermediate frequencies for both alleles and higher heterozygosities ( H : 2.2–3.1%). Vicariance appeared as the more probable explanation for the significant positive correlation detected between genetic and geographical distances in Duero Basin. Genetic relationships with adjacent Iberian drainages indicate a close similarity between the southern group and Cantabric trout, whereas the northern group constitutes an ancient form from this basin. This study confirmed complex genetic relationships in brown trout from northwest Iberia, reasserting the existence of clines at several loci and for genetic diversity. The interaction between Cantabric and Duero trout , as well as the location of the limit of the anadromous form around the 42° N parallel, are both required to understand the genetic characteristics of brown trout from this area.

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

Biological responses of microflora to treatment with CA and/or fumigation - J. L. Zettler; S. Navarro; Maria Fernanda Penteado M. de Castro; J. O. do Vale; Neura Bragnolo; M. F. F. Leitao; Eliane Salvadego Anichiareo; K. A. Mills (Phytoparasitica, 2001)

Lowest effective and optimum poultry manure dose for reclaiming burnt soils: pot experiments - A. Castro; S. J. González-Prieto; M. C. Villar; T. Carballas (Biology and Fertility of Soils, 2000)

Distribution and abundance of co-occurring chthamalid barnacles Chthamalus montagui and Chthamalus stellatus (Crustacea, Cirripedia) on the southwest coast of Portugal - E. B. Sousa; T. Cruz; J. J. Castro (Hydrobiologia, 2000)

Brown trout 5S rDNA maps to chromosome 38 - B. G. Pardo; J. Castro; P. Martínez; L. Sánchez (Chromosome Research, 2000)

Extracellular protease of Natrialba magadii : purification and biochemical characterization - María I. Giménez; Claudia A. Studdert; Jorge J. Sánchez; R. E. De Castro (Extremophiles, 2000)

Morphological comparison of the buccal apparatus in two bivalve commensal Teleostei, Encheliophis dubius and Onuxodon fowleri (Ophidiiformes, Carapidae) - E. Parmentier; J. L. Castro-Aguirre; P. Vandewalle (Zoomorphology, 2000)

PLS and PCR Methods in the Assessment of Coastal Water Quality - P. A. Aguilera; A. Garrido Frenich; H. Castro; J. L. Martinez Vidal (Environmental Monitoring and Assessment, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

A high incidence of Shigella -induced arthritis in a primate species: major histocompatibility complex class I molecules associated with resistance and susceptiblity, and their relationship to HLA-B27 - J. A. Urvater; S. N. McAdam; J. H. Loehrke; T. M. Allen; J. L. Moran; T. J. Rowell; S. Rojo; J.A. López de Castro; J. D. Taurog; D. I. Watkins (Immunogenetics, 2000)

Genotype and phenotype analysis of Friedreich's ataxia compound heterozygous patients - M. De Castro; J. García-Planells; E. Monrós; J. Cañizares; R. Vázquez-Manrique; J.J. Vílchez; M. Urtasun; M. Lucas; G. Navarro; G. Izquierdo; M.D. Moltó; F. Palau (Human Genetics, 2000)

Genetic structure of brown trout, Salmo trutta L., at the southern limit of the distribution range of the anadromous form - C. Bouza; J. Arias; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 1999)
Genetic variation at 33 protein loci was investigated in 41 wild brown trout populations from four river basins in Galicia (northwest Spain) to analyse the amount and distribution of genetic diversity in a marginal area, located in the distribution limit of the anadromous form of this species. The genetic diversity detected within populations ( H between 0 and 6%) lies within the range quoted for this species in previous reports. The Miño, the most southern river basin analysed, showed a significantly lower genetic diversity and the highest genetic differentiation among the river basins studied. The hierarchical gene diversity analysis showed high population differentiation in a restricted area ( G ST = 27%), mostly due to differences among populations within basins ( G SC = 22%). The reduction of G ST observed when the isolated samples were excluded from the analysis ( G ST = 17%) showed the importance of habitat fragmentation on the heterogeneity detected. Gene flow among populations was comparatively evaluated by three indirect methods, which in general revealed low figures of absolute number of migrants per generation, slightly higher than 1. The gene flow among basins reflected a positive relationship with geographical distance. This trend was confirmed by the significant correlation observed between geographical and genetic distances, including all population pairs, which suggests a component of isolation by distance in brown trout genetic structure. Nevertheless, the nonsignificant intrabasin correlation demonstrates the complexity of genetic relationships among populations in this species. The model of genetic structure in brown trout is discussed in the light of the results obtained.

Opioid consumption in Spain - the significance of a regulatory measure - J. García del Pozo; A. Carvajal García-Pando; A. M. Rueda de Castro; M. I. Cano del Pozo; L. H. Martín Arias (European Journal of Clinical Pharmacology, 1999)

Some Results from the Hailpad Network in León (Spain): Noteworthy Correlations among Hailfall Parameters - R. Fraile; J. L. Sánchez; J. L. de la Madrid; A. Castro; J. L. Marcos (Theoretical and Applied Climatology, 1999)

Obtainment of a carbon-13-, nitrogen-15-labelled burnt soil - S. J. González-Prieto; A. Cabaneiro; A. Castro; M. C. Villar; A. Martín; T. Carballas (Biology and Fertility of Soils, 1999)

On the prosthetic groups of the NiFe sulfhydrogenase from Pyrococcus furiosus: topology, structure, and temperature-dependent redox chemistry - Pedro J. Silva; Baltazar de Castro; W. R. Hagen (JBIC Journal of Biological Inorganic Chemistry, 1999)

rDNA RFLPs as genetic markers for resource management in brown trout - J. Castro; B. G. Pardo; L. Sánchez; P. Martínez (Journal of Fish Biology, 1999)
Interesting population‐specific rDNA markers were detected for microgeographical analysis of brown trout Salmo trutta as well as for monitoring stocking practices.

Age constraints to the relationships between magmatism, metamorphism and tectonism in the Aracena metamorphic belt, southern Spain - A. Castro; C. Fernández; H. El-Hmidi; M. El-Biad; M. Díaz; J. de la Rosa; F. Stuart (International Journal of Earth Sciences, 1999)

β-Tubulin accumulation and DNA synthesis are sequentially resumed in embryo organs of cucumber (Cucumis sativus L.) seeds during germination - Hai -Chun Jing; André A. M. van Lammeren; Renato D. de Castro; Raoul J. Bino; Henk W. M. Hilhorst; Steven P. C. Groot (Protoplasma, 1999)

Differentiation of Clams from Fishing Areas as an Approximation to Coastal Quality Assessment - H. Castro; P. A. Aguilera; J. L. Martinez Vidal; E. L. Carrique (Environmental Monitoring and Assessment, 1999)

On the Use of the Jesuit Order Private Correspondence Records in Climate Reconstructions: A Case Study from Castille (Spain) for 1634–1648 A.D. - F. S. Rodrigo; M. J. Esteban-Parra; Y. Castro-Diez (Climatic Change, 1998)

Spatial and temporal patterns of precipitation in Spain for the period 1880–1992 - M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Diez (International Journal of Climatology, 1998)

Stem anatomy and relative growth rate in seedlings of a wide range of woody plant species and types - P. Castro-Díez; J. P. Puyravaud; J. H. C. Cornelissen; P. Villar-Salvador (Oecologia, 1998)

Growth, mineral nutrition and mycorrhizal colonization of red clover and cucumber plants grown in a soil amended with composted urban wastes - M. J. Sáinz; M. T. Taboada-Castro; A. Vilariño (Plant and Soil, 1998)

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions. - Victor M. Fernandez-Soria; Pablo Morales; Maria J. Castro; Belen Suarez; Maria J. Recio; Miguel A. Moreno; Estela Paz-Artal; A. Arnaiz-Villena (Immunogenetics, 1998)

Biochemical alterations in Bradyrhizobium sp USDA 3187 induced by the fungicide Mancozeb - A. Fabra; J. Angelini; A. Donolo; M. Permigiani; S. Castro (Antonie van Leeuwenhoek, 1998)

Plasma membrane redox system activity in tumour cell lines of mammary origins with different proliferation rates - A. E. del Valle; A. del Castillo-Olivares; F. Sánchez-Jiménez; J. Márquez; I. Núñez de Castro; M. A. Medina (Protoplasma, 1998)

Primate Mhc-E and -G alleles - Antonio Arnaiz-Villena; Jorge Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1998)

Numerical analyses of distributions of Iberian and Balearic endemic monocotyledons - J. C. Moreno Saiz; I Castro Parga; H Sainz Ollero (Journal of Biogeography, 1998)
Chorological information concerning 182 taxa of monocotyledons endemic to the Iberian Peninsula and Balearic Islands was compiled and related to the 100×100 km, 50×50 km and 10×10 km UTM grids. Distributions were analysed using multivariate methods (two‐way indicator species analysis and detrended correspondence analysis) for each scale. Comparison of results allows recognition of several floristic elements and sectors (i.e. Balearic, Murcian‐Almerian, south western) common to all three scales, whereas other regions are assigned to different sectors depending on the grid size considered. As a consequence of the increase in detail, characteristics such as number of sectors, the outline of boundaries and continuity or fragmentation of the areas also change. These factors are discussed.

Detection and preliminary characterization of extracellular proteolytic activities of the haloalkaliphilic archaeon Natronococcus occultus - C. A. Studdert; Rosana E. De Castro; Karina Herrera Seitz; Jorge J. Sánchez (Archives of Microbiology, 1997)

Effect of different East Coast Fever control strategies on fertility, milk production and weight gain of Sanga cattle in the Central Province of Zambia - B. Minjauw; J. Otte; A.D. James; J.J. de Castro; P. Sinyangwe (Experimental and Applied Acarology, 1997)

Acoustic behaviour of Abudefduf luridus - J. A. Santiago; J. J. Castro (Journal of Fish Biology, 1997)
Adult males Abudefduf luridus produced sounds during aggressive interactions, although not all aggressive interactions were associated with sounds. Such sounds were always related to characteristic swimming movements during an aggressive display or territorial defence. The sound was a combination of several sonic pulses, with most energy concentrated towards the low end of the spectrum (from

Validation of present-day regional climate simulations over Europe: LAM simulations with observed boundary conditions - J. H. Christensen; B. Machenhauer; R. G. Jones; C. Schär; P. M. Ruti; M. Castro; G. Visconti (Climate Dynamics, 1997)

An objective method for partitioning dendrograms based on entropy parameters - M. A. Casado; L. Ramírez-Sanz; I. Castro; J. M. de Miguel; C. L. de Pablo (Plant Ecology, 1997)

Primate Mhc-E and -G alleles - A. Arnaiz-Villena; J. Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1997)

Follow-up of mercury levels in fish, human hair and urine in the Madeira and Tapajós basins, Amazon, Brazil - O. Malm; J. R. D. Guimarães; M. B. Castro; W. R. Bastos; J. P. Viana; F. J. P. Branches; E. G. Silveira; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

Geographical distribution of B chromosomes in the grasshopper Eyprepocnemis plorans, along a river basin, is mainly shaped by non-selective historical events - J. Cabrero; M. D. Lo´pez–Leo´n; R. Go´mez; A. J. Castro; A. Marti´–Alganza; J. P. M. Camacho (Chromosome Research, 1997)

Agricultural development vs biodiversity conservation: the Mediterranean semiarid vegetation in El Ejido (Almera, southeastern Spain) - J. F. Mota; J. Peas; H. Castro; J. Cabello; J. S. Guirado (Biodiversity and Conservation, 1996)

Direct detection of the porcine reproductive and respiratory syndrome (PRRS) virus by reverse polymerase chain reaction (RT-PCR) - P. Suárez; R. Zardoya; C. Prieto; A. Solana; E. Tabarés; J. M. Bautista; J. M. Castro (Archives of Virology, 1994)

Decreased incorporation of14C-leucine in different liver nuclear protein fractions at early stages of carbon tetrachloride poisoning in the rat - M. Galelli; M. I. Díaz Gómez; J. A. Castro (Archives of Toxicology, 1994)

Antioxidative stress therapy with dithiothreitol tetraacetate I. Protection against carbon tetrachloride induced liver necrosis - M. M. de Mecca; G. D. Castro; J. A. Castro (Archives of Toxicology, 1993)

Late preventive effects of quinacrine on carbon tetrachloride induced liver necrosis - A. González Padrón; E. G. D. de Toranzo; J. A. Castro (Archives of Toxicology, 1993)

Evaluation of prenatal aldrin intoxication in rats - V. L. Castro; M. M. Bernardi; J. Palermo-Neto (Archives of Toxicology, 1992)

Viability of Salmonella spp and indicator microorganisms in seawater using membrane diffusion chambers - Miguel A. Moriigo; Roberto Cornax; Dolores Castro; Eduardo Martinez-Manzanares; Juan J. Borrego (Antonie van Leeuwenhoek, 1990)

Late preventive effects against carbon tetrachloride-induced liver necrosis of the calcium chelating agent calcion - E. C. de Ferreyra; M. C. Villarruel; A. S. Bernacchi; G. Fernández; O. M. de Fenos; J. A. Castro (Archives of Toxicology, 1989)

Evidence for hydroxyl free radical formation during paraquat but not for nifurtimox liver microsomal biotransformation. A dimethyl-sulfoxide scavenging study - G. D. Castro; A. Lopez; J. A. Castro (Archives of Toxicology, 1988)

Effect of inhibitors of the FAD-containing monooxygenase system from rat liver microsomes on monomethylhydrazine metabolism and activation to reactive metabolites - M. I. Diaz Gomez; J. A. Castro (Archives of Toxicology, 1986)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

Metabolism of acetaldehyde and Custers effect in the yeast - J. M. Carrascosa; Mara Dolores Viguera; I. Nez de Castro; W. A. Scheffers (Antonie van Leeuwenhoek, 1981)

l-Alanine as an end product of glycolysis inSaccharomyces cerevisiae growing under different hypoxic conditions - E. Chico; J. S. Olavarría; I. Núñez de Castro (Antonie van Leeuwenhoek, 1978)

The effect of nitrogen fertilization on the composition of the free amino acid pool of poato tubers - J. E. Hoff; C. M. Jones; G. E. Wilcox; Marlene D. Castro (American Journal of Potato Research, 1971)

Developmental genetics of the alcohol dehydrogenase locus of the Japanese quail - S. Ohno; L. Christian; C. Stenius; E. Castro-Sierra; J. Muramoto (Biochemical Genetics, 1969)